Discovery of myrsinane diterpenoids from Euphorbia monostyla with cytotoxic potential - Atabay Kokanov; Hequn Yang; Dan Tang; Artyk Kokanov; Jiangyu Zhao; Haji Akber Aisa (Phytochemistry, 2027)

NMR-guided discovery of bioactive hydroxyl-amide alkaloids from Piper longum L. fruits - Guanghui Gou; Wenli Bao; Liu Liu; Dan Tang; Mingqiang Wang; Jun Li; Haji Akber Aisa (Phytochemistry, 2026)

Promoting the terminal zero-pollution goal of hydrogen fuel cell vehicles: A stochastic evolutionary game analysis - Dan Zhao; Ya Zhang; Ye-kai Li; He-ping Wang; Jin-huan Tang; Jian Wang (Fuel, 2026)

Bioinspired nanocellulose aerogel from spent coffee grounds and natural melanoidins for solar-driven desalination - Dan Wang; Xiaofan Chen; Xueyan Tang; Ruofei Zhu (Desalination, 2026)

Stathmin-mediated autophagy drives the differentiation of dermal fibroblast into myofibroblast under TGFβ1 stimulation - Hui Tang; Luqi Yang; Yanhai Feng; Jianxin Wu; Yi Liang; Zhenglin Li; Lingbo Li; Wan Zhao; Xiaolin Deng; Dan Luo; Xia Lei; Lingfei Li (Molecular Biology Reports, 2026)

Post-stroke endothelial cell plasticity: A transformational lineage from complete to partial EndoMT - Siyi Tang; Cheng Li; Zhijun Yu; Dan Shu; Li Chen; Qiong Yuan (Tissue and Cell, 2026)

Mechanism analysis of enhanced gastrointestinal tolerance of biofilm-state probiotics within calcium alginate by initial medium pH - Yingchun Song; Dan Lv; Qin Liu; Shuo Qi; Yuyu Teng; Chunyu Wang; Wenying Wu; Ying Tang; Jinlong Xu; Junxiang Zhu; Hao Wu; Yongkai Yuan (Food Hydrocolloids, 2026)

Morphology-dependent transport of atmospheric microplastics and the indicator role of polyester fibers across the estuarine- offshore gradient - Fei Jiang; Yan Yang; Pingang Wei; Xuanzheng Wang; Yuang Liu; Xinyue Tang; Zhenming Ge; Dan Zhang; Qiqing Chen (Environmental Pollution, 2026)

A mechanically stable and kinetically optimized organic-inorganic hybrid SEI for ultra-long lifespan zinc metal anodes - Chenyi Cao; Dan Lu; Chao Li; Xin Tan; Tianci Li; Shoubin Zhou; Xueping Tang; Sean C. Smith; Zhao Fu; Hongjia Song; Yunya Liu; Xiangli Zhong; et al. (Chemical Engineering Journal, 2026)

Enhanced bio-electrochemical decolorization of azo dye by an rGO/ polyaniline-modified biocathode: Performance improvement and cathodic microbiome reshaping - Tao Hou; Hong-Li Lu; Naif Abdullah Al-Dhabi; Ai-Hong Chen; Wang-Wang Tang; Meng-Yuan Li; Dan Cui (Journal of Environmental Chemical Engineering, 2026)

Synergistic photo-Fenton catalysis by Fe3Se4 for tetracycline removal: Insights into degradation pathways and reaction mechanisms - Jiawei Deng; Xue Zhu; Sai Teng; Dan Li; Changxin Tang; Tao Wang; Jiren Yuan; Feigao Xu (Journal of Environmental Chemical Engineering, 2026)

Direct electrochemical regeneration of cathode materials from spent lithium-ion batteries: Progress, challenges, and sustainable perspectives - Pengcheng Liu; Haoran Ren; Li Xiao; Pan Tang; Like Zhang; Han Chen; Ruizhi Zhang; Tiansheng Li; Dan Xue; Sheqiang Niu (Journal of Environmental Chemical Engineering, 2026)

Screening of pyrovanadate artificial solid electrolyte interphase for long-lifespan aqueous zinc-ion batteries - Xiaolin Zhang; Yinchuan Wang; Xingjun Li; Fangyan Liu; Jiabei Tang; Junmin Xu; Yue Xu; Chao Huang; Liangliang Liu; Dan Li; Qingdong Ruan; Fangyu Xiong; et al. (Chemical Engineering Journal, 2026)

Heterologous expression of anaerobic reductive dehalogenases: host nanoarchitectonics and synthetic biology optimization - Yashi Lin; Wenxi Yang; Qianwei Tang; Juan Yin; Dan Yang; Yaqing Liu (Bioresource Technology, 2026)

Enzymatic Preparation of Ejiao (Colla Corii Asini) Peptides and Their Preliminary Mechanism of Melanogenesis Inhibition - Xichao Fu; Shangwei Guo; Meijin Li; Zhijie Chen; Dan Liu; Cuicui Men; Na Yang; Xiaobo Duan; Xiaolu Tang; Yaru Zhang; Haibin Liu; Minghao Liu; et al. (International Journal of Peptide Research and Therapeutics, 2026)

The influence of replacing soybean meal with corn gluten meal on the digestive and absorptive capacity and amino acid metabolism of sub-adult grass carp (Ctenopharyngodon idella) - Yan Liu; Xiao-Qiu Zhou; Lin Feng; Wei-Dan Jiang; Hong-Yun Zhang; Yao-Bin Ma; Yang Liu; Shu-Wei Li; Wen-Jie Tang; Cheng-Bo Zhong; Pei Wu (Aquaculture, 2026)

Honokiol Ameliorates Pyroptosis in Bovine Mammary Epithelial Cells via SIRT3-Mediated Inhibition of the NLRP3 Inflammasome - Sha Tang; Yanqiong Wen; Renxin Wu; Xing Shi; Dan Li; Siqing Mao; Xiao Yang; Hang Yu; Lei Tian; Le Zhang; Lei Liu (Tissue and Cell, 2026)

Silica nanoparticles disrupt blood–testis barrier integrity in Sertoli cells by inducing inflammation-mediated p38 MAPK pathway - Ying Wang; Wenpeng Liu; Yichen Wang; Dan Chen; Shoufang Jiang; Jinlong Li; Wenxuan Tang; Ping Lu; Xuan Shang (Reproductive Toxicology, 2026)

Pesticide exposure in Eriocheir sinensis: Oxidative stress, endocrine disruption, gut–hepatopancreas axis impairment, and systems toxicology - Shi-Rong Li; Dan-Dan Bian; Xiang Lu; Shuang-Gui Dai; Bo-Ping Tang; Qiu-Ning Liu (Pesticide Biochemistry and Physiology, 2026)

Anti-obesity function and related comprehensive molecular mechanisms of probiotics: focus more on mitochondrial dysfunction - Junyan Zhang; Yao Zhang; Mengjie Wang; Chao Tang; Huimin Yong; Dan Chen; Juan Kan; Jingguo Xu; Xiaoyu Chen; Jun Liu (Food Bioscience, 2026)

Toward scalable flow-electrode capacitive deionization: An all-channel flow-electrode configuration for enhanced ion transport - Dan Zhao; Yekun Feng; Chongquan Cai; Kai He; Bingjun Liu; Kexin Tang (Desalination, 2026)

Lunar water cycle and D/H fractionation driven by solar wind implantation and micrometeorite impacts - Chuanjiao Zhou; Hong Tang; Xiongyao Li; Bing Mo; Wen Yu; Dan Zhu; Yuanyun Wen; Jianzhong Liu (Earth and Planetary Science Letters, 2026)

Experimental and kinetic study of methane transformation over Fe2O3/Al2O3 oxygen carriers under OCAC-relevant conditions using a novel TG-TFBR method - Xueyu Tang; Weiqin Lu; Bingjun Du; Yang Zhang; Junxiang Chen; Ran Liu; Dan Li; Xiwei Ke; Junfu Lyu (Chemical Engineering Journal, 2026)

Thermosensitive anisotropic electroconductive membrane based on [PMMA]//[W-VO2/PMMA] Janus nanobelt arrays - Xuehua Tang; Xiaona Liu; Yaolin Hu; Xintong Huo; Yunrui Xie; Hong Shao; Qianli Ma; Wensheng Yu; Dan Li; Xiangting Dong (Chemical Engineering Journal, 2026)

Self-powered flexible tactile sensors based on galvanic battery for smart sports and human-machine interaction - Shu-Zheng Liu; Xin-Hua Zhao; Wujing Li; Dan Zhang; Xin-Gui Tang; Qi-Jun Sun (Chemical Engineering Journal, 2026)

Insights into distinct biocarbon assembly and graphitization derived from large-scale bioresource by integrating machine learning with Raman and XRD spectroscopic profiling - Junsheng Yu; Jing Hong; Yujia Fang; Jiacheng Kang; Zongtai Tang; Lei Zhu; Bing Gao; Ling Luo; Dan Sun; Yanting Wang; Liangcai Peng; Hua Yu (Bioresource Technology, 2026)

Multipathway Pesticide Exposure and Cross‐Scale Risk Assessment in Integrated Rice–Crab Aquaculture - Dan‐Dan Bian; Shi‐Rong Li; Bo‐Ping Tang; Qiu‐Ning Liu (Reviews in Aquaculture, 2026)
Integrated rice–crab co‐culture represents a sustainable agroecosystem, yet a critical conflict arises: pesticide applications necessary for rice cultivation undermine the health of the co‐cultured Chinese mitten crab ( Eriocheir sinensis ) and jeopardize system sustainability. To address this challenge, a comprehensive analytical framework is developed, linking multipathway pesticide exposure, molecular toxicity mechanisms, cross‐scale risk assessment, and resilience‐oriented governance. This framework systematically reviews the environmental fate and exposure dynamics of pesticides in paddy fields, as well as their toxicokinetics and tissue‐specific bioaccumulation in E. sinensis . Moving beyond descriptive toxicology, the study integrates “effect hierarchy” and “mechanistic network” perspectives to unravel cascading toxicity pathways, spanning oxidative stress, neuroendocrine disruption, cellular pyroptosis, and immune suppression. The limitations of conventional risk assessment in such a complex system are critically examined, with emphasis on the dual risks to crab population resilience and human food safety. To mitigate these challenges, a novel, mechanism‐informed “Prevent–Intercept–Protect–Adapt (PIPA)” framework is proposed to bolster system resilience, combining green pest control, eco‐engineering, host health enhancement, and smart monitoring. This review enhances theoretical understanding of contaminant impacts in multitrophic systems and offers actionable management strategies to promote the sustainable development of integrated aquaculture.

Correction to: Identification of JAZ1-MYC2 Complex in Lotus corniculatus - Meiliang Zhou; Zhanmin Sun; Jinbo Li; Dan Wang; Yixiong Tang; Yanmin Wu (Journal of Plant Growth Regulation, 2026)

Synergistic SHH activation and BMP inhibition remodel progenitor niche for enhanced hair cell generation - Chunying Li; Dan He; Wenxu Tang; Liping Fu; Xilin Tan; Yao Yao; Xiaolei Yin (Science China Life Sciences, 2026)

Stratospheric intrusion and deep boundary layer coupling drive surface ozone bursts over the Southern Tibetan Plateau during the monsoon season - Ying Shen; Dan Li; Zhixuan Bai; Yinghong Wang; Mengtian Cheng; Yu Wang; Yang Zhang; Deqing Zhuoga; Nima Chuduo; Yaoming Ma; Jianchun Bian; Yuesi Wang; et al. (Science Bulletin, 2026)

Crustal melting and evolution during continental collision in the eastern Central Pamir, Tajikistan - Sharifjon Odinaev; Wei Dan; Andrey K. Litvinenko; Jovid Aminov; Murodov Azamdzhon; Xin Ma; Umed A. Yatimov; Shan-Shan Yang; Guo-Rong Tang; Gong-Jian Tang (Lithos, 2026)

Experimental and numerical investigations on the transport mechanisms of Ti3C2Tx MXene under variable flow and solution chemistry - Liyuan Fu; Tianxin Zhou; Yuxuan Yang; Guohui Yin; Yang Tang; Ziheng Zhang; Tiezhu Sun; Dan Zhou (Journal of Hazardous Materials, 2026)

Preparation of reinforced PVC composites utilizing waste PET fabrics as an alternative to wood materials and potential applications in furniture - Chuanyun Tang; Zhen Shi; Rui Dan; Pu Zheng; Shuo Nie; Xiaoli Wang; Yuanyuan Hu; Quanquan Wang (Journal of Environmental Chemical Engineering, 2026)

Methane production from caproic acid fermentation residuals of food waste in anerobic dynamic membrane bioreactor: A promising route for organic waste valorization - Yunhui Pu; Jingyun Chen; Dan Xu; Yang Luo; Bujiamu Ayi; Yang Li; Yuting Kuang; Qingyuan Wang; Jialing Tang; Abdelfatah Abomohra (Journal of Environmental Management, 2026)

Host-guest construction of hyperbranched poly(quaternary ammonium) triple-action antibacterial coating - Jin Han; Yuehua Tang; Huixin Zhu; Dan Wu; Lei Wang; Kun Shen; Xiaoxue Yin; Zhenping Zhao; Tongdong Shen; Boshi Yu; Dong Xu; Qingquan Xue (Chemical Engineering Journal, 2026)

Analysis of meteorological causes for a spring PM10 pollution episode over Hainan Island, China - Chuan-bo Fu; Li Dan; Jia-xiang Tang; Jin-he Tong (Atmospheric Research, 2026)

Ginsenosides mitigate multi-organ aging: mechanistic insights from a preclinical systematic review and meta-analysis - Ao Li; Hua-Ze Wu; Die-Yi Chen; Yu-Xin Gao; Xiao-Qiang Xiang; Qing-Hui He; Hong-Yan Ma; Dan Tang (Critical Reviews in Food Science and Nutrition, 2026)

Systemic immune evasion and tissue damage underlie the covert pathogenicity of Aeromonas veronii in endangered sturgeons - Jiachen Zhou; Dike Peng; Yuanyuan Tang; Haoyang Liu; Yining Chen; Ye Zhang; Yacheng Hu; Yuanjin Yang; Huifeng Dang; Jianan Xu; Yueping Zheng; Dan Xu (Aquaculture, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

NFIL3-dependent regulation of NF-κB pathway mediates alginic oligosaccharide alleviation of nitrite immunotoxicity in Procambarus clarkii - Xue Zhang; Shuang-Gui Dai; Xiang Lu; Bo-Ping Tang; Dan-Dan Bian; Qiu-Ning Liu (Fish & Shellfish Immunology, 2026)

Ferroportin transporters contribute to nickel hyperaccumulation in Odontarrhena chalcidica - Xuan Cai; Zunhe Hu; Dan Sun; Xinyan Li; Huayuan Feng; Shizhong Wang; Chao Jin; Yetao Tang; Jean-Louis Morel; Mark G.M. Aarts; Lena Q. Ma; Yue Cao; et al. (Bioresource Technology, 2026)

Comparative analysis of chemical compositional profiles and immunomodulatory activity of ginseng in different habitats - Chen-Yue Zeng; Quan-Kuan Dai; Hua-Ze Wu; Ao Li; Yong-Lin Chen; Qing-Hui He; Dan Tang; Hong-Yan Ma (Journal of Natural Medicines, 2026)

Interaction effects and legacy effects of multiple environmental stressors on rice growth and the rhizosphere microbiome - Yifan Zhao; Shuxun Cheng; Rujiong Zeng; Zhiqi Hong; Dan He; Caixian Tang; Zhongmin Dai (Applied Soil Ecology, 2026)

A Parametric Investigation of the Jet Breakup Patterns of a Rotary Sprinkler - Longyu Li; Xinyu Tang; Ziyi Zhao; Dan Zi; Haijun Yan (Irrigation and Drainage, 2026)
The spraying uniformity of a sprinkler is a key hydraulic performance indicator that is closely linked to the jet breakup pattern. The current research has focused mainly on the spraying performance of sprinklers, neglecting the exploration of the breakup morphology of spray jets from sprinklers. High‐speed photography technology is adopted to investigate the entire process of the water jet breaking into droplets in the air under different operating conditions. The jet breakup patterns and their corresponding breakup processes and droplet size distributions are analysed. Through multiple‐condition experimental observations, the jet breakup patterns, including split, column and liquid‐film jets, are identified according to their ejection morphology. The breakup processes differ significantly among the three patterns. Both split and column jets form droplets via continuous ligament rupture under inertia and surface tension, whereas the liquid‐film jet first breaks into ligaments and small droplets under aerodynamic shear, which then coalesce into larger ones. The droplet volume mean diameter follows a nonlinear power function with both working pressure and nozzle diameter. Increasing pressure leads to more complete breakup and a more concentrated size distribution, whereas a larger nozzle diameter flattens the peak of the droplet size distribution, resulting in greater nonuniformity.

Parthenolide accelerates diabetic wound healing through the STAT3 and TNF-α/NF-kappaB pathways - Dan Song; Zhuo Zeng; Hui Tang; Kaiqi Chen; JiaMin Li; Yi Liang; Xia Lei; Hong Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Succinate antagonizes α-ketoglutarate biosynthesis governing myeloid differentiation in normal hematopoiesis and myelodysplastic syndromes - Lingling Zhang; Leiming Liu; Yue Wang; Aoxue Wang; Weitao Tang; Yike Song; Zhuo Zhang; Yaqiong Chen; Dandan Liao; Huixian Liang; Fan Yang; Yiming Liu; et al. (Science Bulletin, 2026)

Pesticide toxicity in Procambarus clarkii: Integrating oxidative stress, immune dysfunction, and gut microbiota disruption - Dan-Dan Bian; Zi-Yi Xing; Xiang Lu; Shuang-Gui Dai; Qiu-Ning Liu; Bo-Ping Tang; Zhi-Gang Wang (Pesticide Biochemistry and Physiology, 2026)

Six previously undescribed bisabolane-type sesquiterpenes from marine derived fungus Aspergillus sp. WHUF04-170 and their antimicrobial activity - Wen-Juan Ding; Hong-Ming Huang; Yu-Ning Liu; Dan-Mei Tian; Ya-Qi Yuan; Ya-Xin Xue; Kui Hong; Hong-Kai Bi; Jin-Shan Tang (Phytochemistry, 2026)

Relationship of catalytic performance and catalyst structure evolution based on pressurized CH4-CO2 reforming reaction over carbon-supported Co-Ir alloy catalysts - Wen Tang; Jing-Pei Cao; Xiao-Yan Zhao; Dan Xie; Kai-Rui Luan; Chang-Jiang Li; Qi-Ming She; Tungalagtamir Bold (Fuel, 2026)

Polyethyleneimine-based magnetic molecularly imprinted polymer for selective enrichment and highly sensitive determination of gallic acid in tea - Xue Tang; Wilson Dumisani Gamuchirai Dube; Wishes Tatenda Machoko; Yaoyao Wang; Dan Wang; Nazia Tarannum; Meriem Fizir; Elhadj Saidou Baldé; Hua He; Deli Xiao; Pierre Dramou (Food Chemistry, 2026)

Hematopoiesis could be improved by correcting aberrant bone marrow macrophages polarization in aplastic anemia patients - Chen-Yuan Li; Dan-Dan Chen; Xin-Yan Zhang; Shu-Qian Tang; Meng-Zhu Shen; Ya-Ting Yu; Zhi-Wei Zhang; Zheng-Li Xu; Yuan-Yuan Zhang; Jin-Song Jia; Lan-Ping Xu; Yu Wang; et al. (Science China Life Sciences, 2026)

Exploring the effects of canola and daylily on deep soil desiccation and jujube tree root traits in semiarid agroforestry systems on the Loess Plateau, China - Qiang Ling; Wenhao Sun; Min Tang; Xiaodong Gao; Xining Zhao; Dan Liu (Plant and Soil, 2026)

Hydroxytyrosol preserves myofibrillar protein integrity in grass carp (Ctenopharyngodon idella): Implications for flesh quality enhancement - Yi-Wei Liao; Pei Wu; Wei-Dan Jiang; Hong-Yun Zhang; Yao-Bin Ma; Yang Liu; Shu-Wei Li; Sheng-Yao Kuang; Ling Tang; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2026)

Sustainable antibiotic degradation in a pH-adaptable heterogeneous electro-Fenton system: Insights into cross-scale mechanism validation - Meiyi Tang; Tao Hou; Hongli Lu; Yutong Xue; Meiqi Ren; Dan Cui (Journal of Environmental Sciences, 2026)

A vacancy-engineered Ce-doped NiCo-LDH electrode material for efficient, selective, and stable groundwater defluorination in FCDI systems - Xingtian Wang; Xinyue Jiang; Pengcheng Tang; Junfeng Zhu; Yuwen Wang; Huiqin Li; Dan He; Yuxuan Ma; Yuhan Qin; Boping Ren; Xiaojing Wang (Chemical Engineering Journal, 2026)

The effects of high-intensity interval training on physical fitness and physiological responses in taekwondo athletes: a systematic review and meta-analysis - Yunzhou Hu; Dinghuang Zhu; Wen Luo; Bingxuan Tang; Yuqing Li; Daniel T. P. Fong; Dan Wang (European Journal of Applied Physiology, 2026)

Comprehensive characterization and genome-resolved insights into the probiotic potential of Bacillus sp. KNSH39 isolated from Litopenaeus vannamei intestine - Patima Permpoonpattana; Sk Injamamul Islam; Luu Tang Phuc Khang; Orathai Dangsawat; Papungkorn Sangsawad; Shu-Dan Yeh; Kritsada Phetduang; Phatthanaphong Therdtatha; Sarayut Onsanit; Nguyen Vu Linh (World Journal of Microbiology and Biotechnology, 2026)

An undescribed jatrophane diterpenoid along with known compounds from Euphorbia sororia with tumour multidrug resistance reversal ability - Hequn Yang; Dan Tang; Jiangyu Zhao; Haji Akber Aisa (Natural Product Research, 2026)

Significantly enhanced Fenton-like degradation activity over oxygen vacancies introduced FeOOH through synergistic effect between active species - Shuang Tian; Xiaowei Hu; Dan Wei; Wei Zhou; Xianjie Chen; Baoguo Xia; Xiaoting Li; Jun Ma; Qiangang Tang (Chemosphere, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Fabrication of Z-scheme ZnIn2S4–CdS heterojunction photocatalyst in-situ grown on novel graphene-based substrate for the photocatalytic reduction of Cr(VI) - Yongming Zhong; Yangting Liao; Rongni Dou; Xiaolong Yu; Jin Tang; Hang Liu; Dan Liu; Yuming Fang; Yilun Luo; Jianteng Sun (Journal of Environmental Chemical Engineering, 2026)

Increased Soil Carbon and Nitrogen Stocks Associate With Stronger Calcium–Microbial and Multi‐Trophic Interactions Under Warming - Dan Xiao; Wei Zhang; David R. Johnson; Peilei Hu; Lin Xu; Mingming Sun; Li Tang; Xunyang He; Jie Zhao; Xionghui Liao; Wanxia Peng; Hongsong Chen; et al. (Global Change Biology, 2026)
Converting cropland to planted forests improves soil organic carbon (SOC) and total nitrogen (TN) storage while contributing to climate change mitigation, primarily through the regulation of belowground organisms and mineral protection such as calcium (Ca). However, the mechanistic pathways linking exchangeable Ca 2+ , soil micro‐food web interactions, and nutrient accumulation under warming remain unclear. Here, we investigated their potential roles in driving the accumulation of mineral‐associated organic matter (MAOM), SOC, and TN in planted forests compared with croplands under warming conditions. Planted forests exhibited higher MAOM, SOC, and TN than cropland and had stronger coupling between carbon and nitrogen. Warming increased MAOM, SOC, and TN in planted forests but reduced SOC in cropland. Compared to cropland, planted forests displayed elevated levels of soil exchangeable Ca 2+ , microbial necromass carbon and nitrogen, stronger Ca–microbial and multi‐trophic associations. Warming further amplified positive Ca–microbial (e.g., bacteria and fungi) and cross‐trophic associations (e.g., nematode–bacteria, nematode–fungi, nematode–protist, and omnivore‐predator–bacteria/fungi) in planted forests by increasing plant productivity, litter biomass, and soil exchangeable Ca 2+ , whereas cropland showed limited responsiveness to temperature changes. In planted forests, soil exchangeable Ca 2+ was positively correlated with Ca–microbial and cross‐trophic associations, microbial necromass carbon and nitrogen, and the contents of MAOM, SOC, and TN. These relationships were absent in cropland. Notably, cross‐trophic associations rather than microbial abundance or diversity, with significant modulation by soil exchangeable Ca 2+ , had the strongest positive relationship with MAOM, SOC, and TN accumulation in planted forests. Collectively, our findings lead to the hypothesis that warming promotes SOC and TN storage in planted forests by jointly strengthening exchangeable Ca 2+ , Ca–microbial and cross‐trophic interactions. These results highlight the potential importance of multi‐trophic interactions and Ca‐mediated processes in stabilizing microbial necromass and fostering carbon and nitrogen preservation during vegetation restoration in response to warming.

Repetitive transcranial magnetic stimulation modulates neuroinflammation and cell apoptosis via the interaction between Ifit3 and Stat1 for the treatment of neuropathic pain - Maomao Huang; Fei Xing; Zhangyu Xu; Haiyan Tang; Luting Zhao; Yue Yang; Qi Deng; Ronglan Shi; Lei Li; Jiayi Zhu; Xiaomin Chen; Dan Li; et al. (Inflammation Research, 2026)

Nitrogen removal performance and microbial communities during wastewater treatment through anammox: Effect of HRT and COD content - Yunhui Pu; Yao Xiong; Yan Liu; Yang Luo; Ruoran Liu; Jingyun Chen; Dan Xu; Jialing Tang; Shah Faisal; Abdelfatah Abomohra; Qingyuan Wang (Journal of Water Process Engineering, 2026)

The role of the nasal microbiome in linking ozone pollution to allergic rhinitis in children - Hao Tang; Shuang Du; Yongqiang Tan; Wen Su; Zhiping Niu; Jin Sun; WenPu Shao; Xinyi Fang; Zhiwei Tang; Dongjun Zhang; Zhuoru Chen; Zhenhua Zhang; et al. (Journal of Hazardous Materials, 2026)

The main Paleo-Tethys Ocean suture in the Pamir Region: Revealed by detrital zircon U–Pb geochronology - Murodov Azamdzhon; Wei Dan; Xin Ma; Murodov Davlatkhudzha; Sharifjon Odinaev; Ilhomjon Oimuhammadzoda; Mustafo Gadoev; Upendra Baral; Dzhovid Yogibekov; Gong-Jian Tang (Journal of Asian Earth Sciences, 2026)

Co-infection of Cryptocaryon irritans and Vibrio harveyi impairs osmoregulatory and respiratory functions in orange-spotted grouper Epinephelus coioides - Xueli Lai; Haoran Tang; Huicheng Wu; Yanwei Li; Xueming Dan; Zequan Mo (Fish & Shellfish Immunology, 2026)

Self-enhancing climatic resilience of surface soil through bio-carbonation constructed barrier - Rui Wang; Chao-Sheng Tang; Guang-Hui Lei; Xiao-Hua Pan; Zhi-Hao Dong; Shao-Dan Wang; Xiancai Lu (Engineering Geology, 2026)

Territorial spatial carbon balance governance from a spatially refined perspective: Incorporating sub-regional differences in spatial driving effects into zoning regulation - Yifei Xu; Mingxiang Wang; Wei Tang; Sinan Li; Wenqi Ai; Wenjing Xu; Dan Xu; Chang Liu; Jiarui Sun; Weixin Cui (Environmental Impact Assessment Review, 2026)

Effects of Abscisic Acid and Strigolactone on the Yield and Economic Benefit of Tartary Buckwheat - Lihua Dai; Fang Cai; Dan Lu; Jingang Tang; Kaifeng Huang; Xiaoyang Huang (Journal of Soil Science and Plant Nutrition, 2026)

Regulatory mechanisms of spatiotemporal variations in aboveground and belowground net primary production in global terrestrial ecosystems - Tao Zhou; Yanting Xiong; Zhihan Yang; Yuting Hou; Yuqing Zhang; Dan Liao; Xiaodong Wang; Dinghui Xu; Pingfeng Li; Peng Hou; Wenji Zhao; Guo Chen; et al. (Agricultural and Forest Meteorology, 2026)

Mechanism of baicalein from Wudang Mountain Scutellaria baicalensis Georgi. against atopic dermatitis based on network pharmacology, transcriptomics and in vitro experimental validation - Liu Tang; Gang Liu; Dan Li; Tianshuai Wang; Chun Wang; Guangwen Luo; Rui Peng; Xu Cai (Natural Product Research, 2026)

From agricultural waste to water treatment functional materials: Performance study of nano zero-valent iron loaded on ramie biochar for persulfate-activated carbamazepine degradation - Weiwei Yu; Lu Lv; Yang Liu; Cong Liu; Chuandong Tang; Yuanxin Liu; Xinyan Li; Dan Liu; Yan Luo; Ji Li (Journal of Environmental Chemical Engineering, 2026)

Prenatal exposure to bisphenols, metals, and risk of fetal chromosome numerical abnormalities in high-risk pregnancies: Independent, combined, and interactive effects - Jinglin Li; Mengli Yang; Jingting Chen; Dan Wang; Hongyue Sun; Zinuo Wang; Xiaoyu Li; Ying Chang; Baoqin Huang; Xi Chen; Nai-jun Tang (Journal of Environmental Sciences, 2026)

Comparison of the structural characteristics, pH-sensitivity, antioxidant activity and thermal stability of different dialdehyde polysaccharides grafted with purple sweet potato anthocyanins - Dawei Yun; Chao Tang; Dan Chen; Huimin Yong; Jun Liu (Food Chemistry, 2026)

Low-δ18O magmas at Batur, Indonesia: Evidence for slab-window melting beneath arc volcanoes - Guo-Rong Tang; Wei Dan; Adi Maulana; Jian Wang; Xiu-Zheng Zhang; Xin Ma; Qiang Wang; Xi-Jun Liu; Gong-Jian Tang (Chemical Geology, 2026)

TRIM21 contributes to senile osteoporosis by shifting the osteoadipogenic balance toward adipogenesis in BMSCs - Changwei Li; Leilei Chang; Li Zhou; Zhou Dan; Minglong Qiu; Zhe Chen; Yong Chen; Guoqing Tang; Lianfu Deng (Science China Life Sciences, 2026)
During aging, bone marrow stromal cells (BMSCs) tend to differentiate more into adipocytes than into osteoblasts, resulting in decreased bone formation and contributing to age-related osteoporosis and impaired bone regeneration. However, the molecular mechanisms underlying this process remain unclear. In this study, we observed an increase in the expression of TRIM21 in aged BMSCs, particularly those involved in adipogenesis. This increase in TRIM21 levels shifted the osteoadipogenic balance toward adipogenesis in BMSCs, resulting in reduced bone formation and ultimately leading to age-related osteoporosis and impaired bone regeneration. Mechanistically, activation of the IL-1β-JNK MAPK pathway triggered the expression of TRIM21 in aged BMSCs, which then shifted the osteoadipogenic balance toward adipogenesis by facilitating the degradation of β-catenin through K48 ubiquitination. Therefore, our findings suggest a potential intrinsic mechanism for age-related bone loss and suggest that targeting TRIM21 could be beneficial for treating age-related osteoporosis and impaired bone regeneration.

First report of marine leech Limnotrachelobdella okae infestation in miiuy croaker (Miichthys miiuy): An emerging threat to Chinese mariculture - Shunli Che; Zequan Mo; Hai Zhang; Haoran Tang; Xueming Dan; Yanwei Li (Veterinary Parasitology, 2026)

Insights into pesticides-induced toxicity in the silkworm (Bombyx mori) from physiological responses to molecular mechanisms - Dan-Dan Bian; Shuang-Gui Dai; Bo-Ping Tang; Qiu-Ning Liu (Pesticide Biochemistry and Physiology, 2026)

Sesquiterpenoids from Euphorbia esula L. - Defeng Yan; Miaomiao Zhang; Dan Tang; Yuqing Song; Liu Liu; Haiqing Zhao; Nurmirza Begmatov; Orzimat Turdimatovich Turginov; Bo Zhao; Hequn Yang; Guoan Zou (Phytochemistry, 2026)

Association between prenatal PFAS exposure and catch-up growth in children born with adverse outcomes: evidence from a prospective cohort study - Su-Qin Tan; Yan-Xi Li; Shao-Ya Huang; Shen-Pan Li; Qiong Zhang; Cui-Lan Tang; Ying-Chao Ye; Guang-Hui Dong; Jian Chen; Dan Cai; Xiao-Wen Zeng (Journal of Hazardous Materials, 2026)

Water loss and return flows matter for water stress mitigation in China - Dan Wang; Reetik Kumar Sahu; Taher Kahil; Ting Tang; Wei Zhang; Weili Ye; Guangxue Wu; Zhuo Chen; Huimei Li; Junxia Wang; Haoyuan Feng; Yuli Shan; et al. (Journal of Cleaner Production, 2026)

Molten Li/Na/K ternary carbonate salt pyrolysis of biomass: A facile approach for co-production of porous biochar, CO-enriched syngas, and high-selectivity bio-oil - Jiazhen Tang; Tianyu Lu; Xing Xie; Dan Lin; Dongjing Liu; Qingfa Zhang; Mingfeng Wang; Weiwei Liu; Zhong Ma; Haiping Yang; Shihong Zhang; Bin Li (Journal of Cleaner Production, 2026)

Dual regulation strategy to enhance polysaccharide coating adhesion and tangerine fruits preservation: Mechanistic insights and effect evaluation - Chunfeng Tang; Ying Liu; Qibin Li; Wanting Yu; Dan Ren; Xiyu Wu; Dan Xu (Food Packaging and Shelf Life, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Association of PM2.5, O3 and greenness exposure with risk of cardiometabolic multimorbidity: a prospective cohort study - Ning Gao; Dan Sheng; Shaoyan Tang; Minzhen Wang; Shan Zheng (International Journal of Biometeorology, 2026)

Stressor Combinations Shift Soil Microbial Communities From Rare to Unknown Taxa and Alter Genomic Strategies - Shuxun Cheng; Xianjin Tang; Xing Huang; Yang Li; Shuyi Huang; Dan He; Eduardo Moreno‐Jiménez; Jianming Xu; Matthias C. Rillig; Zhongmin Dai; Manuel Delgado‐Baquerizo (Global Change Biology, 2026)
Soil microorganisms constitute the largest portion of Earth's biodiversity. However, soil microorganisms are also highly sensitive to on‐going global change, and the influence of an increasing number of stressors on common, rare, and unknown taxa across large environmental gradients remains virtually unknown. Here, we combined a large‐scale spatial field survey across multiple different ecosystems and found that the diversity and abundance of soil rare taxa were significantly reduced under high environmental stressor number (i.e., a high number of stressors passing a 75% stressor threshold). Strikingly, the abundance of unknown soil taxa and unknown genes increased with increasing environmental stress number. We further identified the metagenome‐assembled genomes (MAGs) that were considered as relatively common taxa using metagenomics. Compared to 9% of negative responders, 32% of common MAGs were resistant or positively responsive to multiple stress, displaying a reduced potential for cellular processes and an enhanced potential for environmental, genetic, and metabolic processes. Our study suggests that as stress increases, we would have less rare, but more unknown microorganisms and unique genomes of resistant common taxa, suggesting major changes in the soil microbiome in a world subjected to multiple global change stressors.

Toxicological Insights Into Multiple Pesticide Exposures in Red Swamp Crayfish ( Procambarus clarkii ): Molecular Mechanisms, Risk Assessments, and Future Perspectives for Aquaculture - Dan‐Dan Bian; Zi‐Yi Xing; Shuang‐Gui Dai; Xiang Lu; Dai‐Zhen Zhang; Bo‐Ping Tang; Bao‐Jian Zhu; Qiu‐Ning Liu (Reviews in Aquaculture, 2026)
The rice–crayfish integrated system (RCIS) is vital to Asian aquaculture, yet its sustainability is threatened by a critical paradox: pesticides used in rice cultivation jeopardize the health of the red swamp crayfish ( Procambarus clarkii ) and the safety of its products. This review systematically synthesizes evidence establishing oxidative stress as the central hub linking pesticide exposure to multilevel toxicity in P. clarkii . We delineate how pesticides dysregulate key pathways (PI3K/AKT/mTOR, MAPK, NF‐κB), triggering apoptosis, metabolic disruption, and immunosuppression. A pivotal mechanism involves pesticide‐induced gut microbiota dysbiosis, which diminishes beneficial short‐chain fatty acids and enriches pathogens, thereby amplifying intestinal barrier damage and host vulnerability. These interconnected processes collectively stunt growth and heighten susceptibility to pathogens like white spot syndrome virus (WSSV). Beyond organismal effects, we evaluate environmental pesticide fate and propose a novel risk assessment framework integrating these sublethal endpoints. Our proposed mitigation strategies include eco‐friendly pesticides, ecological engineering, and microbiome‐directed interventions. We advocate for future research prioritizing multi‐omics and mixture toxicity assessment. By deciphering this toxicity cascade and translating insights into practice, this review aims to protect the productivity, ecological integrity, and food safety of integrated aquaculture systems for long‐term sustainability.

Systematic Review and Meta-Analysis on Heavy Metals and Trace Elements in Mild Cognitive Impairment - Yaxin Dong; Lu Ren; TianRan Tang; Xinyi Zhang; Dan Han; Yingyi Luo; Liqiang Wang; Zonghui Cui; Sheng Ji; Jianheng Zheng; Ying Qing (Biological Trace Element Research, 2025)

Discovery of rearranged eudesmane-type sesquiterpenes from Artemisia tournefortiana - Guziliayi Kuerban; Ablajan Turak; Nannan Xu; Dan Tang; Deng Zang; Xiayidan Abulimiti; Jiangyu Zhao; Haji Akber Aisa (Phytochemistry, 2025)

Protracted crustal melting and formation of the giant Shakhdara gneiss dome, South Pamir - Murodov Azamdzhon; Wei Dan; Xin Ma; Amjad Hussain; Sharifjon Odinaev; Dzhovid Yogibekov; Ilhomjon Oimuhammadzoda; Davlatkhudzha Murodov; Sherzod Abdulov; Mustafo Gadoev; Gong-Jian Tang (Lithos, 2025)

Cambrian intermediate-felsic rocks in Central Pamir: Insights into source heterogeneity and subduction initiation in the Proto-Tethys Ocean - Sharifjon Odinaev; Jovid Aminov; Gennadiy Kallistov; Xin Ma; Guo-Rong Tang; Murodov Azamdzhon; Aleksandr S. Stepanov; Ilhomjon Oimuhammadzoda; Mustafo Gadoev; Sohibnazar Ashuraliev; Wei Dan; Gong-Jian Tang (Lithos, 2025)

A peptidomics-based investigation of the synergistic effects of neutral and Alcalase proteases on release of antioxidant peptides from soybean protein isolates - Shulong Cai; Liqi Fan; Dan Liu; Changxing Wei; Na Yang; Xichao Fu; Rong Tang; Jucai Xu; Sheng Yin; Xin Chen (Food Chemistry, 2025)

Performance enhancement strategies for lithium-based battery electrodes via covalent organic frameworks: A review of recent advances - Waheed Ahmad; Muhammad Tahir; Batoul Bibi; Liang He; Hui Tang; Longbing Qu; Fazal Ul Nisa; Mizna Naseem; Habib Ullah; Iram Abdul Ghafar; Saira Manzoor; Yihao Long; et al. (Chemical Engineering Journal, 2025)

Corrigendum to “Sirtuin 1/3 regulates p53 deacetylation to inhibit iron poisoning-induced alveolar epithelial cell death and contributes to Rapamycin-mediated protection against limb ischemia/reperfusion-induced lung injury” [Chem. Biol. Interact. 421 (2025) 111756] - Dan Huang; Yong-lin Liang; Lie-liang Zhang; Bin Zhou; Bin Tang (Chemico-Biological Interactions, 2025)

BS-D275: A novel locus on the chromosome arm 2DS governing branched spike development in wheat - Yunfeng Qu; Yongkang Ren; Jinghuang Hu; Yi Liu; Dan Qiu; Yahui Li; Qiuhong Wu; Miao He; Qing Guo; Yu Sun; Wenze Yan; Zhaohui Tang; et al. (Theoretical and Applied Genetics, 2025)

Magmatism in continental rifts and rifted margins - Wei Dan; Qiang Wang; Gong-Jian Tang; Xiu-Zheng Zhang (Science China Earth Sciences, 2025)

Body Composition-Derived Subtypes in Tibetan Adults Residing at Qinghai-High Plateau and Their Associations with Distinct Metabolite Profiles and Cardiometabolic Outcomes - Tiemei Li; Lin Shi; Qingxia Huang; Ruijie Xu; Bin Zhang; Dan Zhang; Qi Wang; Haijing Wang; Li Tong; Huiru Tang; Youfa Wang; Wen Peng (Phenomics, 2025)

DNA methylation in plant heterosis: mechanisms and prospects - Dan Wang; Xinrui Tang; Chaoguan Yu; Jianfeng Hua; Tingting Chen; Yinfeng Xie (Functional & Integrative Genomics, 2025)

Machine learning-based identification of potential debris flow catchments in the Wenchuan earthquake region - Dunlong Liu; Jing Zhou; Xuejia Sang; Dan Tang; Shaojie Zhang; Qiao Chen (Earth Science Informatics, 2025)

The size-variation of microplastics alters plant nitrogen uptake by regulating soil gross nitrogen transformation rates - Xiaoqian Dan; Mengqiu He; Yuhong Wen; Longwei Meng; Meirong Huang; Shending Chen; Qilin Zhu; Yanzheng Wu; Shuirong Tang; Ahmed S. Elrys; Zucong Cai; Jinbo Zhang; et al. (Soil Biology and Biochemistry, 2025)

Iridoids and other constituents from the aerial parts of Patrinia rupestris and their inhibitory effects on nitric oxide production - Zhi-Yuan Liu; Sheng-Run Guo; Jian-Xian Tang; Chun-Yan Zhao; Li Pu; Li-Zhong Wang; Dan Liu; Rong-Tao Li; Hong-Mei Li (Phytochemistry, 2025)

Determining the differences in O3-NOx-VOCs sensitivity between sauna and roast days - Yuting Liu; Yinghong Wang; Yusi Liu; Mengtian Cheng; Baoxian Liu; Tao Song; Bo Hu; Dan Yao; Miao Yu; Yu Shi; Guiqian Tang; Yuesi Wang (Journal of Environmental Sciences, 2025)

rGO/polypyrrole-modified bioelectrode reshapes microbial communities for enhanced energy-recovering denitrification in carbon-limited wastewater - Yue-Jia Yang; Hong-Li Lu; Naif Abdullah Al-Dhabi; Wang-Wang Tang; Shuai Wang; Dan Cui (Environmental Research, 2025)

Seawater desalination by multistage flow-electrode capacitive deionization with graded electric field and electrode salinity - Yekun Feng; Dan Zhao; Hongyang Wang; Kai He; Bingjun Liu; Kexin Tang (Desalination, 2025)

Theranostic covalent organic frameworks for biosensing and targeted drug delivery - Wilson Dumisani Gamuchirai Dube; Theophilus Ngong Gha ajem; Prince Nicholas Yarh; Wishes Tatenda Machoko; Yaoyao Wang; Dan Wang; Tatenda Chimbunde; Xue Tang; Zhao Linjie; Deli Xiao; Pierre Dramou (Chemical Engineering Journal, 2025)

Sirtuin 1/3 regulates p53 deacetylation to inhibit iron poisoning-induced alveolar epithelial cell death and contributes to Rapamycin-mediated protection against limb ischemia/reperfusion-induced lung injury - Dan Huang; Yong-lin Liang; Lie-liang Zhang; Bin Zhou; Bin Tang (Chemico-Biological Interactions, 2025)

Interdecadal feature and mechanism of global dusty weather - Weiqi Tang; Yuzhi Liu; Tongyu Wang; Dan Li; Jie Gao; Ziyuan Tan; Xuefeng Dong (Atmospheric Environment, 2025)

Cumulative exposure to the chemical components of PM2.5 and the prevalence of Anemia: Insights from a large group of workers in South China - Xinyue Li; Zhiqiang Li; Yongqing Sun; Man Zhang; Meimei Zhong; Yueqian Wu; Xudan Chen; Xurui Sun; Dan Chen; Huanle Cai; Guanghui Dong; Hui Tang; et al. (Atmospheric Environment, 2025)

Establishment of Agrobacterium-mediated genetic transformation in Salix brachista - Dan Tang; Yumeng Li; García-Caparrós Pedro; Jiahui Chen; Xudong Sun (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Optimization of organogenesis and antibiotic screening in genetic transformation of Taxodium hybrid ‘zhongshanshan’ - Dan Wang; Xinrui Tang; Chaoguang Yu; Jianfeng Hua; Yinfeng Xie; Tingting Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Correction: Flavisericum labens gen. nov., sp. nov., a novel member of the family Flavobacteriaceae isolated from the seawater of Dongshan Bay - Jieyi Li; Ziling Xu; Zhiyi Su; Guohua Liu; Yue Xu; Dan Lin; Kai Tang (Antonie van Leeuwenhoek, 2025)

Evaluating green total factor productivity in Chinese port listed companies based on biased technological change perspective - Yuting Zheng; Xiongjun Yuan; Dan Liu; Jingying Tang; Huishan Fu (Environment, Development and Sustainability, 2025)

Preclinical pharmacokinetic and toxicokinetic profiles of AY-1001 (IsoLiPro), a novel small molecule lithium-organic coordination compound - Yi Guo; Bingjie Zhang; Chuanbin Cai; Qinmin Tang; Zhifeng Lei; Jiang Chen; Xiaojiang Zheng; Shaowei Lei; Weidi Zhang; Dan Zi; Jun Tan; Song Li (Toxicology and Applied Pharmacology, 2025)

Vacancy-rich Nd2S3/TiO2 S-scheme heterojunction for boosted photocatalytic tetracycline hydrochloride degradation: Interfacial engineering and mechanism insight - Qiang Wang; Ying Tang; Tiantian Li; Dan Cui; Weixia Yang; Li Zhang; Kezhen Qi; Feng Yu (Journal of Environmental Chemical Engineering, 2025)

Response of formaldehyde to meteorology in Beijing: Primary or secondary contributions - Yanyu Kang; Yinghong Wang; Mengtian Cheng; Baoxian Liu; Dan Yao; Yiming Wang; Guiqian Tang (Journal of Environmental Sciences, 2025)

Dietary biotin facilitates collagen deposition and myofiber growth and development, improving muscle chewiness and hardness in grass carp (Ctenopharyngodon idella) - Yang Yang; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Sheng-Yao Kuang; Shu-Wei Li; Ling Tang; Cheng-Bo Zhong; Lin Feng; Xiao-Qiu Zhou (Food Bioscience, 2025)

Isolation and characterization of minor monoterpene glycosides from the roots of Paeonia lactiflora - Yongliang Ding; Dan Han; Qian Tang; Lijuan Wang; Zhongtang Qu (Biochemical Systematics and Ecology, 2025)

Phytochemical characterization, antioxidant, enzyme inhibitory and anti-inflammatory activities of Hedychium coccineum Buch.-Ham. ex Sm. rhizome - Yuanquan Ran; Dan Xie; Dan Long; Lu Jin; Guo Chen; Bing Yang; Dongxin Tang; Minyi Tian (Biochemical Systematics and Ecology, 2025)

Plant Nitrogen Preferences Mirror Underground Nitrogen Cycling in Natural Ecosystems - Ahmed S. Elrys; Lei Meng; Yves Uwiragiye; Khaled A. El‐Tarabily; Qilin Zhu; Xiaoqian Dan; Tang Shuirong; Wu Yanzheng; Yanfu Bai; Tong‐bin Zhu; Jinbo Zhang; Christoph Müller (Global Change Biology, 2025)
Reliable prediction of plant nitrogen (N) acquisition strategies is critical for interpreting ecosystem productivity. We propose a process‐based framework that connects plant N preferences to soil microbial N cycling and environmental conditions. We compiled data from 66 15 N labeling studies, yielding 336 triplet observations, each consisting of plant organic‐N, ammonium‐N, and nitrate‐N uptake measurements (Dataset 1). Additionally, 2030 observations of gross soil N transformations from 270 studies were compiled to predict the spatial variation of these rates globally, with the aim of populating Dataset 1. We found that ammonium‐N was the primary contributor to N uptake in forests (49% ± 1.84%) and wetlands (55% ± 3.29%), whereas nitrate‐N was the dominant source in grasslands (41% ± 1.52%). Plant ammonium‐N and nitrate‐N preferences were lowest in temperate and tropical regions, respectively. Nitrification capacity—autotrophic nitrification (the process where ammonium is oxidized to nitrate) to gross N mineralization (GNM; the conversion of organic N to ammonium) ratio—was the main regulator of plant ammonium‐N and nitrate‐N preferences. Terrestrial environments with high nitrification capacity (e.g., temperate or grassland soils) resulting from high soil pH and low carbon‐to‐N ratio exhibited higher plant nitrate‐N preference, while adverse conditions (e.g., tropical, forest, or wetland soils) exhibited higher ammonium‐N preference. Interestingly, dissimilatory nitrate reduction to ammonium (DNRA) process redirected plant preference toward ammonium‐based nutrition in organic carbon‐rich, low‐oxygen soils. Climate‐driven shifts in plant N preference are mediated by gross soil N transformations, as increased precipitation and/or temperature accelerated GNM and/or DNRA while inhibiting nitrification capacity, promoting plant ammonium preference. Soil N cycling and environmental conditions explained little variation in plant organic‐N preference, suggesting that other variables (e.g., mycorrhizal associations and plant functional traits) may be at play. We highlight that plant N acquisition is not purely plant‐driven, but it mirrors underground N transformations, with environmental conditions acting as pivotal modulators of this relationship.

Design and synthesis of novel indolinone Aurora B kinase inhibitors based on fragment-based drug discovery (FBDD) - Baoxing Xie; Miaomiao Shi; Dan Tang; Shan Yang; Yan Zeng; Lifei Nie; Chao Niu (Molecular Diversity, 2025)

Retraction Note: Spironolactone inhibits apoptosis in rat mesangial cells under hyperglycaemic conditions via the Wnt signalling pathway - Dan Zhu; Hongwei Yu; Hongjiang He; Jiuli Ding; Jie Tang; Dan Cao; Lirong Hao (Molecular and Cellular Biochemistry, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Children’s home environments as reservoirs of antimicrobial resistance: Divergent urban-rural risks from antibiotic resistance genes and pathogens - Shuang Du; Hao Tang; Zhang Wang; Han Chen; Xinyi Fang; Jin Sun; Zhiping Niu; Yiwei Liu; Yuanzhuo Hu; Wen Su; Zhenhua Zhang; Tippawan Prapamontol; et al. (Journal of Hazardous Materials, 2025)

Molecular characteristics and formation pathways of organosulfates in atmospheric fine particles: A case study in steel industrial city during winter heating period - Cuiping Ning; Yutong Tang; Hao Sun; Dan Wang; Shuai Sun; Yuan Gao (Journal of Hazardous Materials, 2025)

Interplanting Phoebe bournei modifies soil microbial community characteristics in Cunninghamia lanceolata monocultures - Dan Zhou; Chengjian Hong; Jiahuan Guo; Chang Pan; Yazhou Tang; Jie Yan; Kaizhi Xie; Yuanchun Yu (European Journal of Soil Biology, 2025)

Metamorphic evolution of Mesozoic microcontinent suture zones in the Tibet region - Wei Dan; Xiu-Zheng Zhang; Yi-Xiang Chen; Gong-Jian Tang; Qiang Wang; Yong-Fei Zheng (Earth-Science Reviews, 2025)

Tailoring sodium storage with phosphorus-doped hollow carbon nanospheres: Atomic-level engineering of charge transport and ion dynamics - Xilong Wang; Deng Zhang; Qiaotian Zheng; Jie Song; Dawei Chen; Debing Yan; Bin He; Dan Xiao; Yan Meng; Jing Ying; Qian Zhao; Mao Tang (Chemical Engineering Journal, 2025)

Flavisericum labens gen. nov., sp. nov., a novel member of the family Flavobacteriaceae isolated from the seawater of Dongshan Bay - Jieyi Li; Ziling Xu; Zhiyi Su; Guohua Liu; Yue Xu; Dan Lin; Kai Tang (Antonie van Leeuwenhoek, 2025)

From Disruption to Restoration: Global Impacts of Soil Salinity and Its Mitigation Strategies on Ecosystem Nitrogen Cycling - Nathan O. Oduor; Ahmed S. Elrys; Manal A. Alnaimy; Tracy Opande; Di Feng; Yves Uwiragiye; Xiaoqian Dan; Shuirong Tang; Tong‐bin Zhu; Lei Meng; Jinbo Zhang; Christoph Müller (Global Change Biology, 2025)
Salinity impairs soil health by disrupting microbial activity and altering soil physicochemical properties, ultimately undermining ecosystem resilience and productivity. Yet, the effect of salinity and its mitigation strategies on soil nitrogen (N) cycling and plant ammonium and nitrate uptake and N use efficiency is not well established on a global scale. Through a meta‐analysis of 3422 paired observations from 309 publications, we found that salinity significantly alters soil N dynamics across multiple pathways. It inhibited the nitrification process by reducing microbial biomass, leading to a substantial accumulation of ammonium (+145%) and nitrite (+203%), while significantly suppressing biological N fixation (−82%). These shifts significantly increased plant uptake of ammonium but reduced that of nitrate and total N, ultimately contributing to a decline in crop yield by 9.5%. Accumulated ammonium in soil also increased ammonia volatilization by 158%. The effect of salinity on soil N availability was context‐specific, exhibiting greater effects under high salinity levels, especially in natural ecosystems, arid zones, and alkaline soils. Contrastingly, salinity mitigation treatments led to significant improvements across multiple N pathways. They enhanced soil N pools, including increased biological N fixation and available and total N concentrations. These changes supported greater plant N uptake, resulting in increased N use efficiency and crop yield. However, these benefits were accompanied by a significant increase in nitrous oxide emissions by 80%, indicating a trade‐off between environmental impacts and productivity gains. These effects of salinity mitigation treatments on N cycling were more pronounced under the application of organic and mineral fertilizers, as well as crop growth promoters. Collectively, our findings indicate that while salinity appears to impair N cycling by reducing microbial biomass and limiting plant N assimilation, these effects are reversible through mitigation measures. However, further investigation is required to develop salinity mitigation approaches that concurrently minimize nitrous oxide emissions.

Nitrite Toxicity in Shrimp Aquaculture: Mechanisms, Health Impacts, and Sustainable Mitigation Strategies - Dan‐Dan Bian; Yan‐Xia Shi; Xue Zhang; Xin Liu; Jun‐Jie Jiang; Xi‐Rong Zhu; Dai‐Zhen Zhang; Qiu‐Ning Liu; Bao‐Jian Zhu; Bo‐Ping Tang (Reviews in Aquaculture, 2025)
The rapid expansion of intensive aquaculture systems has caused escalating environmental challenges due to excessive nitrogenous waste accumulation, which surpasses the metabolic capacity of aquatic microbiota and elevates nitrite concentrations. As a pervasive environmental toxin, nitrite induces oxidative stress, disrupts metabolic homeostasis, and compromises gut microbiota and immune function in shrimp, leading to mass mortality, economic losses, and ecological disruption. These impacts threaten both aquaculture productivity and ecological sustainability. This review synthesizes three decades of research to elucidate the multifactorial mechanisms of nitrite toxicity, including genotoxicity, apoptosis, growth impairment, and dysregulated cellular signaling pathways. Key findings highlight that nitrite overload impairs mitochondrial function, dysregulates apoptosis pathways, and interferes with growth and reproductive processes, thereby undermining shrimp development and reproduction. To address these challenges, the review evaluates emerging mitigation strategies such as antioxidant‐enriched feeds, probiotic modulation, and biofloc technology, which optimize nitrogen cycling, enhance detoxification capacity, restore microbial equilibrium, and improve survival rates in experimental trials. Unlike prior fragmented studies, this review integrates mechanistic insights into nitrite toxicity with scalable interventions, proposing a novel decision framework for system‐specific nitrite management. This framework offers actionable recommendations for policymakers and industry stakeholders to balance aquaculture productivity with ecological sustainability. By advancing the understanding of nitrite's ecotoxicological impacts, this review charts a path toward resilient and sustainable aquaculture systems, transforming mechanistic insights into preventive protocols and offering a holistic perspective on nitrite pollution control that reconciles economic objectives with ecological sustainability.

Machine learning based prediction by PlantCdMiner and experimental validation of cadmium-responsive genes in plants - Chaoqun Xu; Ling Sun; Lu-Dan Zhang; Ze-Jun Guo; Ji-Cheng Wang; Li-Han Zhuang; Dong-Na Ma; Ling-Yu Song; Jing Li; Qian-Su Ding; Han-Chen Tang; Hai-Lei Zheng (Journal of Hazardous Materials, 2025)

TET2 promotes UVB-induced cell death by activating RIPK3-MLKL-necroptosis signaling - Daijing Long; Yangfan Xu; Xuemei Li; Yilan Zeng; Ziting Tang; Lulu Liu; Yuanhong Liu; Xiule Zong; Shengbo Yang; Dan Wang (Chemico-Biological Interactions, 2025)

P2Y1R-IGFBP2 signaling: new contributor to astrocyte-neuron communication - Dan Huang; Yong Tang (Purinergic Signalling, 2025)

Combining network pharmacology and RNA sequencing to reveal the mechanism of emodin for the treatment of human neuroblastoma - Hai-mei Jiang; Shang-yi Huang; Dan Huang; Yan Zhao; Yi Yuan; Hai-fu Huang; Ying Tang; Jin-fang Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

AHNAK2 Regulates NF-κB/MMP-9 Signaling to Promote Pancreatic Cancer Progression - Na-na Tang; Rong-bo Xu; Bo Jiang; Hai-ling Zhang; Xiao-song Wang; Dan-dan Chen; Ji-jun Zhu (Biochemical Genetics, 2025)

Elevated temperature promotes methane-dependent arsenate reduction in paddy soils - Yujie Zhou; Zhaofeng Yuan; Ouyuan Jiang; Dan Chen; Williamson Gustave; Jianming Xu; Xianjin Tang (Soil Biology and Biochemistry, 2025)

Baoslingzhines Q−X: Structurally previously undescribed trace phenolic meroterpenoids from Ganoderma lucidum and their biological activities toward renal fibrosis and cytotoxicity - Yun-Yun Liu; Dan Cai; Xin-Ping Tang; Yong-Xian Cheng (Phytochemistry, 2025)

Adsorption and in vitro controlled–release properties of a soybean cellulose nanocrystal/polyacrylamide–based hydrogel as a carrier for different polyphenols - Lu Tang; Dan Zhao; Bo Wang; Shiru Bai; Bei Fan; Liang Zhang; Fengzhong Wang (Food Chemistry, 2025)

Sodium butyrate attenuates liver fibrogenesis via promoting H4K8 crotonylation - Ruiqi Tang; Hua Zha; Rongrong Liu; Jiawen Lv; Dan Cao; Lanjuan Li (Molecular and Cellular Biochemistry, 2025)

MiR-3202–DTL signaling axis impedes NSCLC malignancy via regulating the ubiquitination-proteasome degradation of p21 - Hongjuan Guo; Qianbin Tang; Yujie Zhao; Jianghao Cheng; JunJie Wang; Dan Liu; Ruyu Yan; Dongjin Lv; Bingxiao Lu; Mingsong Wu; Hongtao Yu; Hao Leng; et al. (Molecular and Cellular Biochemistry, 2025)

A Risk Prognostic Signature Basing on Cuproptosis-related Ferroptosis and Immune Genes for Esophageal Squamous Cell Carcinoma Patients - Jie Ma; Dan Liu; Yang Li; Lei Tang; Xukun Gao; Feng Zhu (Cell Biochemistry and Biophysics, 2025)

A nutritional strategy for improving sub-adult grass carp (Ctenopharyngodon idella) flesh flavor: The role of α-lipoic acid in regulating muscle nucleotide and fatty acid metabolism - Yang Zhang; Pei Wu; Wei-Dan Jiang; Yang Liu; Yao-Bin Ma; Sheng-Yao Kuang; Shu-Wei Li; Ling Tang; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2025)

Corrigendum to “Novel nutritional strategy: Dietary valine improves the health value and nutrient deposition in grass carp (Ctenopharyngodon idella)” [Aquaculture Volume 598, 15 March 2025, 742053] - Meng-Ling Cai; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Shu-Wei Li; Ling Tang; Cheng-Bo Zhong; Lin Feng (Aquaculture, 2025)

Cadmium inhibits carbon and nitrogen cycling through soil microbial biomass and reduces soil nitrogen availability - Ahmed S. Elrys; YuHong Wen; Di Feng; Rasha M. El-Mekkawy; Mengru Kong; Xiaofeng Qin; Qiqian Lu; Xiaoqian Dan; Qilin Zhu; Shuirong Tang; Yanzheng Wu; Lei Meng; et al. (Journal of Hazardous Materials, 2025)

Nectar characteristics and pollination ecology of Camellia perpetua in South China - Hai-du Jiang; Dan-juan Zeng; Hui-zhen Qin; Li-hui Peng; Yi-shan Yang; Zong-you Chen; Rong Zou; Jian-min Tang; Yun-sheng Jiang; Zhong-chen Xiong; Xiao Wei; Sheng-feng Chai (Flora, 2025)

A Cyanosiloxane additive enhances the high-voltage performance of layered oxide cathodes in sodium-ion batteries - Minli Wu; Junjie Tu; Yonghuang Ye; Yaxin Qin; Xiaobing Huang; Yougen Tang; Haiyan Wang; Dan Sun (Chemical Engineering Journal, 2025)

Molecular level characteristics and sources of rainwater water-soluble organic matter in different regions of China by FT-ICR MS - Cuiping Ning; Yutong Tang; Shuai Sun; Dan Wang; Yuan Gao (Atmospheric Environment, 2025)

Impacts of water conservation, wastewater treatment, and reuse on water quantity and quality stress mitigation in China - Dan Wang; Zhuo Chen; Reetik Kumar Sahu; Taher Kahil; Ting Tang; Yuli Shan; Wei Zhang; Weili Ye; Guangxue Wu; Huimei Li; Klaus Hubacek (Journal of Industrial Ecology, 2025)
Wastewater treatment plays a crucial role in removing pollutants. Water conservation and reuse of wastewater help to reduce freshwater use and to alleviate water stress. However, the extent to which water conservation, wastewater treatment, and reuse can contribute to water stress mitigation is not clear. This study aims to investigate the impact of water conservation, wastewater treatment, and reuse on both water quantity and quality stress mitigation in China. The investigation is based on a dataset mapping water quantity and pollutant flows across 32 sectors in 31 provinces in 2017 and a dataset of 7411 wastewater treatment plants containing information on wastewater quantity and quality. The findings show that wastewater reuse can reduce provincial water quantity stress by less than 10% and alleviate water stress in 4 out of 25 water‐stressed provinces. In contrast, water conservation can contribute to water quantity stress reduction by 31% on average. When water conservation measures and reuse are jointly implemented, quantity stress levels can significantly be alleviated in 19 out of 25 water‐stressed provinces, with quantity stress reductions ranging from 25% to 74%. The contribution of wastewater treatment to water quality stress mitigation varies between 6% and 86%, with an average of 29%. Nevertheless, wastewater treatment cannot sufficiently safeguard most regions against water quality stress. This is evident as 25 out of 29 water quality‐stressed provinces continue to suffer from quality stress despite implementing wastewater treatment and water conservation practices. Additional measures such as non‐point‐source pollution control should be implemented alongside wastewater treatment to eliminate provincial quality stress.

Exposure of Australian dams to seismic hazard from proximal faults - Mark Quigley; Tim Werner; Yuxiang Tang; Dan Clark; Jonathan Griffin; Haibin Yang (Environment Systems and Decisions, 2025)
The purpose of this study is to obtain estimates of ground surface rupture and ground motion hazards at standardised scales useful for general reference and regional comparisons of dams (n = 548) registered with the Australian National Committee on Large Dams (ANCOLD). Geospatial and statistical methods are used to investigate the exposure of dams to seismic hazard from 409 faults in the Geoscience Australia Neotectonic Features Database (NFD). We identify 216 faults at distances less than 100 km from 428 dams and measure 4055 fault-to-dam distances. At least 31 dams are located within 1 km of NFD fault traces and at least 16 of these dams could reside within NFD primary fault zones. Estimates of NFD maximum moment magnitudes (M w,max ) from fault area and length regressions range from 5.6 ≤ M w ≤ 7.9. Average (AD) and maximum (MD) NFD fault displacements for M w,max events range from 0.3 m ≤ AD ≤ 4.4 m and 0.9 m ≤ MD ≤ 8.4 m. Distance-probability regressions for distributed ground surface rupture suggest approximately 40 dams have a ≥ 10% probability of ground surface rupture occurring in the area encompassing the dam in a M w,max event. Peak ground accelerations (PGA) and pseudo-spectral acceleration at 1.0 s (PSA[1.0 s]) are estimated for M w,max at dam sites using the same set of ground motion models (GMMs) for the 2023 National Seismic Hazard Assessment (NSHA23), assuming engineering rock site conditions with a time-averaged shear wave velocity between the surface and 30 m sediment depth (VS30) of 760 m/s. Of the 4055 M w,max scenarios considered in total, 3579 M w,max scenarios produce 85th percentile PGA ≥ 0.1 g at dam sites and 2844 scenarios produce 85th percentile PSA[1.0 s] ≥ 0.1 g. Comparison with 1:5,000 annual exceedance probability (AEP) PGA and PSA[1.0 s] estimates from the NSHA23 indicate there are 404 out of 428 dams where NFD M w,max PGA are greater than NSHA23 values, and 422 instances where PSA[1.0] > NSHA23. Proximity to NFD faults imparts a first-order control on relative hazard. A large increase in the number of identified NFD faults over the last decade suggests further research will continue to increase NFD fault populations. NFD fault slip rates and M w,max are important parameters in seismic hazard analysis for many dams but exhibit large epistemic and aleatoric uncertainties. Improving the characterisation of NFD faults through acquisition of direct fault-specific seismic hazard information (e.g., single-event displacements, slip rates, inter-event times, frequency-M w distributions, segmentation scenarios) will assist with hazard profiling for many ANCOLD dams.

Invasion of Spartina species enhance blue carbon functions by increasing CO2 uptake and reducing methane emissions in Chinese and Danish coastal wetlands - Ming Ge; Linjing Ren; Dan Yang; Xiuzhen Li; Ying Huang; Jianwu Tang; Hans Brix (Journal of Cleaner Production, 2025)

Microcapsules stabilized by cellulose nanofibrils/whey protein complexes and modified with cinnamaldehyde: Characterization and release properties - Dan Wang; Lin Liu; Tanghui Liu; Jie Zhao; Hai Chi; Hongrui Chen; Jie Tang; Xingzhong Zhang (Food Chemistry, 2025)

Elevated mercury wet deposition in the biodiversity hotspot of southwestern China - Xiaohui Li; Dan Hu; Mengjie Lei; Ya Tang; Xue Qiao; Lei He (Environmental Research, 2025)

Early life imidacloprid and copper exposure affects the gut microbiome, metabolism, and learning ability of honey bees (Apis mellifera) - Xijie Li; Qihe Tang; Mengshang Hou; Yantao Pang; Dan Li; Yajuan Chen; Richan Fang; Yi Deng; Jun Zhang; Chonghui Zhao; Junjie Li; Yuan Chen; et al. (Environmental Research, 2025)

Synergistic doping and coating of lithium ion-sieves for enhanced lithium recovery from brine - Guotai Zhang; Qilin Wei; Xinyuan Xia; Dan Huang; Weiping Tang; William W. Yu (Desalination, 2025)

The Role of Regional Ocean–Atmosphere Coupling in Simulating the 2020 Extreme Mei-yu Event - Kai Li; Liwei Zou; Li Dan; Hui Zheng; Zhongfeng Xu; Jianping Tang; Fuqiang Yang; Wenli Fei; Taotao Zhang; Chunxiang Shi; Zong-Liang Yang (Advances in Atmospheric Sciences, 2025)

A comprehensive omics resource and genetic tools for functional genomics research and genetic improvement of sorghum - Chengxuan Chen; Fengyong Ge; Huilong Du; Yuanchang Sun; Yi Sui; Sanyuan Tang; Zhengwei Shen; Xuefeng Li; Huili Zhang; Cuo Mei; Peng Xie; Chao Li; et al. (Molecular Plant, 2025)

Investigation the antioxidant mechanisms of Capsaicinoids on myofibrillar protein based on multispectral and molecular docking - Jianhua Zhao; Chunyan Jiang; Meijuan Lei; Yilin Xie; Jie Zhao; Jiaxin Chen; Mingyuan Yang; Dan Xiang; Jie Tang; Hongbin Lin (Food Chemistry, 2025)

Dietary pyridoxine promoted muscle protein deposition relating to PI3K/AKT/TOR pathway and the ubiquitin proteasome system in grass carp (Ctenopharyngodon idella) - Li-Fu Gong; Xiao-Qiu Zhou; Lin Feng; Pei Wu; Wei-Dan Jiang; Yao-Bin Ma; Xiao-Wan Jin; Hong-Mei Ren; Jia-Yong Tang; Fa-Li Wu; Yang Liu (Food Bioscience, 2025)

Balancing method for landslide monitoring samples and construction of an early warning system - Dunlong Liu; Zhaoyang Xie; Dan Tang; Xuejia Sang; Shaojie Zhang; Qiao Chen (Natural Hazards, 2025)

Swertiamarin relieves radiation-induced intestinal injury by limiting DNA damage - Zhe Zhao; Dan He; Jinyu Wang; Yu Xiao; Lixin Gong; Can Tang; Haibo Peng; Xuemei Qiu; Rui Liu; Tao Zhang; Jingyi Li (Molecular and Cellular Biochemistry, 2025)

Loading of redox-active metal Fe largely enhances the capacity of biochar to mitigate soil N2O emissions by promoting complete denitrification - Dan Yuan; Ping Wu; Jiao Yuan; Zhifen Jia; Chunsheng Hu; Tim J. Clough; Nicole Wrage-Mönnig; Jiafa Luo; Jiahuan Tang; Shuping Qin (Biology and Fertility of Soils, 2025)

Novel nutritional strategy: Dietary valine improves the health value and nutrient deposition in grass carp (Ctenopharyngodon idella) - Meng-Ling Cai; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Shu-Wei Li; Ling Tang; Cheng-Bo Zhong; Lin Feng (Aquaculture, 2025)

Recombinant Bacillus subtilis displaying OmpA and cholera toxin B subunit fusion proteins on the spore surface: An orally delivered engineered probiotic against Edwardsiella tarda infection - Minggang Liu; Xixi Dai; Jianzhen Li; Dan Xiao; Bin Chen; Zhenhua Wang; Yicen Tang; Yan Zeng; Dongmei Zhang; Xueqin Ni; Kangcheng Pan (Aquaculture, 2025)

The key role of tyrosinase in color variation of the autotetraploid Carassius auratus - Xi-Dan Xu; Wan-Jing Peng; Yue Zhou; Chong-Qing Wang; Kun Zhang; Xu Huang; Xiao-Wei Xu; Jin-Hai Bai; Ling Xiong; Zheng-Kun Liu; Xin-Yi Deng; Yan Tang; et al. (Aquaculture, 2025)

Electrosorption-coupled flow-electrode capacitive deionization process for simultaneous fractionation, desalination, and resources removal/recovery from dye/salt mixture - Yekun Feng; Dan Zhao; Chongquan Cai; Kai He; Hongyang Wang; Kun Zhou; Kexin Tang (Journal of Water Process Engineering, 2025)

Modulating the spatial locations of bimetallic sites in KL zeolite via atomic layer deposition for improved n-heptane aromatization - Dan Xu; Li Wei; Yang Jiao; Zhuoya Bao; Angang Song; Guofu Liu; Jianmei Wang; Arthur Ernest Dr.Koschany; Peng Zhang; Laizhi Sun; Mingxing Tang; Tao Li; et al. (Fuel, 2025)

Inflammatory modulation effects of human milk oligosaccharides: From screening in-vitro to application in the milk powders - Jiayue Tang; Dan Yao; Jiahe Zhao; Maolin Tu (Food Bioscience, 2025)

Defective boron nitride aerogels by salt template synthesis: A green adsorbent for tetracycline removal - Dan Li; Zhaowei Liu; Qingnan Meng; Guoxin Xing; Kang Zhao; Yufei Tang (Environmental Research, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Near-infrared-absorbing and -emitting indium phosphide quantum dots via nucleation/growth modulation for killing multidrug-resistant bacteria - Ye Yuan; Yizhang Tang; Zhiwen Yang; Xujiang Yu; Liangrui He; Dan Li; Wanwan Li (Chemical Engineering Journal, 2025)

Energy Evolution and Nonlinear Breakage Constitutive Model of Granite Influenced by Non-uniformity of Crystal Combinations Under Cyclic Loading - Hu-dan Tang; Ming-li Zhu (Rock Mechanics and Rock Engineering, 2025)

Root carboxylate release is common in phosphorus-limited forest ecosystems in China: using leaf manganese concentration as a proxy - Li Yan; Dan Tang; Jiayin Pang; Hans Lambers (Plant and Soil, 2025)
Background and aims Certain plant species release root carboxylates in response to phosphorus (P) limitation; however, the prevalence of root exudate release in species in P-limited forest ecosystems remains unexplored due to challenges in field assessment. Methods Manganese (Mn) accumulation in mature leaves can indicate the presence of root carboxylate exudates in rhizosphere soil. To account for environmental factors such as soil pH, a negative reference species that does not release carboxylates is used for comparison. In this study, we assessed multiple forest stands across soil types and different levels of P availability in northern (Gansu) and southern (Guangxi) China. Leaf and soil samples were collected from 188 plant families representing various life forms, and leaf Mn concentration ([Mn]) was analyzed as a proxy for root carboxylate exudation patterns, using Dryopteridaceae as a negative reference. Results The results supported our hypotheses that leaf [Mn] was higher in P-limited forests of southern China compared to P-richer forests of northern China, even though the soil [Mn] was higher in the forests of northern China. Additionally, we observed a higher prevalence of species with high leaf [Mn] across various plant families in Guangxi (82%) than in Gansu (42%). Conclusion Our findings suggest a potential common strategy among plants in Guangxi forests, where root exudates are released in response to P limitation, possibly due to ineffective mycorrhizal symbiosis for nutrient acquisition. The diverse forest systems in China exhibit varying soil P availability, leading to the evolution of plant species with distinct P-acquisition strategies.

Spatiotemporal evolution of PM2.5 and its components and drivers in China, 2000–2023: effects of air pollution prevention and control actions in China - Yindi Peng; Yamin Zhao; Ning Gao; Dan Sheng; Shaoyan Tang; Shan Zheng; Minzhen Wang (Environmental Geochemistry and Health, 2025)

Geochemical characteristics and environmental implications of heavy metals and fluoride of the hot spring waters in China’s Tengchong Geothermal Field - Bo Xia; Lan Jiang; Yufei Yuan; Hua Tang; Xiaocheng Zhou; Jiao Tian; Miao He; Yongxian Zhang; Xiaoyi Zhu; Jiang Li; Dan Zhou; Yi Huang (Environmental Science and Pollution Research, 2025)

Imino and Benzimidazolinyl Functionalized pyrano[2,3-b] Quinoline as a Dual-Responsive Probe for Detection of Mercury ion and Phosgene - Feijun Dan; Qian Tang; Xin Chen; Liang Liu (Journal of Fluorescence, 2025)

Potentially harmful effects of micro-/nanoplastics on humans as well as protective actions of dietary natural products - Jin Cheng; Jiahui Li; Ruo-Gu Xiong; Dan-Dan Zhou; Si-Yu Huang; Si-Xia Wu; Ao Shang; Guo-Yi Tang; Hua-Bin Li; Ren-You Gan (Trends in Food Science & Technology, 2025)

Validation of the spray drift modeling software AGDISPpro applied to remotely piloted aerial application systems - Sebastian Castro-Tanzi; Michael Winchell; Zhenxu Tang; Milton E. Teske; Glen R. Whitehouse; Brad Fritz; Dan Martin (Science of The Total Environment, 2025)

Surfactant solubilization enhanced electrochemical degradation of a long-chain perfluoroalkyl substance: Applicability analysis - Yujia Tang; Zhenchu Dan; Hui Sun; Xinyue Hu (Journal of Water Process Engineering, 2025)

Design and preparation of non-porous amorphous PEI-based polymers and their adsorption properties for anionic dyes - Henglong Tang; Mingyue Qian; Zhu Long; Dan Zhang; Chang Sun (Journal of Hazardous Materials, 2025)

Removal performance and mechanism of aniline from landfill leachate by ozone oxidation process using iron-based packed catalyst - Zhiquan Xiang; Yijie Zhang; Lei Bo; Zhuowei Shen; Dan Wang; Zhiqiang Shen; Yaoyu Tang (Journal of Environmental Management, 2025)

Design, synthesis and antifungal activity of novel pyrazole-amide-isothiazole derivatives as succinate dehydrogenase inhibitors - Ai-ling Bao; Xian-song Xie; De-yuan Wang; Zi-quan Deng; Yun Chen; Dan Liu; Wei-yi Li; Xiao-rong Tang; Wei Cheng; Ying-kun Yan (Food Chemistry, 2025)

Mechanism of removal of Sb from printing and dyeing wastewater by a novel titanium-manganese binary oxide - Zhiquan Xiang; Yijie Zhang; Zhuowei Shen; Dan Wang; Zhiqiang Shen; Yaoyu Tang; Lei Bo; Man Wang (Environmental Research, 2025)

Multifunctional composites made from waste polyester cotton fabric and waste rigid polyurethane foam for potential building wall material applications - Feng Liang; Qinxian Chen; Zhen Shi; Rui Dan; Huan Liang; Xu Feng; Chuanyun Tang; Xijing Yu; Xianqin Shang; Denglu Zhang; Yuanyuan Hu (Energy and Buildings, 2025)

Revealing the blocking effect of hemicellulose on the formation of closed pores in reed-derived hard carbon for sodium-ion batteries - Zhouhao Fu; Dan Jiang; Zheng Tang; Zhi Tang; Jia Zhou; Rui Liu; Huanhuan Li; Dan Sun; Yougen Tang; Haiyan Wang (Chemical Engineering Journal, 2025)

Salinity affects C/N ratio through differential responses of carbon and nitrogen metabolism in mangrove Avicennia marina leaves revealed by combined analysis of transcriptome and metabolome - Jing Li; Ling-Yu Song; Ze-Jun Guo; Chao-Qun Xu; Lu-Dan Zhang; Ji-Cheng Wang; Han-Chen Tang; Ming-Jin Dai; Xue-Yi Zhu; Hai-Lei Zheng (Plant and Soil, 2025)

SaTDT enhanced plant tolerance to NaCl stress by modulating the levels of malic acid and citric acid in cells - Xiangyu Wei; Li Xu; Suisui Dong; Nina He; Qianqian Xi; Dan Yao; Qianqian Wang; Yue Zuo; Chen Ling; Meiting Qi; Wen Bai; Kai Han; et al. (Plant Molecular Biology, 2025)

Rapid and visual detection of the strawberries pathogenic fungi Fusarium oxysporum and Colletotrichum siamense by one-pot LAMP-CRISPR/Cas12b - Ya-Ru Tian; Dong-Lan Tang; Tian-Qi Wang; Jia-Yue Chen; Yan-Fang Dong; Xin-Yu Ying; Dan Zhang; Wen-Jing Wang; Zhi-Dan Luo (Journal of Plant Diseases and Protection, 2025)

Higher temperatures decreased the abundance of arbuscular mycorrhizal fungi and the complexity of their networks by reducing tree diversity - Dan Xiao; Yixin Tang; Wei Zhang; Peilei Hu; Kelin Wang (Applied Soil Ecology, 2025)

Toxicology of aspartame to largemouth bass (Micropterus salmoides) on the basis of antioxidant capacity, liver histology and the intestinal microbiota - Qiuwen Su; Jiafa Yang; Zixin Yang; Qin Kong; Guohong Xiao; Dan Liu; Huijuan Tang (Animal Feed Science and Technology, 2025)

Effects of dietary fish oil replacement with rice bran oil on growth performance, serum biochemical index, antioxidant capacity, lipid metabolism and inflammatory response of large yellow croaker (Larimichthys crocea) juveniles - Kenneth Chibuikem Chukwuma; Zhen Wang; Jichang Zheng; Fatou Ndoye Fall; Zhou Zhang; Yuhang Tang; Dan Xu; Bwebwe Botaa Tabuariki; Kangsen Mai; Qinghui Ai (Aquaculture, 2025)

Allelic variation in the promoter of WRKY22 enhances humid adaptation of Arabidopsis thaliana - Ruyun Liang; Luna Tan; Xiang Guo; Shangling Lou; Xuming Dan; Yu Han; Cheng Zeng; Han Zhang; Kai Yang; Liyang Chen; Xin Liang; Meng Liu; et al. (Molecular Plant, 2025)

Associations between metal/metalloid exposure during pregnancy and placental growth characteristics: Findings from the Hangzhou birth cohort study II - Hao Zhao; Lanfei Jin; Kegui Huang; Kunhong Zhong; Yexinyi Zhou; Yang Xu; Qinheng Zhu; Jiena Zhou; Jun Tang; Qiong Luo; Jing Guo; Dan Zhang; et al. (International Journal of Hygiene and Environmental Health, 2025)

Corrigendum to “Soybean glycinin impaired immune function and caused inflammation associated with PKC-ζ/NF-κb and mTORC1 signaling in the intestine of juvenile grass carp (Ctenopharyngodon idella)” [Fish and Shellfish Immunol. 106 (2020) 393–403] - Ya-Lin Zhang; Xu-Dong Duan; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Sheng-Yao Kuang; Ling Tang; Xiao-Qiu Zhou (Fish & Shellfish Immunology, 2025)

Graphene quantum dots decorated organic conductive polymer for advanced ternary amorphous solar-blind UV photovoltaic photodetectors - Han Cai; Haolin Yang; Weisen Li; Jiarong Liang; Zhuogeng Lin; Xingui Tang; Yanghui Liu; Dan Zhang; Wei Zheng (Chemical Engineering Journal, 2025)

Impact of the tibetan plateau heat source on heatwaves in China - Ziyuan Tan; Yuzhi Liu; Weiqi Tang; Dan Li; Jie Gao; Min Luo (Climate Dynamics, 2025)

Cerasicoccus fimbriatus sp. nov., isolated from the mid-ridge of the Southwest Indian Ocean - Xuanyun Qiu; Beihan Chen; Dan Lin; Guohua Liu; Zhiyi Su; Mingzhe Zhang; Kai Tang (Antonie van Leeuwenhoek, 2025)

Effects of nitrite exposure on the oxidative stress, immune response and intestine microbiota of Procambarus clarkii - Dan-Dan Bian; Yan-Xia Shi; Xi-Rong Zhu; Xiao-Li Sun; Xuan Xu; Lu Ding; Dai-Zhen Zhang; Qiu-Ning Liu; Bo-Ping Tang; Bao-Jian Zhu (Aquaculture, 2024)

Unraveling drivers of per- and polyfluoroalkyl substances (PFASs) occurrence and removal in leachate: Insights from disposal methods, geo-climate, and biodegradation - Leilei Lu; Xiaofei Yan; Guodong Kang; Dan Qi; Na Tang; Rui Zhu; Changwei Lv; Yuanqing Bu; Houhu Zhang; Shenghu Zhang (Science of The Total Environment, 2024)

NIR spectroscopy for quality assessment and shelf-life prediction of kiwifruit - Hongbo Li; Linlin Zhu; Na Li; Zhenbin Liu; Liheng Wang; Bimal Chitrakar; Dan Xu; Zhenkun Cui; Yanhua Tang; Liangbin Hu; Haizhen Mo (Postharvest Biology and Technology, 2024)

Dissolved N pollution and its biogeochemical constraints along a river-sea continuum of a typical dense oyster mariculture coastal water, northwest South China Sea - Solomon Felix Dan; Zeng Xiaolian; Jianhui Tang (Journal of Hazardous Materials, 2024)

AmTPS6 promotes trehalose biosynthesis to enhance the Cd tolerance in mangrove Avicennia marina - Ling-Yu Song; Jing Li; Lu-Dan Zhang; Zhao-Yu Guo; Chao-Qun Xu; Li-Wei Jiang; Jin-Yu Liu; Ji-Cheng Wang; Qing-Hua Li; Han-Chen Tang; Hai-Lei Zheng (Journal of Hazardous Materials, 2024)

A novel combination of surfactant solubilization and electrooxidation for remediation of pyrene - Yujia Tang; Zhenchu Dan; Hui Sun; Xinyue Hu (Journal of Environmental Chemical Engineering, 2024)

Untargeted metabolomics study of mature human milk from women with and without gestational diabetes mellitus - Dan Yao; Cai Shen; Xinghe Zhang; Jiayue Tang; Jingwen Yu; Maolin Tu; Worawan Panpipat; Manat Chaijan; Hong Zhang; Xuebing Xu; Yanan Liu; Ling-Zhi Cheong (Food Chemistry, 2024)

Histidine is effective in promoting muscle growth and protein deposition: In vivo and in vitro experimental models of grass carp (Ctenopharyngodon idella) - Xin Zeng; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Ling Tang; Shu-Wei Li; Sheng-Yao Kuang; Lin Feng (Food Bioscience, 2024)

Effect of light conditions on phycoerythrin accumulation by thermophilic cyanobacterium Leptothermofonsia sichuanensis and characterization of pigment stability - Dan Yao; Ying Jiang; Maurycy Daroch; Jie Tang (Bioresource Technology, 2024)

Ground-based MAX-DOAS observations of tropospheric formaldehyde and nitrogen dioxide: Insights into ozone formation sensitivity - Yuanyuan Qian; Dan Wang; Zhiyan Li; Houtong Liu; Haijin Zhou; Ke Dou; Liang Xi; Fuying Tang; Fuqi Si; Yuhan Luo (Atmospheric Pollution Research, 2024)

Enhancing biomass and ecological sustainability in rice–fish cocropping systems through the induction of functional microbiota with compound biogenic bait - Yang Zhang; Ying-Han Liu; Dan-Yao Tang; Jun Zhang; Xi-Yue Zhang; Chen-Wei Xu; Yu-Juan Yuan; Chuan-Chao Dai (Soil Ecology Letters, 2024)

Rapid and Efficient Investigation of Ciliate Nuclear Development During Conjugation Through Optimizing Hoechst33342 Staining Workflow - Yaohan Jiang; Xue Zhang; Dan Liu; Xianglin Tang; Ruitao Gong (Journal of Ocean University of China, 2024)

Roseihalotalea indica gen. nov., sp. nov., a halophilic Bacteroidetes from mesopelagic Southwest Indian Ocean with higher carbohydrate metabolic potential - Beihan Chen; Mingzhe Zhang; Dan Lin; Jianing Ye; Kai Tang (Antonie van Leeuwenhoek, 2024)

Quantitative susceptibility mapping reveals brain iron accumulation in minimal hepatic encephalopathy: associations with neurocognitive changes - Li-Min Cai; Jing-Yi Zeng; Hui-Wei Huang; Ying Tang; Dan Li; Jian-Qi Li; Hua-Jun Chen (Metabolic Brain Disease, 2024)

Unveiling the hidden impact: How human disturbances threaten aquatic microorganisms in cities - Ganghui Jiao; Yi Huang; Hua Tang; Ying Chen; Dan Zhou; Daming Yu; Zhongjian Ma; Shijun Ni (Science of The Total Environment, 2024)

Upcycling C1 gas-derived resources in future food system - Jiawei Li; Jiunwei Tseng; Dan Tang; Yunqian Yong; Lichao Sun; Yi-Xin Huo (Resources, Conservation and Recycling, 2024)

Rapid redox-response featured visual ascorbic acid sensor based on simple-assembled europium metal-organic framework - Lin-Lin Zhang; Li Li; Dan Wang; Yanping Hong; Kaijie Tang; Jiaxin Hong; Zeng Chen; Wuying Yang; Limin Lu; Lu-Ying Duan (Food Chemistry, 2024)

ZnO nanoparticles induce melanoma-like lesions via recruiting dermal dendritic cells in barrier-damaged skin in mice - Menghan You; Yingying Huang; Yeda Chen; Dan Li; Yaping Tang; Yi kuan Du; Hong Yang; Anfa Liang; Guodong Hu; Yinghua Chen (Food and Chemical Toxicology, 2024)

Intrauterine exposure to long-chain perfluorocarboxylic acids (PFCAs) were associated with reduced primary bile acids in three-year-old children: Findings from a prospective birth cohort study - Yu-Ting Guo; Jin-bo Huang; Jing-chuan Xue; Shuang-Jian Qin; Dan Cai; Qi-Zhen Wu; Chu Chu; Cui-lan Tang; Yan-qi Xie; Li-Zi Lin; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Pollution, 2024)

Molecularly tailored bifunctional nano-overlayers for efficient and stable inverted perovskite solar cells - Lu-Lu Jiang; Shao-Jie Li; Qi Li; Shuai-Ke Guo; Zhen-Rong Song; Ying-Zhuo Shen; Xiao-Nan Zhang; Dong-Sheng Zheng; Xiao-Dan Tang; Hai-Rui Liu (Chemical Engineering Journal, 2024)

Sequence-Unconstrained DNA Computing: DSN cycling and PER circuitry for dynamic miRNAs analysis and multifunctional logic operations - Dan Bai; Yaoyi Zhang; Jiu Pu; Li Zhang; Hongyan Yu; Xiaole Han; Ke Lv; Li Wang; Junjie Li; Ao Tang; Wang Luo; You Wu; et al. (Chemical Engineering Journal, 2024)

PbHfO3-based antiferroelectric materials: Fundamentals, properties, and advanced applications - Dong-Liang Li; Xin-Gui Tang; Shui-Feng Li; Xiao-Bin Guo; Dan Zhang; Qi-Jun Sun; Wen-Hua Li; Zhen-Hua Tang; Yan-Ping Jiang; Qiu-Xiang Liu (Chemical Engineering Journal, 2024)

Organic fertilization strengthens multiple internal pathways for soil mineral nitrogen production: evidence from the meta-analysis of long-term field trials - Ahmed S. Elrys; Shending Chen; Mengru Kong; Lijun Liu; Qilin Zhu; Xiaoqian Dan; Shuirong Tang; Yanzheng Wu; Lei Meng; Jinbo Zhang; Christoph Müller (Biology and Fertility of Soils, 2024)

Coordination Between Bioelements Induce More Stable Macroelements Than Microelements in Wetland Plants - Zhenjun Zuo; Peter B. Reich; Xiujuan Qiao; Haocun Zhao; Liangjian Zhang; Lei Yang; Tian Lv; Zhiyao Tang; Dan Yu; Zhong Wang (Ecology Letters, 2024)
Elements are the basic substances that make up living organisms, and the element composition in plants quantitatively reflect the adaptation of plants to environment. However, the drivers that constitute the species‐specific plant elementome, as well as the bivariate bioelemental correlations in determining the stability of different bioelements are yet unclear. Based on 1058 leaf observations of 84 plant species from 232 wetlands across large environmental gradients, we found that bioelements with higher concentration were more stable and evolutionary constrained. We proposed a stability of well‐coordinated elements hypothesis, suggesting that bioelements that coordinate well in driving certain physiological functions constrain each other, thus maintaining relatively stable ratios in plants. In contrast, those functionally independent bioelements fluctuate greatly with environmental nutrient availability. Cold and saline stresses decreased plant stoichiometric network connectivity, complexity, and stability. Our research filled the gap in study of wetland plant elementome, and provided new evidences of plant–environment interactions in regions sensitive to climate change.

Comparative transcriptome analysis reveals the immune defense mechanism of the red swamp crayfish (Procambarus clarkii) in response to Vibrio parahaemolyticus challenge - Xiang Lu; Sheng Tang; Xin Liu; Jun-Jie Jiang; Dan-Dan Bian; Dai-Zhen Zhang; Qiu-Ning Liu; Yong-Xu Cheng; Bo-Ping Tang; Li-Shang Dai (Aquaculture, 2024)

Assessing the potential of mariculture to provide ecosystem services based on cultured species, modes and regions - Yazhou Tang; Yu Tang; Rong Chen; Linyuan Chen; Dan Zhou; Jianhui Xue; Yongbo Wu; Yinlong Zhang (Ocean & Coastal Management, 2024)

Effect of lead exposure on silkworm midgut: Insights into oxidative gene expression, digestive function, and microbial community structure - Yan-Xia Shi; Dan-Dan Bian; Fan-Xing Chen; Ye Jin; Qi Jiang; Qiu-Ning Liu; Bo-Ping Tang; Li-Shang Dai (Process Safety and Environmental Protection, 2024)

Early Cretaceous fayalite-, ferrosilite-, and biotite-bearing rhyolitic porphyries in the Baishuizhai area, South China: Formation by fractional crystallization in the shallow crust - Xiao Liu; Qiang Wang; Xi-Jun Liu; Lin Ma; Derek A. Wyman; Gong-Jian Tang; Wei Dan; Zi-Qi Jiang; Hao Wu; Wan-Long Hu; Jin-Heng Liu; Chuan-Bing Xu; et al. (Lithos, 2024)

Late cretaceous intraplate magmatism in Central and South Pamir: Response to edge-driven convection - Xin Ma; Jian Wang; Wei Dan; Qiang Wang; Guo-Rong Tang; Mustafo Gadoev; Ilhomjon Oimahmadov; Murodov Azamdzhon; Sharifjon Odinaev; Gong-Jian Tang (Lithos, 2024)

Rational design of molecularly imprinted electrochemical sensor based on Nb2C-MWCNTs heterostructures for highly sensitive and selective detection of Ochratoxin a - Hao Huang; Weiwei Ouyang; Kehuai Feng; María Belén Camarada; Tao Liao; Xinjie Tang; Rumeng Liu; Dan Hou; Xiaoning Liao (Food Chemistry, 2024)

Myo-inositol: A potential game-changer in preventing gill cell death and alleviating “gill rot” in grass carp (Ctenopharyngodon idellus) - Jie Chen; Wei-Dan Jiang; Lin Feng; Pei Wu; Yang Liu; Xiao-Wan Jin; Hong-Mei Ren; Jia-Yong Tang; Rui-Nan Zhang; Xiao-Qiu Zhou (Fish & Shellfish Immunology, 2024)

Size-resolved molecular characterization of water-soluble organic matter in atmospheric particulate matter from northern China - Cuiping Ning; Yuan Gao; Shuai Sun; Haiming Yang; Wei Tang; Dan Wang (Environmental Research, 2024)

Design of enhanced entropy-driven non-covalent DNA catalytic reactions via the paired junction structure - Weitao Wang; Hongyan Yu; Xiaole Han; Li Zhang; Zhi Weng; Chen Zuo; Na Yin; Yaoyi Zhang; Tong Feng; Dan Bai; Ao Tang; Yongcan Guo; et al. (Chemical Engineering Journal, 2024)

Validation and revision of low latitudes cloud base height from ERA5 - Dan Li; Yuzhi Liu; Run Luo; Weiqi Tang; Jie Gao; Ziyuan Tan (Atmospheric Research, 2024)

Effect of remediation technologies on soil fertility in heavy metal(loid)-contaminated soils: A critical review - Lizhi He; Yan Xu; Mengen Zhang; Saima Gul; Xiaokai Zhang; Huan Zhong; Yanxin Tang; Dubin Dong; Yong Xu; Dan Liu; Nanthi Bolan; Hailong Wang (Critical Reviews in Environmental Science and Technology, 2024)

Impacts of land surface darkening on frozen ground and ecosystems over the Tibetan Plateau - Shuchang Tang; Tao Wang; Dan Liu; Tandong Yao; Shilong Piao (Science China Earth Sciences, 2024)

Extraction and purification, pharmacological action, synthesis and product development of salidroside: a review - Yaxiao Liu; Linwei Dan; Jiamei Tang; Zitong Yin; Longzhu Yang; Dongdong Zhang; Xiaomei Song; Wei Wang; Yuze Li (Medicinal Chemistry Research, 2024)

Nitrogen fertilization increases the niche breadth of soil nitrogen-cycling microbes and stabilizes their co-occurrence network in a karst agroecosystem - Xionghui Liao; Tiangang Tang; Jiangnan Li; Jiachen Wang; Deborah A. Neher; Wei Zhang; Jun Xiao; Dan Xiao; Peilei Hu; Kelin Wang; Jie Zhao (Agriculture, Ecosystems & Environment, 2024)

Simultaneously inhibit cadmium and arsenic uptake in rice (Oryza sativa L.) by Selenium enhanced iron plaque: Performance and mechanism - Peicheng Huang; Dan Zou; Chunhua Dong; Chongjian Tang; Qingzhu Li; Pengwei Zhao; Ping Zhang; Qi Liao; Zhihui Yang (Chemosphere, 2024)

The role of pantothenic acid in alleviating hypoxia-induced liver injury of sub-adult grass carp (Ctenopharyngodon idellus): Possible mechanisms and implication - Yan Xia; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Jia-Yong Tang; Rui-Nan Zhang; Lu Zhang; Hai-Feng Mi; Lin Feng (Aquaculture, 2024)

Transcriptome analysis of porcine oocytes during postovulatory aging - Wenjie Yu; Xinyue Peng; Xiaoshi Cai; Hong Xu; Chen Wang; Fengjiao Liu; Dan Luo; Shuhan Tang; Yue Wang; Xiaoxue Du; Yan Gao; Tian Tian; et al. (Theriogenology, 2024)

Ruthenium-modified catalyst Ru-CeO2 significantly enhances mercury removal from sulfur-containing coal flue gas - Dan Zhang; Yiming Tang; Anchao Zhang; Zhihui Zhang; Yonghui Li; Fahui Wang; Qian Wang (Process Safety and Environmental Protection, 2024)

BpAFP, a Broussonetia papyrifera latex chitinase, exhibits a dual role in resisting to both Verticillium wilt disease and lepidopterous pests, Plutella xylostella and Prodenia litura - Xianbi Li; Dan Jin; Feifei Yi; Meng Tang; Siyi Wan; Yanhua Fan; Yuehua Xiao; Ting Liu; Hui Li; Jiancong Li; Mingliang Qiu; Yan Pei (Plant Science, 2024)

Expression of a novel hydrolase MhpC in Brevibacillus parabrevis BCP-09 and its characteristics for degrading synthetic pyrethroids - Yingyue Zhang; Dan Xiang; Jie Tang; Chuanning Peng; Siqi Chen; Siqi Huang; Qi Wen; Lin Liu; Wenliang Xiang; Qing Zhang; Ting Cai; Xuan Yu (Pesticide Biochemistry and Physiology, 2024)

10Be exposure age data reveals last Glacial ice sheet histories in the Larsemann Hills of East Antarctica - Luming Chen; Zhigang Zhang; Jingxue Guo; Lin Li; Xueyuan Tang; Dan Zhao; Hongmei Zhang; Yi Lin (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Boosted energy storage densities in lead-free Na0.5Bi0.5TiO3-based thick film ceramics via the compositional and microstructural tailoring - Xiang Niu; Yuleng Jiang; Wei Liang; Huanwei Liu; Xiaodong Jian; Xianyi Chen; Wenhan Zeng; Mingtao Xu; Dan Qie; Zichun Zhu; Yufeng Liu; Yi Tang; et al. (Chemical Engineering Journal, 2024)

Arc building and maturation of the Lombok Island, East Sunda Arc - Guo-Rong Tang; Wei Dan; Adi Maulana; Jian Wang; Xiu-Zheng Zhang; Yun-Ying Zhang; Xin Ma; Qiang Wang; Xi-Jun Liu; Gong-Jian Tang (Chemical Geology, 2024)

Critical threshold mining of landslide deformation and intelligent early-warning methods based on multi-factor fusion - Dunlong Liu; Dan Tang; Juan Ma; Shaojie Zhang; Hongjuan Yang; Xuejia Sang (Bulletin of Engineering Geology and the Environment, 2024)

Variation of root traits and its influences on soil organic carbon stability in response to altered precipitation in an alpine meadow - Xiaoyan Song; Changting Wang; Dan Liu; Fusheng Qiao; Guo Tang; Zalmen Henkin (Science of The Total Environment, 2024)

Analysis of mercury removal and sulfur resistance of CrOx-MnOx-SnOx-TiO2 catalysts - Dan Zhang; Yiming Tang; Anchao Zhang; Ziyi Jing; Yonghui Li; Fahui Wang; Yuyan Wang (Process Safety and Environmental Protection, 2024)

Exploring the novel benefits of leucine: Protecting nitrite-induced liver damage in sub-adult grass carp (Ctenopharyngodon idella) through regulating mitochondria quality control - Lu-Lu Zhen; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Ling Tang; Shu-Wei Li; Cheng-Bo Zhong; Xiao-Qiu Zhou (Fish & Shellfish Immunology, 2024)

Microstructure size and packing of fracture surface on the nonlinear breakage mechanical response of different marbles under cyclic loading - Hu-dan Tang; Ming-li Zhu; Zhen-hua Li (Engineering Geology, 2024)

Durable and highly signal-stable pressure sensors prepared by sequential thiol-acrylate click reactions - Wanqi Feng; Yu Jiang; Junjie Tang; Yixiang Chen; Tao Zhang; Dan Yu; Wei Wang (Chemical Engineering Journal, 2024)

Dynamic hydrogel-integrated microneedle patch with extracellular vesicles encapsulation for wound healing - Dan Wu; Xiangyi Wu; Qichen Luan; Qing Tang; Lu Fan; Xin Shou; Xia Gao; Xiaoyun Qian; Yuanjin Zhao (Chemical Engineering Journal, 2024)

Engineering disease-resistant plants with alternative translation efficiency by switching uORF types through CRISPR - Jingjing Tian; Zhijuan Tang; Ruixia Niu; Yulu Zhou; Dan Yang; Dan Chen; Ming Luo; Rui Mou; Meng Yuan; Guoyong Xu (Science China Life Sciences, 2024)

Anti-inflammatory and analgesic properties of Polyphyllin VI revealed by network pharmacology and RNA sequencing - Zhenglang Zhang; Tingting Wang; Zhenhui Luo; Muhammad Haris Zaib; Mengqin Yi; Hekun Zeng; Peiyang Li; Dan Tang; Alexei Verkhratsky; Hong Nie (Purinergic Signalling, 2024)

Correction to: The connection between six common air pollution particles and adult brain tumors: a meta-analysis of 26,217,930 individuals - Lu-Ting Shen; Meng-Wei Ge; Fei-Hong Hu; Yi-Jie Jia; Wen Tang; Wan-Qing Zhang; Dan-Yan Zhao; Wang-Qin Shen; Hong-Lin Chen (Environmental Science and Pollution Research, 2024)

Spatial Variation in CO2 Concentration Improves the Simulated Surface Air Temperature Increase in the Northern Hemisphere - Jing Peng; Li Dan; Xiba Tang (Advances in Atmospheric Sciences, 2024)

Taurine prevented the decline of fillet quality and muscle antioxidant capacity in on-growing grass carp (Ctenopharyngodon idella) fed non-fishmeal diet - Shun-Shi Sun; Liang-Chao Yan; Lin Feng; Wei-Dan Jiang; Yang Liu; Ling Tang; Pei Wu; Xiao-Qiu Zhou (Aquaculture, 2024)

Proteomic analysis of milk fat globule membrane proteins in mature human milk of women with and without gestational diabetes mellitus - Dan Yao; Cai Shen; Jingwen Yu; Jiayue Tang; Hong Zhang; Xuebing Xu; Maolin Tu; Ling-Zhi Cheong (Food Chemistry, 2024)

Genome-wide association studies dissect low-phosphorus stress response genes underling field and seedling traits in maize - Bowen Luo; Guidi Zhang; Ting Yu; Chong Zhang; Guohui Yang; Xianfu Luo; Shuhao Zhang; Jianyong Guo; Haiying Zhang; Hao Zheng; Zirui Tang; Qile Li; et al. (Theoretical and Applied Genetics, 2024)

Exploring the phosphorus–starch content balance mechanisms in maize grains using GWAS population and transcriptome data - Bowen Luo; Haiying Zhang; Zheng Han; Xiao Zhang; Jianyong Guo; Shuhao Zhang; Xianfu Luo; Jin Zhao; Wei Wang; Guohui Yang; Chong Zhang; Jing Li; et al. (Theoretical and Applied Genetics, 2024)

Is short-term exposure to primary gaseous air pollutants associated with AIDS-related deaths? Evidence from a time-stratified case-crossover study - Dan Sun; Faxue Zhang; Lianguo Ruan; Dingyuan Zhao; Heng Tang; Wei Zhu (International Journal of Biometeorology, 2024)

An appetite assessment method for fish in outdoor ponds with anti-shadow disturbance - Weiqiang Ni; Dan Wei; Zequn Peng; Zhen Ma; Songming Zhu; Rong Tang; Xuelei Tian; Jian Zhao; Zhangying Ye (Computers and Electronics in Agriculture, 2024)

Minor ergosteroids and a 19-nor labdane-type diterpenoid with anti-inflammatory effects from Ganoderma lucidum - Dan Cai; Yun-Yun Liu; Xin-Ping Tang; Mei Zhang; Yong-Xian Cheng (Phytochemistry, 2024)

High-pressure microfluidization enhanced the stability of sodium caseinate-EGCG complex-stabilized fish oil emulsion - Wei Tang; Rui Wang; Minghui Li; Qingchun Zhang; Jianfei He; Dan Liu; Yuqi Feng; Weilin Liu; Jianhua Liu (Food Chemistry, 2024)

The relationships between high-fat diet and metabolic syndrome: Potential mechanisms - Chao Tang; Yuxin Wang; Zeyu Xu; Dan Chen; Jingguo Xu; Duo Yang; Li Zhang; Jun Liu; Juan Kan (Food Bioscience, 2024)

Is cryoablation still suitable for advanced non-small cell lung cancer after failure of first-line chemotherapy? A multicenter, prospective, randomized-controlled trial of eighty-seven patients - Yu Chen; Xueni Fang; Dan Wang; Quanwang Li; Kerui Zhang; Yuan Li; Jinghua Li; Haoyue Pang; Zhiqiang Cheng; Chunyang Zhang; Caiyun Zhang; Wuwei Yang; et al. (Cryobiology, 2024)

Investigating cultivation strategies for enhancing protein content in Auxenochlorella pyrenoidosa FACHB-5 - Qun Wei; Ting Yuan; Zhuang Li; Dan Zhao; Canmei Wang; Gairen Yang; Wangwang Tang; Xiangmeng Ma (Bioresource Technology, 2024)

Recognition of ethylene plasma image based on dual residual with attention mechanism network - Baoxia Li; Wenzhuo Chen; Shaohuang Bian; A Lusi; Xiaojiang Tang; Yang Liu; Junwei Guo; Dan Zhang; Cheng Yang; Feng Huang (Rendiconti Lincei. Scienze Fisiche e Naturali, 2024)

Peroxynitrite imaging in ferroptosis-mediated drug-induced liver injury with a near-infrared fluorescence probe - Ruixin Liu; Haijing Jiang; Wenjie Yang; Zhijuan Zheng; Xiaoming Wang; Zhenhua Tian; Danyang Wang; Dongfang Kan; Dan Zhang; Zhixin Tang (Analytica Chimica Acta, 2024)

β-Sitosterol alleviates the malignant phenotype of hepatocellular carcinoma cells via inhibiting GSK3B expression - Ruoyu Wang; Dan Tang; Longyun Ou; Jiacheng Jiang; Yu-nan Wu; Xuefei Tian (Human Cell, 2024)
To explore the effects of β-Sitosterol upon hepatocellular carcinoma cell proliferation, apoptosis, migration, invasion, and epithelial–mesenchymal transition (EMT), and to investigate the underlying mechanism using network pharmacology. Human hepatocellular carcinoma cell lines (Huh-7 and HCCLM3) were expose to gradient concentrations of β-Sitosterol (5 μg/mL, 10 μg/mL, and 20 μg/mL). Cell viability and proliferation were assessed using MTT, CCK-8, colony formation, and EdU assays.Flow cytometry was employed to evaluate cell cycle and apoptosis. Scratch and Transwell assays were performed, respectively, to detect cell migration and invasion. The levels of apoptosis-associated proteins (BAX, BCL2, and cleaved caspase3) as well as EMT-associated proteins (E-cadherin, N-cadherin, Snail, and Vimentin) were detected in Huh-7 and HCCLM3 cell lines using Western blot analysis. The drug target gene for β-Sitosterol was screened via PubChem and subsequently evaluated for expression in the GSE112790 dataset. In addition, the expression level of glycogen synthase kinase 3 beta (GSK3B) within the Cancer Genome Atlas-Liver Hepatocellular Carcinoma (TCGA-LIHC) database was analyzed, along with its correlation to the survival outcomes of patients with hepatocellular carcinoma. The diagnostic efficiency of GSK3B was assessed by analyzing the ROC curve. Subsequently, Huh-7 and HCCLM3 cell lines were transfected with the overexpression vector of GSK3B and then treated with β-Sitosterol to further validate the association between GSK3B and β-Sitosterol. GSK3B demonstrated a significantly elevated expression in patients with hepatocellular carcinoma, which could predict hepatocellular carcinoma patients’ impaired prognosis based on GEO dataset and TCGA database. GSK3B inhibitor (CHIR-98014) notably inhibited cell proliferation and invasion, promoted cell apoptosis and cell cycle arrest at G0/G1 phase in hepatocellular carcinoma cells. β-Sitosterol treatment further promoted the efffects of GSK3B inhibitor on hepatocellular carcinoma cells. GSK3B overexpression has been found to enhance the proliferative and invasive capabilities of hepatocellular carcinoma cells. Furthermore it has been observed that GSK3B overexpression, it has been obsear can partially reverse the inhibitory effect of β-Sitosterol upon hepatocellular. β-Sitosterol suppressed hepatocellular carcinoma cell proliferation and invasion, and enhanced apoptosis via inhibiting GSK3B expression.

New sight in arginine-improved flesh quality: Role of MRFs, cyclins, and WNT signaling in grass carp (Ctenopharyngodon idellus) - Yu-Long Ma; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Hong-Mei Ren; Rui-Nan Zhang; Shu-Wei Li; Ling Tang; Lin Feng (Aquaculture, 2024)

Aggregation of graphene oxide upon the stripping of oxidized debris: An experimental and molecular dynamics simulation study - Jiahai Yu; Wenli Li; Dan Zhang; Tinglin Huang; Huan Tang (Environmental Pollution, 2024)

Single-atom Fe with Fe-N4F1 structure showing superior performances for semi-hydrogenation of alkynol - Haiyang Xie; Dan Tang; Yanjuan Zhang; Zuqiang Huang; Huayu Hu; Qian He; Hongbing Ji; Tao Gan (Chemical Engineering Journal, 2024)

Compound impacts of South Asian summer monsoon and westerlies on summer precipitation over Tibetan Plateau - Xuefeng Dong; Yuzhi Liu; Xiaoqiang Yan; Yingsi Wang; Ziyuan Tan; Min Luo; Dan Li; Ying Wang; Shijia Tang (Climate Dynamics, 2024)

Development of a novel fluorescent protein-based probe for efficient detection of Pb2+ in serum inspired by the metalloregulatory protein PbrR691 - Dan Wang; Min Wei; Liu Zhao; Tianyu Song; Qunfang Li; Jiaxin Tan; Jing Tang; Zhipeng Li; Rukui Zhu (Analytica Chimica Acta, 2024)

The emerging role of zinc on alleviating inflammatory responses and enhancing immunity in grass carp (Ctenopharyngodon idella) - Xin Zeng; Zheng-Xing Song; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Ling Tang; Shu-Wei Li; Juan Yang; Lin Feng (Aquaculture, 2024)

Acetyl-11-keto-beta-boswellic acid inhibits cell proliferation and growth of oral squamous cell carcinoma via RAB7B-mediated autophagy - Dan Pan; Qing Wang; Shouyi Tang; Xingbo Wu; Luyao Cai; Zhen Wang; Ying Li; Mei Huang; Yu Zhou; Ying-Qiang Shen (Toxicology and Applied Pharmacology, 2024)

Lithology and niche habitat have significant effect on arbuscular mycorrhizal fungal abundance and their interspecific interactions - Dan Xiao; Yixin Tang; Wei Zhang; Peilei Hu; Kelin Wang (Science of The Total Environment, 2024)

Enhancement of pyranoanthocyanin formation in blueberry wine with non-Saccharomyces yeasts - Jianli Zhou; Chuqi Tang; Shuliang Zou; Liangbo Lei; Yuangen Wu; Wenhua Yang; Jean Damascene Harindintwali; Jiang Zhang; Wenwen Zeng; Dan Deng; Manman Zhao; Xiaobin Yu; et al. (Food Chemistry, 2024)

Effects of maternal and perinatal factors on human milk fat globule membrane proteome: A data independent acquisition approach - Jiayue Tang; Dan Yao; Cai Shen; Jingwen Yu; Hong Zhang; Xuebing Xu; Maolin Tu; Ling-Zhi Cheong (Food Bioscience, 2024)

New insight into identifying sediment phosphorus sources in multi-source polluted urban river: Effect of environmental-induced microbial community succession on stability of microbial source tracking results - Wenlong Zhang; Zikang Tang; Yuting Yan; Chenyue Sun; Dan He; Yi Li (Environmental Research, 2024)

Ubiquitous occurrence of p-Phenylenediamine (PPD) antioxidants and PPD-quinones in fresh atmospheric snow and their amplification effects on associated aqueous contamination - Xu Zhang; Zifang Peng; Shijiao Hou; Qiannan Sun; Hang Yuan; Dan Yin; Wenfen Zhang; Yanhao Zhang; Jianwei Tang; Shusheng Zhang; Zongwei Cai (Journal of Hazardous Materials, 2024)

Comprehensive assessment of the extraction of Phyllanthus emblica L. based on the G1-Entropy Method and Response Surface Methodology - Zhen-Yu Gai; Ying Wang; Ming-Hua Xian; Dan Tang; Shu-Mei Wang (Journal of Applied Research on Medicinal and Aromatic Plants, 2024)

Reduction of antigenicity and emulsibility improvement of ovalbumin by dielectric-barrier discharge plasma treatment induced structure modification - Pan-Pan Tang; Lin-Lin Zhang; Yu-Xin Xiong; Dan-Dan Jiang; Xiu-Bin Liu; Jun-Hu Cheng; Rana Muhammad Aadil; Zhi-Wei Liu (Innovative Food Science & Emerging Technologies, 2024)

Characterization of key flavor substances and their microbial sources in traditional sour bamboo shoots - Hui Tang; Jin-Kui Ma; Lin Chen; Li-Wen Jiang; Lin-Zhi Kang; Ying-Yu Guo; Ge-Yang Men; Dan-Xia Nie; Rui-Min Zhong (Food Chemistry, 2024)

Shaping the succession patterns of different soil nutrients, enzyme stoichiometry, and microbial communities through rotation systems - Dan Liu; Yang Liu; Junjie Li; Qin Mo; Junyan Tang; Wenhan Liu; Maksat Batyrbek; Tiening Liu; Xudong Zhang; Qingfang Han (CATENA, 2024)

One-line hybrid rice with high-efficiency synthetic apomixis and near-normal fertility - Junhao Dan; Yumei Xia; Yao Wang; Yijie Zhan; Junyou Tian; Ning Tang; Huafeng Deng; Mengliang Cao (Plant Cell Reports, 2024)
Key message High-frequency clonal seeds and near-normal fertility were obtained by engineering synthetic apomixis in hybrid rice. Abstract The one-line strategy, with the advantage of unnecessary seed production, is the final stage for the hybrid rice development and can be achieved through the fixation of heterosis via artificially inducing apomixis. Recently, synthetic apomixis has been generated in rice by combining MiMe (Mitosis instead of Meiosis) with either the ectopic expression of BABY BOOM ( BBM1 or BBM4 ) or mutation of MATRILINEAL ( MTL ), resulting in over 95.00% of clonal seeds. However, the frequency of clonal seeds was only 29.20% when AtDD45 promoter was used to drive BBM1 . In addition, achieving both a high frequency of clonal seeds and near-normal fertility simultaneously had been elusive in earlier strategies. In this study, using AtDD45 promoter to drive BBM1 expression in combination with the MiMe mutant resulted in the apomixis frequency as high as 98.70%. Even more, employing fusion promoters ( AtMYB98 _ AtDD1 _ OsECA1-like1 ) to drive WUS expression in combination with pAtDD45 : BBM1 and MiMe could produce clonal seeds at rates of up to 98.21%, the highest seed setting rate reached to 83.67%. Multiple-embryos were observed in clonal lines at a frequency ranging from 3.37% to 60.99%. Transmission of the high frequency of apomixis through skipped generations (atavism) was identified in two clonal lines, even though it remained stable in the majority of clonal lines. These findings significantly advance the pursuit of fixed heterosis in rice through synthetic apomixis, edging closer to its agricultural application.

Mechanism of deltamethrin biodegradation by Brevibacillus parabrevis BCP-09 with proteomic methods. - Yingyue Zhang; Jie Tang; Su Wang; Xuerui Zhou; Chuanning Peng; Hu Zhou; Dan Wang; Haoran Lin; Wenliang Xiang; Qing Zhang; Ting Cai; Xuan Yu (Chemosphere, 2024)

Energy-efficient flexible job shop scheduling problem considering discrete operation sequence flexibility - Guiliang Gong; Jiuqiang Tang; Dan Huang; Qiang Luo; Kaikai Zhu; Ningtao Peng (Swarm and Evolutionary Computation, 2024)

Photocatalytic degradation of perfluorooctanoic acid (PFOA) from water: A mini review - Peiru Luo; Yangyang Zhang; Zifang Peng; Qingyun He; Wuduo Zhao; Wenfen Zhang; Dan Yin; Yanhao Zhang; Jianwei Tang (Environmental Pollution, 2024)

Human Bone Marrow Derived-Mesenchymal Stem Cells Treatment for Autoimmune Premature Ovarian Insufficiency - Wen-Qing Ma; Ai-Ping Zhuo; Yuan-Ling Xiao; Meng Gao; Yu-Tao Yang; Li-Chao Tang; Yan-Hong Wu; Dan Tian; Xia-Fei Fu (Stem Cell Reviews and Reports, 2024)

Key issues to consider toward an efficient constructed wetland-microbial fuel cell: the idea and the reality - Diaodiao Li; Yaqian Zhao; Dan Wei; Cheng Tang; Ting Wei (Environmental Science and Pollution Research, 2024)

In vitro and in vivo anti-oomycetes activities and mechanisms of linalool against Saprolegnia ferax - Tao Tang; Weiming Zhong; Linlin Yang; Mingwang He; Sifan Jiang; Dan Yin; Jiajing Guo; Zhipeng Gao (Aquaculture, 2024)

SERS and MRS signals engineered dual-mode aptasensor for simultaneous distinguishment of aflatoxin subtypes - Honghui Cao; Dan Liang; Kaizhen Tang; Yu Sun; Yinjuan Xu; Ming Miao; Yuan Zhao (Journal of Hazardous Materials, 2024)

Early Cretaceous magmatic-hydrothermal processes for the lode Yingdongpo gold and Poshan silver deposits in the Tongbai Orogen, central China - Jiang Zhu; Dan-yang Liu; Chao Chen; Song Chen; Yuan-bing Zou; Leonid V. Danyushevsky; Jing-meng Huang; Xiang-wei Tang (Journal of Asian Earth Sciences, 2024)

Vertical distribution of VOCs in the boundary layer of the Lhasa valley and its impact on ozone pollution - Dan Yao; Yinghong Wang; Zhixuan Bai; Mengtian Cheng; Guiqian Tang; Yuting Liu; Deqing Zhuoga; Hao Yu; Jianchun Bian; Yuesi Wang (Environmental Pollution, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Aridity creates global thresholds in soil nitrogen retention and availability - Ahmed S. Elrys; Mohamed F. Abo El‐Maati; Xiaoqian Dan; YuHong Wen; Jinxia Mou; Ahmed Elsayed Abdelghany; Yves Uwiragiye; Tang Shuirong; Wu Yanzheng; Lei Meng; JinBo Zhang; Christoph Müller (Global Change Biology, 2024)
Identifying tipping points in the relationship between aridity and gross nitrogen (N) cycling rates could show critical vulnerabilities of terrestrial ecosystems to climate change. Yet, the global pattern of gross N cycling response to aridity across terrestrial ecosystems remains unknown. Here, we collected 14,144 observations from 451 15 N‐labeled studies and used segmented regression to identify the global threshold responses of soil gross N cycling rates and soil process‐related variables to aridity index (AI), which decreases as aridity increases. We found on a global scale that increasing aridity reduced soil gross nitrate consumption but increased soil nitrification capacity, mainly due to reduced soil microbial biomass carbon (MBC) and N (MBN) and increased soil pH. Threshold response of gross N production and retention to aridity was observed across terrestrial ecosystems. In croplands, gross nitrification and extractable nitrate were inhibited with increasing aridity below the threshold AI ~0.8–0.9 due to inhibited ammonia‐oxidizing archaea and bacteria, while the opposite was favored above this threshold. In grasslands, gross N mineralization and immobilization decreased with increasing aridity below the threshold AI ~0.5 due to decreased MBN, but the opposite was true above this threshold. In forests, increased aridity stimulated nitrate immobilization below the threshold AI ~1.0 due to increased soil C/N ratio, but inhibited ammonium immobilization above the threshold AI ~1.3 due to decreased soil total N and increased MBC/MBN ratio. Soil dissimilatory nitrate reduction to ammonium decreased with increasing aridity globally and in forests when the threshold AI ~1.4 was passed. Overall, we suggest that any projected increase in aridity in response to climate change is likely to reduce plant N availability in arid regions while enhancing it in humid regions, affecting the provision of ecosystem services and functions.

Recycling and transport of evapotranspiration over the Tibetan Plateau: Detected by a water vapour tracer method embedded in regional climate model - Yingge Tang; Jingyu Dan; Meng Zhang; Haojun Jiang; Yanhong Gao (International Journal of Climatology, 2023)
With an average elevation of 4000 m, the Tibetan Plateau (TP) exerts a global influence on weather and climate. To investigate and quantify the impact of terrestrial evapotranspiration (ET) over the TP on both local and downstream regions, we employed the water vapour tracer (WVT) method integrated into the Weather Research and Forecasting (WRF) model to track the propagation of evaporative moisture across the TP. Based on precipitation landing location, termination of evaporative moisture over the TP was categorized into recycled ET (ET in , which precipitates inside the TP) and moving‐out ET (ET out , which precipitates outside the TP). Our findings reveal that ET in dominates 70% of ET moisture termination over the TP, exhibiting a decrease gradient from eastern to western regions. The majority of ET out spreads eastward with some reaching southward. Seasonal variations indicate that more than 75% of ET recycles during summer, while more ET moves out from TP in spring and autumn. The interplay between convection and advection leads to different reach‐outs for moving‐out ET in summer compared to other seasons: strong convection and diabatic heating plus a relative weak large‐scale advection result in shorter reach‐outs during summer, whereas weaker convection combined with strong advection leads to longer ‐reach‐outs in other seasons. This study enhances our understanding of terrestrial ET moisture transport over the TP as well as its mechanism influencing both local water cycle dynamics and downstream processes.

LncRNA SPRY4-IT1 regulates 16HBE cell malignant transformation induced by particulate matter through DUSP6-ERK1/2-Chk1 signaling pathway - Yanli Li; Dan Tang; Jian Zhang; Wanting Ou; Xuan Sun; Qiaoyuan Yang; Jianjun Wu (Chemosphere, 2023)

Improvement of flesh quality, muscle growth and protein deposition in adult grass carp (Ctenopharyngodon idella): The role of tryptophan - Lu-Qiao Xiao; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Ling Tang; Shu-Wei Li; Cheng-Bo Zhong; Rui-Nan Zhang; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2023)

Isalo scorpion Cytotoxic peptide (IsCT) improved the physical barrier of the intestine on on-growing grass carp (Ctenopharyngodon idella) - Chong Zhang; Qi-Yu Hu; Lin Feng; Pei Wu; Yang Liu; Sheng-Yao Kuang; Ling Tang; Jiang Li; Xiao-Qiu Zhou; Wei-Dan Jiang (Aquaculture, 2023)

Rapid and sensitive Cas13a/Cas12a-based one-pot dual-target strategy to detect monkeypox virus and its co-infected viruses - Xiao Wang; Qiao Rao; Zhengrong Lu; Xiaobao Deng; Rong Shen; Rui Wang; Weiyi Dong; Xianhua Qi; Zhen Jin; Youzhi Tang; Dan Du (Science Bulletin, 2023)

Identification and characterization of a novel Iflavirus in a stored-product psocid, Liposcelis bostrychophila (Psocodea: Liposcelididae) - Peng-Yu Guo; Dan-Dan Wei; Hua-Yue Feng; Xin-Ping Tang; Yu-Ang Chen; Yi Li; Jin-Jun Wang (Journal of Stored Products Research, 2023)

Effect of Proinflammatory S100A9 Protein on Migration and Proliferation of Microglial Cells - Qiao Bai; Dan Sun; Yang Zeng; Jie Zhu; Ce Zhang; Xiaoyin Zhang; Li Chen; Xin Zhou; Liu Ye; Yong Tang; Yonggang Liu; Ludmilla A. Morozova-Roche (Journal of Molecular Neuroscience, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Reducing spatial resolution increased net primary productivity prediction of terrestrial ecosystems: A Random Forest approach - Tao Zhou; Yuting Hou; Zhihan Yang; Benjamin Laffitte; Ke Luo; Xinrui Luo; Dan Liao; Xiaolu Tang (Science of The Total Environment, 2023)

Seco-iridoid glycosides from the Gentiana olivieri Griseb and their bioactivities - Reyilan Maituoheti; Ruxianguli Rouzimaimaiti; Dan Tang; Jiangyu Zhao; Haji Akber Aisa (Phytochemistry, 2023)

Efficient genome editing in cotton using the virus-mediated CRISPR/Cas9 and grafting system - Wei-Feng Guo; Dan-Dan Guo; Fen Li; Shen-Zhai Shang; Ting-Wan Li; Ying-Chao Tang; Man Jiang; Fu-Chun Xu; Wei Gao (Plant Cell Reports, 2023)

The Research Progress and Prospects of the NIGT1.2 Gene in Plants - Qiang Lv; Wenjun Ji; Hao Chu; Mingtong You; Weiwei Tang; Min Chen; Yu Huang; Paul Promise Michael; Bo Zhou; Fenghua Wang; Dan Peng (Journal of Plant Growth Regulation, 2023)

Hybrid chain reaction and selective recognition-based homogeneous dual-fluorescence analysis of circulating tumor cells in clinical ovarian cancer samples - Qian Hu; Dan Tang; Mei Li; Xiaodu Liang; Juan Zhou; Yanming Meng; Yinhao Wei; Shixin Yan; Ruoyu Lin; Xiaoyu Niu; Lin Zhang (Analytica Chimica Acta, 2023)

By reconstructing a multifunctional intensive microbiome, effective microorganisms (EM) improve the ecological environment of rice–crayfish cocropping - Yang Zhang; Bao-Ying Wang; Jun Zhang; Ying-Han Liu; Dan-Yao Tang; Jun Zhao; Chuan-Chao Dai (Agriculture, Ecosystems & Environment, 2023)

The connection between six common air pollution particles and adult brain tumors: a meta-analysis of 26,217,930 individuals - Lu-Ting Shen; Meng-Wei Ge; Fei-Hong Hu; Yi-Jie Jia; Wen Tang; Wan-Qing Zhang; Dan-Yan Zhao; Wang-Qin Shen; Hong-Lin Chen (Environmental Science and Pollution Research, 2023)

Dietary selenium promoted muscle growth (myofiber hypertrophy rather than hyperplasia) by reducing endoplasmic reticulum stress in juvenile grass carp (Ctenopharyngodon idella) - Ya Wang; Wei-Dan Jiang; Pei Wu; Yang Liu; Xiao-Wan Jin; Jun Jiang; Jia-Yong Tang; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2023)

Application of enzymatically treated Artemisia annua L. on adult grass carp (Ctenopharyngodon idella): Improved growth performance, intestinal antioxidant capacity and apical junctional complex - Qin-Qin Dai; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; He-Qun Shi; Lu Zhang; Hai-Feng Mi; Jia-Yong Tang; Rui-Nan Zhang; Lin Feng (Aquaculture, 2023)

Vanadium mobilization and redistribution during mineral transformation of vanadium-titanium magnetite tailings with different weathering degrees - Chun-dan Gan; Jin-yan Yang; Xin-yue Du; Jia-li Li; Qi-xuan Tang; Aleksander Nikitin (Science of The Total Environment, 2023)

Cretaceous magmatic migration and flare-up in Pamir–Karakoram - Xin Ma; Wei Dan; Jian Wang; Qiang Wang; Guo-Rong Tang; Mustafo Gadoev; Ilhomjon Oimahmadov; Gong-Jian Tang (Lithos, 2023)

Comparative study on the toxic effects of secondary nanoplastics from biodegradable and conventional plastics on Streptomyces coelicolor M145 - Xiaomei Liu; Shakeel Ahmad; Jingkang Ma; Dan Wang; Jingchun Tang (Journal of Hazardous Materials, 2023)

Natural polysaccharides protect against diet-induced obesity by improving lipid metabolism and regulating the immune system - Chao Tang; Yuxin Wang; Dan Chen; Man Zhang; Jingguo Xu; Chen Xu; Jun Liu; Juan Kan; Changhai Jin (Food Research International, 2023)

Dietary threonine improves muscle nutritional value and muscle hardness associated with collagen synthesis in grass carp (Ctenopharyngodon idella) - Mei-Lan Wen; Pei Wu; Wei-Dan Jiang; Yang Liu; Cai-Mei Wu; Cheng-Bo Zhong; Shu-Wei Li; Ling Tang; Lin Feng; Xiao-Qiu Zhou (Food Chemistry, 2023)

Nickel foam supported CuCe mixed metal oxide as monolith catalyst for NO removal - Fei Gao; Ying Tang; Jinbao Liu; Keke Pan; Mei Zhou; Gang Qian; Minmin Liu; Feng Yu; Jianming Dan; Bin Dai (Chemical Engineering Journal, 2023)

Root predominant overexpression of iaaM and CKX genes promotes root initiation and biomass production in citrus - Dan Tang; Yanjun Li; Longmei Zhai; Wei Li; Rahul Kumar; Huseyin Yer; Hui Duan; Baoping Cheng; Ziniu Deng; Yi Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)
Promoting initiation and biomass production of roots is significant for plant-based industries including using roots as bioreactors. Two citrus genotypes, Carrizo and US-897, were used as model plants to test the effects of root-predominantly overexpressed the iaaM (indoleacetic acid-tryptophan monooxygenase) gene and a CKX (a cytokinin oxidase/dehydrogenase) gene. The iaaM transgenic lines exhibited markedly faster root initiation, more root numbers, and higher root biomass compared to their wild-type counterparts. The transgenic iaaM + CKX plants also exhibited similar phenotypes, albeit to a lesser extent than the iaaM plants. Molecular analysis revealed an auxin-responsive CsGH3.1 gene was up-regulated in the iaaM roots and iaaM + CKX roots, and a cytokinin-responsive gene CsARR5 gene was down-regulated in the iaaM + CKX roots. Our results demonstrate that root predominant overexpression of the iaaM or both the iaaM and CKX genes drastically enhances the initiation, growth and biomass production of roots. These results provide additional support that manipulation of auxin and cytokinin levels in roots via transgenic or gene-editing technologies may benefit production of high-value secondary metabolites using roots as bioreactors and also improve rooting of recalcitrant plant species.

Mosses stimulate soil carbon and nitrogen accumulation during vegetation restoration in a humid subtropical area - Lumei Xiao; Wei Zhang; Peilei Hu; Lars Vesterdal; Jie Zhao; Li Tang; Dan Xiao; Kelin Wang (Soil Biology and Biochemistry, 2023)

As-hyperaccumulator Pteris vittata and non-hyperaccumulator Pteris ensiformis under low As-exposure: Transcriptome analysis and implication for As hyperaccumulation - Dan Sun; Xiang Zhang; Zeyu Yin; Huayuan Feng; Chunyan Hu; Nan Guo; Yetao Tang; Rongliang Qiu; Lena Q. Ma; Yue Cao (Journal of Hazardous Materials, 2023)

Opportunities and challenges in Asian bee research and conservation - Natapot Warrit; John Ascher; Parthib Basu; Vasuki Belavadi; Axel Brockmann; Damayanti Buchori; James B. Dorey; Alice Hughes; Smitha Krishnan; Hien T. Ngo; Paul Williams; Chao-Dong Zhu; et al. (Biological Conservation, 2023)

Role of iron in host-microbiota interaction and its effects on intestinal mucosal growth and immune plasticity in a piglet model - Zhenglin Dong; Shuan Liu; Qingqing Deng; Guanya Li; Yulong Tang; Xin Wu; Dan Wan; Yulong Yin (Science China Life Sciences, 2023)

Gut microbiota bridges the iron homeostasis and host health - Lanling Xiao; Rui Tang; Jie Wang; Dan Wan; Yulong Yin; Liwei Xie (Science China Life Sciences, 2023)

Dietary iron regulates intestinal goblet cell function and alleviates Salmonella typhimurium invasion in mice - Shuan Liu; Zhenlin Dong; Wenjie Tang; Jian Zhou; Liu Guo; Chengyan Gong; Guang Liu; Dan Wan; Yulong Yin (Science China Life Sciences, 2023)

Effects of biochar and inorganic amendments on soil fertility, tea yield, and quality in both Pb–Cd-contaminated and acidified tea plantations - Wenbin Liu; Yanxin Tang; Jiawei Ma; Weiling Zhang; Shiyan Liao; Shiyu Cui; Zhengqian Ye; Dan Liu (Journal of Soils and Sediments, 2023)

New insights into the protection of dietary components on anxiety, depression, and other mental disorders caused by contaminants and food additives - Ruo-Gu Xiong; Jiahui Li; Jin Cheng; Si-Xia Wu; Si-Yu Huang; Dan-Dan Zhou; Adila Saimaiti; Ao Shang; Guo-Yi Tang; Hua-Bin Li; Ren-You Gan; Yibin Feng (Trends in Food Science & Technology, 2023)

Nitrogen addition increases topsoil carbon stock in an alpine meadow of the Qinghai-Tibet Plateau - Jianliang Liu; Wei Zhan; Xinya Huang; Di Tang; Shaofei Jin; Dan Zhu; Huai Chen (Science of The Total Environment, 2023)

3D coaxial printing of porous construct stacked with hollow filaments for heavy metal removal - Yun Wu; Chunxia Tang; Pengxiang Si; Dan Zhang (Science of The Total Environment, 2023)

Experimental study on the decomposition and odor-release process of a decayed submerged plant—A case study of Potamogeton crispus - Dan Zhang; Xiaolong Cheng; Ran Li; Jingjie Feng; Lei Tang (Journal of Water Process Engineering, 2023)

Dynamics of vanadium and response of inherent bacterial communities in vanadium–titanium magnetite tailings to beneficiation agents, temperature, and illumination - Qi-xuan Tang; Chun-dan Gan; Jin-yan Yang; Yi Huang (Environmental Pollution, 2023)

The construction of a PAM-less base editing toolbox in Bacillus subtilis and its application in metabolic engineering - Yan Xia; Lichao Sun; Zeyu Liang; Yingjie Guo; Jing Li; Dan Tang; Yi-Xin Huo; Shuyuan Guo (Chemical Engineering Journal, 2023)

What are the Limiting Environmental Factors for the Evolution of Early Eukaryotic Diversity? - Shuichang Zhang; Xiaomei Wang; Huajian Wang; Qing Tang; Fenglian Zhang; Dan Lü (Journal of Earth Science, 2023)

Recent Progress in Studies on the Influences of Human Activity on Regional Climate over China - Jianping Duan; Hongzhou Zhu; Li Dan; Qiuhong Tang (Advances in Atmospheric Sciences, 2023)

Efficient mechanical exfoliation of MXene nanosheets - Yuchen Liu; Qi Tang; Mao Xu; Jie Ren; Chan Guo; Cheng Chen; Wenjing Geng; Weiwei Lei; Xiaoli Zhao; Dan Liu (Chemical Engineering Journal, 2023)

Phosphorus Limitation on Carbon Sequestration in China under RCP8.5 - Jing Peng; Li Dan; Xiba Tang (Advances in Atmospheric Sciences, 2023)

Dietary zearalenone alters gill epithelial morphology and subsequent risk of infection: Insights from a freshwater grass carp (Ctenopharyngodon idella) model - Hong-Yun Zhang; Ya-Li Wang; Wei-Dan Jiang; Pei Wu; Yang Liu; Lu Zhang; Hai-Feng Mi; Sheng-Yao Kuang; Ling Tang; Shu-wei Li; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2023)

Aflatoxin B1 exposure induced developmental toxicity and inhibited muscle development in zebrafish embryos and larvae - Xiang-Ning He; Pei Wu; Wei-Dan Jiang; Yang Liu; Sheng-Yao Kuang; Ling Tang; Hong-Mei Ren; Hua Li; Lin Feng; Xiao-Qiu Zhou (Science of The Total Environment, 2023)

Shewanella oneidensis MR-1 and oxalic acid mediated vanadium reduction and redistribution in vanadium-containing tailings - Chun-dan Gan; Qi-xuan Tang; Hao Wang; Jin-yan Yang; Aleksander Nikitin (Journal of Hazardous Materials, 2023)

Recent advances on the biological activities of purple sweet potato anthocyanins - Chao Tang; Jiaqi Han; Dan Chen; Shuai Zong; Jun Liu; Juan Kan; Chunlu Qian; Changhai Jin (Food Bioscience, 2023)

Adjustable Skeleton of Bilateral Lewis Base Passivator for CsPbI3 Perovskite Solar Cells with PCE over 20% and Superior Stability - Jin Huang; Hao Wang; Chunyang Chen; Yizhe Tang; Husheng Yang; Shengzhong Liu; Dan Zhang (Chemical Engineering Journal, 2023)

Coseismic landslides triggered by the 2022 Luding Ms6.8 earthquake, China - Lanxin Dai; Xuanmei Fan; Xin Wang; Chengyong Fang; Chengbin Zou; Xiaochuan Tang; Zhenlei Wei; Mingyao Xia; Dan Wang; Qiang Xu (Landslides, 2023)

ARPC5 is transcriptionally activated by KLF4, and promotes cell migration and invasion in prostate cancer via up-regulating ADAM17 - GenYi Qu; YuLong Zhang; HongTao Duan; Cheng Tang; Guang Yang; Dan Chen; Yong Xu (Apoptosis, 2023)

Rab37 Promotes Endothelial Differentiation and Accelerates ADSC-Mediated Diabetic Wound Healing through Regulating Secretion of Hsp90α and TIMP1 - Haili Huang; Ling Liang; Dan Sun; Jin Li; Wentao Wang; Lixia Zha; Jiaqi Yang; Kunyan Pan; Xianmou Fan; Chengzhang He; Xudong Tang; Peihua Zhang (Stem Cell Reviews and Reports, 2023)

Overexpression of ClWRKY48 from Cunninghamia lanceolata improves Arabidopsis phosphate uptake - Weiwei Tang; Jing Wang; Qiang Lv; Paul Promise Michael; Wenjun Ji; Min Chen; Yu Huang; Bo Zhou; Dan Peng (Planta, 2023)

Arbuscular mycorrhizal fungi increase the interspecific competition between two forage plant species and stabilize the soil microbial network during a drought event: Evidence from the field - Xionghui Liao; Jie Zhao; Lin Xu; Li Tang; Jiangnan Li; Wei Zhang; Jun Xiao; Dan Xiao; Peilei Hu; Yunpeng Nie; Dongsheng Zou; Kelin Wang (Applied Soil Ecology, 2023)

Future hotter summer greatly increases residential electricity consumption in Beijing: A study based on different house layouts and shared socioeconomic pathways - Qiyuan Hu; Jiayue Tang; Xiang Gao; Sijia Wang; Dan Zhang; Yuting Qin; Qihan Wang; Yi Zhou; Na Huang; Josep Penuelas; Jordi Sardans; Josep G. Canadell; et al. (Sustainable Cities and Society, 2023)

Insights into characterization of organophosphorus flame retardants transformation under thermal activation persulphate - Jia Liu; Liang Tang; Yaqing Liu; Dan Zhang; Xinshu Jiang (Process Safety and Environmental Protection, 2023)

Proteomic analysis reveals differential responsive mechanisms in Solanum nigrum exposed to low and high dose of cadmium - Ling-Yu Song; Xiang Liu; Lu-Dan Zhang; Wen-Jun Hu; Chao-Qun Xu; Jing Li; Shi-Wei Song; Ze-Jun Guo; Chen-Yang Sun; Han-Chen Tang; Ji-Cheng Wang; Xue-Yi Zhu; et al. (Journal of Hazardous Materials, 2023)

Precipitation-free aluminum-air batteries with high capacity and durable service life - Chaonan Lv; Yixin Li; Yuanxin Zhu; Yuxin Zhang; Jialin Kuang; Dan Huang; Yougen Tang; Haiyan Wang (Chemical Engineering Journal, 2023)

Aflatoxin B1 damaged structural barrier through Keap1a/Nrf2/ MLCK signaling pathways and immune barrier through NF-κB/ TOR signaling pathways in gill of grass carp (Ctenopharyngodon idella) - Xiang-Ning He; Zhen-Zhen Zeng; Lin Feng; Pei Wu; Wei-Dan Jiang; Yang Liu; Lu Zhang; Hai-Feng Mi; Sheng-Yao Kuang; Ling Tang; Xiao-Qiu Zhou (Aquatic Toxicology, 2023)

Lithologic control of soil C:N:P stoichiometry across a climatic gradient in southwest China - Mingming Sun; Rong Yang; Yixin Tang; Dan Xiao; Wei Zhang; Zhihong Xu; Zhihua Shi; Peilei Hu; Hanqing Wu; Kelin Wang (Journal of Soils and Sediments, 2023)

Production of MSTN knockout porcine cells using adenine base-editing-mediated exon skipping - Shuai-peng Yang; Xiang-xing Zhu; Zi-xiao Qu; Cai-yue Chen; Yao-bing Wu; Yue Wu; Zi-dan Luo; Xin-yi Wang; Chu-yu He; Jia-wen Fang; Ling-qi Wang; Guang-long Hong; et al. (In Vitro Cellular & Developmental Biology - Animal, 2023)

Numerical modeling and damage evolution research on the effect of joint geometrical parameters in nonpersistent jointed rock masses - Dan Huang; Wen Tang; Xiao-qing Li (Bulletin of Engineering Geology and the Environment, 2023)

Controllable assembly of three-dimensional porous graphene-Au dual aerogels and its application for high-efficient bioelectrocatalytic O2 reduction - Tuotuo Ma; Wenjing Mu; Yarui Tang; Wenhua Bi; Wei Liu; Dan Wen (Analytica Chimica Acta, 2023)

Identification and characterization of biocontrol agent Lysinibacillus boronitolerans P42 against Cerrena unicolor that causes root rot of arecanut palm - Xiang Ma; Yuxiao Gao; Hong Li; Dan Wang; Juanjuan Li; Xinwen Hu; Xi Huang; Min Lin; Yanqiong Tang; Zhu Liu (Archives of Microbiology, 2023)

Geochemical record of methane seepage in carbon cycling and possible correlation with climate events in the Qiongdongnan basin, South China Sea - Xiaopeng Dan; Shuang Liu; Xiuli Feng; Lin Lin; Rong Tang; Chao Yang; Jinya Xu; Zihan Wu (Marine and Petroleum Geology, 2023)

Single aromatics sulfonamide substituted dibenzothiazole squaraines for tumor NIR imaging and efficient photodynamic therapy at low drug dose - Jun-Hui Li; Pei-Dan You; Fei Lu; Jun-Tao Huang; Jia-Luo Fu; Hao-Yun Tang; Chun-Qiong Zhou (Journal of Photochemistry and Photobiology B: Biology, 2023)

Effects of perfluorooctanoic acid on Microcystis aeruginosa: Stress and self-adaptation mechanisms - Jinlu Hu; Dan Wang; Ning Zhang; Kaixin Tang; Yueqiu Bai; Yanqiu Tian; Yan Li; Xin Zhang (Journal of Hazardous Materials, 2023)

Hexavalent chromium (Cr(VI)) removal by ball-milled iron-sulfur @biochar based on P-recovery: Enhancement effect and synergy mechanism - Dan Ai; Yani Tang; Ruiming Yang; Yang Meng; Taiqing Wei; Bo Wang (Bioresource Technology, 2023)

Macromolecular structural characteristics and functional potential of tobacco stalk lignin from the phosphotungstic acid-assisted delignification process - Zhichang Liu; Xidong Peng; Yaowei Xu; Tianming Tang; Shuoguo Wei; Ben Liu; Dan Wang; Han-Min Wang; Jungang Jiang (Biomass and Bioenergy, 2023)

The evolution process of ecological vulnerability and its quantitative analysis of influencing factors: a case study of Longdong area - Lixia Ma; Hou Kang; Dan He; Jiawei Liu; Haojie Tang; Siqi Wu; Xuxiang Li (Environmental Science and Pollution Research, 2023)

Vitamin D serves as a modulator of immune organs in grass carp (Ctenopharyngodon idella) infected with Aeromonas hydrophila - Yao Zhang; Chao-Nan Li; Wei-Dan Jiang; Pei Wu; Yang Liu; Sheng-Yao Kuang; Ling Tang; Shu-Wei Li; Xiao-Wan Jin; Hong-Mei Ren; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2023)

Enhancements in flavor substances, mouthfeel characteristics and collagen synthesis in the muscle of sub-adult grass carp (Ctenopharyngodon Idella): Application of a dietary lysine nutrition strategy - Yan-Jie Tang; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Lu Zhang; Sheng-Yao Kuang; Hong-Mei Ren; Xiao-Wan Jin; Shu-Wei Li; Hai-Feng Mi; Xiao-Qiu Zhou (Aquaculture, 2023)

A spatial distribution – Principal component analysis (SD-PCA) model to assess pollution of heavy metals in soil - Jiawei Liu; Hou Kang; Wendong Tao; Hanyu Li; Dan He; Lixia Ma; Haojie Tang; Siqi Wu; Kexin Yang; Xuxiang Li (Science of The Total Environment, 2023)

Association of walkability and fine particulate matter with chronic obstructive pulmonary disease: A cohort study in China - Yonghao Wu; Peng Shen; Zongming Yang; Luhua Yu; Zhanghang Zhu; Tiezheng Li; Lisha Xu; Dan Luo; Xuecheng Yao; Xinhan Zhang; Lin Meng; Hongbo Lin; et al. (Science of The Total Environment, 2023)

Rapid screening of antioxidant from natural products by AAPH-Incubating HPLC-DAD-HR MS/MS method: A case study of Gardenia jasminoides fruit - Guo-Dong Zhuang; Wen-Ting Gu; Shu-Hong Xu; Dong-Min Cao; Si-Min Deng; Yong-Sheng Chen; Shu-Mei Wang; Dan Tang (Food Chemistry, 2023)

Construction of PP membranes with robust interfacial stability by ALD and fluorinated grafting for high salt solution distillation - Lei Zhang; Dan He; Jia Li; Yanting Li; Yiming Xiao; Jun Xiang; Wei Du; Na Tang (Desalination, 2023)

Vertical distribution of PbI2 nanosheets for robust air-processed perovskite solar cells - Zhenkun Zhu; Jitao Shang; Guanqi Tang; Zhen Wang; Xiaxia Cui; Junjun Jin; Yuan Zhou; Xiang Zhang; Dan Zhang; Xiaowei Liu; Qidong Tai (Chemical Engineering Journal, 2023)

Nutrient removal and lipid production by the co-cultivation of Chlorella vulgaris and Scenedesmus dimorphus in landfill leachate diluted with recycled harvesting water - Chunming Tang; Xinxin Gao; Dan Hu; Dian Dai; Mingxiang Qv; Dongyang Liu; Liandong Zhu (Bioresource Technology, 2023)

Somatostatin-Positive Neurons in the Rostral Zona Incerta Modulate Innate Fear-Induced Defensive Response in Mice - Shan Lin; Meng-Yue Zhu; Meng-Yu Tang; Mi Wang; Xiao-Dan Yu; Yi Zhu; Shi-Ze Xie; Dan Yang; Jiadong Chen; Xiao-Ming Li (Neuroscience Bulletin, 2023)
Defensive behaviors induced by innate fear or Pavlovian fear conditioning are crucial for animals to avoid threats and ensure survival. The zona incerta (ZI) has been demonstrated to play important roles in fear learning and fear memory, as well as modulating auditory-induced innate defensive behavior. However, whether the neuronal subtypes in the ZI and specific circuits can mediate the innate fear response is largely unknown. Here, we found that somatostatin (SST)-positive neurons in the rostral ZI of mice were activated by a visual innate fear stimulus. Optogenetic inhibition of SST-positive neurons in the rostral ZI resulted in reduced flight responses to an overhead looming stimulus. Optogenetic activation of SST-positive neurons in the rostral ZI induced fear-like defensive behavior including increased immobility and bradycardia. In addition, we demonstrated that manipulation of the GABAergic projections from SST-positive neurons in the rostral ZI to the downstream nucleus reuniens (Re) mediated fear-like defensive behavior. Retrograde trans-synaptic tracing also revealed looming stimulus-activated neurons in the superior colliculus (SC) that projected to the Re-projecting SST-positive neurons in the rostral ZI (SC-ZIr SST -Re pathway). Together, our study elucidates the function of SST-positive neurons in the rostral ZI and the SC-ZIr SST -Re tri-synaptic circuit in mediating the innate fear response.

Vitamin D deficiency leads to the abnormal activation of the complement system - Huan Li; Xiaomin Xie; Guirong Bai; Dan Qiang; Li Zhang; Huili Liu; Yanting He; Yanpan Tang; Ling Li (Immunologic Research, 2023)
Vitamin D deficiency can damage the human immune system, and the complement system is a key component of the immune system. This study aimed to elucidate the mechanism by which vitamin D affects the immune system by analyzing the changes in the protein expression of the complement system under different vitamin D levels. We selected 40 participants and divided them into three groups according to their serum levels of 25-hydroxyvitamin D (25(OH)VD): group A, 25(OH)VD ≥ 40 ng/mL; group B, 30 ng/mL ≤ 25(OH)VD < 40 ng/mL; and group C, 25(OH)VD < 30 ng/mL. Serum samples were subjected to biochemical analysis, followed by proteomic analysis using high-throughput untargeted proteomic techniques. Vitamin D deficiency increased the levels of fasting blood sugar, fasting serum insulin, and homeostasis model assessment (HOMA) of insulin resistance and decreased the secretion of HOMA of β-cell function, which led to insulin resistance and glucose metabolism disorder. Moreover, vitamin D deficiency resulted in the abnormal expression of 56 differential proteins, among which the expression levels of complement factor B, complement component C9, inducible co-stimulator ligand, and peptidase inhibitor 16 significantly changed with the decrease in vitamin D content. Functional enrichment analysis of these differential proteins showed that they were mainly concentrated in functions and pathways related to insulin secretion and inflammation. In conclusion, vitamin D deficiency not only contributes to insulin resistance and glucose metabolism disorder but also causes abnormal protein expression, resulting in the abnormal activation of the complement system. This study provides a novel theoretical basis for further studies on the relationship between vitamin D and the immune system.

Anaerobic methane oxidation coupled to arsenate reduction in paddy soils: Insights from laboratory and field studies - Yujie Zhou; Ting Guo; Williamson Gustave; Zhaofeng Yuan; Jingxuan Yang; Dan Chen; Xianjin Tang (Chemosphere, 2023)

Impaired intestinal physical barrier of on-growing grass carp by deficient iron under Aeromonas hydrophila infection - Yan-Lin Guo; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Sheng-Yao Kuang; Shu-wei Li; Ling Tang; Lu Zhang; Haifeng Mi; Xiao-Qiu Zhou (Aquaculture, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Experimental study on non-isothermal oxidative characteristics and kinetics of methane in accelerating rate calorimetry tests - Xiaodong Tang; Wanfen Pu; Dan Wang; Shanshan Qu; Yiming Rui; Xuepei Zhao; Renbao Liu (Fuel, 2023)

Dietary cinnamaldehyde improves muscle protein content by promoting muscle fiber growth via PTP1B/IGF1/PI3K/AKTs-TOR/FOXO3a signaling pathway in grass carp (Ctenopharyngodon idella) - Yang Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Yan Peng; Sheng-Yao Kuang; Ling Tang; Shu-Wei Li; Lin Feng; Xiao-Qiu Zhou (Food Chemistry, 2023)

Breast adipose metabolites mediates the association of tetrabromobisphenol a with breast cancer: A case-control study in Chinese population - Ai Zhang; Rui Wang; Qianfeng Liu; Zhengjun Yang; Xiaohui Lin; Jing Pang; Xiaoyu Li; Dan Wang; Jiayu He; Jianping Li; Mingyue Zhang; Yue Yu; et al. (Environmental Pollution, 2023)

Photo-induced reduction of vanadium in vanadium-containing iron/manganese oxide agglomerates by oxalic acid - Qi-xuan Tang; Chun-dan Gan; Jin-yan Yang (Environmental Pollution, 2023)

Nonoxidative propane dehydrogenation by isolated Co2+ in BEA zeolite: Dealumination-determined key steps of propane C H activation and propylene desorption - Sheng Wei; Hua Dai; Jiangping Long; Hongqiao Lin; Junkun Gu; Xupeng Zong; Dan Yang; Yu Tang; Yanhui Yang; Yihu Dai (Chemical Engineering Journal, 2023)

Perfluorooctanoic acid promotes pancreatic β cell dysfunction and apoptosis through ER stress and the ATF4/CHOP/TRIB3 pathway - Xiaowei He; Dan Wu; Yanan Xu; Yaqin Zhang; Yue Sun; Xiaoai Chang; Yunxia Zhu; Wei Tang (Environmental Science and Pollution Research, 2022)

Transcriptome Reveals the Mechanism of Immunity in the Low Salinity Stress of the Chinese Shrimp (Fenneropenaeus chinensis) - Dan Tang; Ya Wu; Suping Huang; Lv Wu; Yaqi Luo; Zhengfei Wang (Thalassas: An International Journal of Marine Sciences, 2022)

Drivers of foliar 15 N trends in southern China over the last century - Songbo Tang; Jianfeng Liu; Frank S. Gilliam; Peter Hietz; Zhiheng Wang; Xiankai Lu; Feiyan Zeng; Dazhi Wen; Enqing Hou; Yuan Lai; Yunting Fang; Ying Tu; et al. (Global Change Biology, 2022)
Foliar stable nitrogen (N) isotopes (δ 15 N) generally reflect N availability to plants and have been used to infer about changes thereof. However, previous studies of temporal trends in foliar δ 15 N have ignored the influence of confounding factors, leading to uncertainties on its indication to N availability. In this study, we measured foliar δ 15 N of 1811 herbarium specimens from 12 plant species collected in southern China forests from 1920 to 2010. We explored how changes in atmospheric CO 2 , N deposition and global warming have affected foliar δ 15 N and N concentrations ([N]) and identified whether N availability decreased in southern China. Across all species, foliar δ 15 N significantly decreased by 0.82‰ over the study period. However, foliar [N] did not decrease significantly, implying N homeostasis in forest trees in the region. The spatiotemporal patterns of foliar δ 15 N were explained by mean annual temperature (MAT), atmospheric CO 2 (), atmospheric N deposition, and foliar [N]. The spatiotemporal trends of foliar [N] were explained by MAT, temperature seasonality, , and N deposition. N deposition within the rates from 5.3 to 12.6 kg N ha −1 year −1 substantially contributed to the temporal decline in foliar δ 15 N. The decline in foliar δ 15 N was not accompanied by changes in foliar [N] and therefore does not necessarily reflect a decline in N availability. This is important to understand changes in N availability, which is essential to validate and parameterize biogeochemical cycles of N.

β-Cyclodextrin-Grafted Chitosan Enhances Intestinal Drug Absorption and Its Preliminary Mechanism Exploration - Linghui Zou; Zhongbin Zhang; Jinqing Chen; Xu Yang; Yuyang Li; Jing Tang; Xiaolu Du; Ling Tang; Dan Liang; Xiaoyong Zhu; Jianfang Feng; Wenya Ding (AAPS PharmSciTech, 2022)

Importing or self-dependent: energy transition in Beijing towards carbon neutrality and the air pollution reduction co-benefits - Jun Liu; Wenji Zhou; Jing Yang; Hongtao Ren; Behnam Zakeri; Dan Tong; Ying Guo; Zbigniew Klimont; Tong Zhu; Xiaolong Tang; Honghong Yi (Climatic Change, 2022)

The effects of ammonia stress exposure on protein degradation, immune response, degradation of nitrogen-containing compounds and energy metabolism of Chinese mitten crab - Dan Tang; Ya Wu; Lv Wu; Yuze Bai; Ying Zhou; Zhengfei Wang (Molecular Biology Reports, 2022)

An inactivating mutation in the vacuolar arginine exporter gene Vae results in culture degeneration in the fungus Metarhizium robertsii - Hui Song; Yuting Bao; Mingxiang Zhang; Shuxing Liu; Chaonan Yu; Jin Dai; Congcong Wu; Dan Tang; Weiguo Fang (Environmental Microbiology, 2022)
Summary Culture degeneration usually results in great commercial losses in the economically important filamentous fungi, but the genetic causes of the degeneration remain elusive. In the fungus Metarhizium robertsii , we found that deletion of the vacuolar arginine exporter gene Vae caused culture degeneration. Compared to the WT strain, the mutant showed increased apoptosis, reactive oxygen species (ROS) level and mitochondrial membrane potential collapse, reduced conidial yield and abnormal lipid droplet formation. The extent of the degeneration in the mutant gradually increased over the successive subculturing, which eventually became irreversible; compared to the third subculture of the mutant, the seventh subculture showed a lower conidial yield and pathogenicity to insects, stronger apoptosis, higher ROS level and a smaller number of conidial lipid droplets. Incorporation of the genomic clone of Vae could not restore the WT phenotypes in the seventh subculture, but could in the third one. Loss‐of‐function in Vae resulted in vacuolar arginine accumulation and reduction in the cytosolic arginine. This downregulated the expression of the regulator CAG9 of G protein signalling pathway, which accounted for most of the phenotypic changes associated with the degeneration of the mutant. We identified a deleterious mutation that causes culture degeneration in a filamentous fugus.

A Deep Mesencephalic Nucleus Circuit Regulates Licking Behavior - Di Zheng; Jia-Yu Fu; Meng-Yu Tang; Xiao-Dan Yu; Yi Zhu; Chen-Jie Shen; Chun-Yue Li; Shi-Ze Xie; Shan Lin; Minmin Luo; Xiao-Ming Li (Neuroscience Bulletin, 2022)

Comparison of genetic characteristics between captive and wild giant pandas based on 13 mitochondrial coding genes - Yixin Zhu; Tao Deng; Maiju Qiao; Dan Tang; Xiaoyu Huang; Wenwen Deng; Huan Liu; Rengui Li; Tianming Lan (Molecular Biology Reports, 2022)

Potential Application of Biosurfactant-Producing Bacteria for Bioremediation of Oil Polluted Marine Intertidal Sediments - Ping Guo; Wei-Wei Xu; Dan-Na Wei; Man-Xia Zhang; Jin Zhang; Shi Tang; Bin-Xia Cao; Jian-Guo Lin; Wei Li (Journal of Marine Science and Engineering, 2022)
The removal of oil contaminants in marine intertidal sediments under cold climate is an urgent issue. Although the bioavailability of petroleum hydrocarbons decreases at low temperatures, biosurfactants can promote oil biodegradation. In this study, characteristics of biosurfactants produced by cold-adapted oil-degrading bacteria Planococcus sp. XW-1 were studied. Adding the XW-1 biosurfactant could effectively facilitate the solubility of phenanthrene, pyrene, diesel oil, and crude oil. The solubilization was limited by the number of rings and the molecular weight (WSRphenanthrene = 0.0234; WSRpyrene = 0.0165; WSRdiesel oil = 0.0027; WSRcrude oil = 0.0015). Additional biosurfactants significantly washed out crude oil adsorbed to the sand (reduction from 17.1%, 22.7% to 87.9% and 94.28% in 24 h). With the increase in particle size, the removal efficiency increased from 87.9% to 94.28%. After the addition of biosurfactant, the effect of degradation increased by 20% in 20 days. The results suggest that the biosurfactant-producing bacteria Planococcus sp. XW-1 is a promising candidate used in the in situ bioremediation of petroleum-contaminated intertidal sediment.

Links between continental subduction and generation of Cenozoic potassic–ultrapotassic rocks revealed by olivine oxygen isotopes: A case study from NW Tibet - Gong-Jian Tang; Derek A. Wyman; Qiang Wang; Lin Ma; Wei Dan; Ya-Nan Yang; Xi-Jun Liu; Hong-Yi Chen (Contributions to Mineralogy and Petrology, 2022)

Identification of Genes Involved in Digestion from Transcriptome of Parasesarma pictum and Parasesarma affine Hepatopancreas - Zhengfei Wang; Dan Tang; Chenchen Shen; Lv Wu (Thalassas: An International Journal of Marine Sciences, 2022)

The effects of ammonia exposure on immune response, oxidative stress, and apoptosis in Procambarus clarkii - Yaqi Luo; Chenchen Shen; Dan Tang; Yuze Bai; Lv Wu; Yiping Zhang; Ya Wu; Zhengfei Wang (Aquaculture International, 2022)

Sesquiterpene lactones isolated from Carpesium abrotanoides L. by LC–MS combined with HSCCC inhibit liver cancer through suppression of the JAK2/STAT3 signaling pathway - Bingbing Shen; Yupei Yang; Dan Wan; Huanghe Yu; Yuan Cai; Xionglong Wang; Daifeng Tang; Chunyu Tang; Shuihan Zhang (Medicinal Chemistry Research, 2022)

Kinematics, strain pattern, and temperature environment of the Yeba shear zone and multistage structural evolution of the Yeba Group - Yipeng Feng; Yu Tang; Genhou Wang; Yang Lu; Dian Li; Ci Dan; Yuanku Meng; Peilie Zhang; Jixin Hu; Zhengzhe Fan (International Journal of Earth Sciences, 2022)

Effects of magnetically treated Sedum alfredii seeds on the dissolved organic matter characteristics of Cd-contaminated soil during phytoextraction - Youjun Tang; Shuaizhi Ji; Dan Chen; Jiawei Wang; Min Cao; Jie Luo (Environmental Science and Pollution Research, 2022)

PHD2 attenuates high-glucose-induced blood retinal barrier breakdown in human retinal microvascular endothelial cells by regulating the Hif-1α/VEGF pathway - Jia Li; Xi Lu; Liqing Wei; Dan Ye; Jianqiang Lin; Xiaoyu Tang; Kaixuan Cui; Shanshan Yu; Yue Xu; Xiaoling Liang (Inflammation Research, 2022)

Retraction Note to: Revisiting the male genetic landscape of China: a multi-center study of almost 38,000 Y-STR haplotypes - Michael Nothnagel; Guangyao Fan; Fei Guo; Yongfeng He; Yiping Hou; Shengping Hu; Jiang Huang; Xianhua Jiang; Wook Kim; Kicheol Kim; Chengtao Li; Hui Li; et al. (Human Genetics, 2022)

Human telomerase reverse transcriptase (hTERT) synergistic with Sp1 upregulate Gli1 expression and increase gastric cancer invasion and metastasis - Lingyi Wu; Sumin Wang; Bo Tang; Li Tang; Yuanyuan Lei; Yaojiang Liu; Min Yang; Guodong Yang; Dan Zhang; En Liu (Journal of Molecular Histology, 2021)

Retraction Note: EDAR, LYPLAL1, PRDM16, PAX3, DKK1, TNFSF12, CACNA2D3, and SUPT3H gene variants influence facial morphology in a Eurasian population - Yi Li; Wenting Zhao; Dan Li; Xianming Tao; Ziyi Xiong; Jing Liu; Wei Zhang; Anquan Ji; Kun Tang; Fan Liu; Caixia Li (Human Genetics, 2021)

Expression and functional analysis of cytoplasmic dynein during spermatogenesis in Portunus trituberculatus - Chao-Guang Wei; Dan-Li Mu; Dao-Jun Tang; Jun-Quan Zhu; Cong-Cong Hou (Cell and Tissue Research, 2021)

Soil lead distribution characteristics and source identification in Hanyuan, upstream of Yangtze River, China - Xiaowen Liu; Dan Zhou; Xue Tang; Ying Li; Ying Yang; Yi Huang (Arabian Journal of Geosciences, 2021)

Two new pregnane steroidal glycosides from Cynanchum taihangense - Yu-Bo Wang; Shan-Shan Su; Ming-Xu Tang; Dan Zhao; Gang Chen; Shao-Fei Chen; Hai-Feng Wang; Yue-Hu Pei (Natural Product Research, 2021)

Maribacter hydrothermalis sp. nov., Isolated from Shallow-Sea Hydrothermal Systems Off Kueishantao Island - Huaying Lin; Dan Lin; Mu Zhang; Jianing Ye; Jia Sun; Kai Tang (Current Microbiology, 2021)

Assessment of long-term functional maintenance of primary human hepatocytes to predict drug-induced hepatoxicity in vitro - Yi Chen; Dan Tang; Hongping Wu; Yuling Wu; Tianjie Yuan; Hongdan Zhang; Yingfu Jiao; Weifeng Yu; Hexin Yan (Archives of Toxicology, 2021)

Vertical Evolution of Boundary Layer Volatile Organic Compounds in Summer over the North China Plain and the Differences with Winter - Shuang Wu; Guiqian Tang; Yinghong Wang; Rong Mai; Dan Yao; Yanyu Kang; Qinglu Wang; Yuesi Wang (Advances in Atmospheric Sciences, 2021)

A theoretical relationship between probabilistic relative operating characteristic skill and deterministic correlation skill in dynamical seasonal climate prediction - Dejian Yang; Youmin Tang; Xiu-Qun Yang; Dan Ye; Ting Liu; Tao Feng; Xiaoqin Yan; Xuguang Sun; Yaocun Zhang (Climate Dynamics, 2021)
Understanding the relationship between probabilistic and deterministic prediction skills is of important significance for the study of seasonal forecasting and verification. Based on the Brier skill score methodology, we have previously found a theoretical relationship between the probabilistic resolution skill and the deterministic correlation (i.e., anomaly correlation; AC) skill and a lack of necessary or consistent relationship between the probabilistic reliability skill and the deterministic skill in dynamical seasonal prediction. Here, we further theoretically investigate the relationship between the probabilistic relative operating characteristic (ROC) skill and the deterministic skill. The ROC measures the discrimination attribute of probabilistic forecast quality, another important attribute besides the resolution and reliability. With some simplified assumptions, we first derive theoretical expressions for the hit and false-alarm rates that are basic ingredients for the ROC curve, then demonstrate a sole dependence of the ROC curve on the AC, and finally analytically derive a relationship between the related ROC score and the AC. Such a theoretically derived ROC-AC relationship is further examined using dynamical models’ ensemble seasonal hindcasts, which is well verified. The finding here along with our previous findings implies that the discrimination and resolution attributes of probabilistic seasonal forecast skill are intrinsically equivalent to the corresponding deterministic skill, while the reliability appears to be the fundamental attribute of the probabilistic skill that differs from the deterministic skill, which constitutes an understanding of the fundamental similarities and difference between the two types of seasonal forecasting skills and predictability and can offer important implications for the study of seasonal forecasting and verification.

PKM2 promotes cell metastasis and inhibits autophagy via the JAK/STAT3 pathway in hepatocellular carcinoma - Zhi Yu; Dan Wang; Yingying Tang (Molecular and Cellular Biochemistry, 2021)

Toxic effects of metal copper stress on immunity, metabolism and pathologic changes in Chinese mitten crab (Eriocheir japonica sinensis) - Dan Tang; Ruobing Liu; Xueling Shi; Chenchen Shen; Yuze Bai; Boping Tang; Zhengfei Wang (Ecotoxicology, 2021)

Identification of putative ingestion-related olfactory receptor genes in the Chinese mitten crab (Eriocheir japonica sinensis) - Chenchen Shen; Dan Tang; Yiping Zhang; Lv Wu; Yaqi Luo; Boping Tang; Zhengfei Wang (Genes & Genomics, 2021)

Clinical characteristics of 100 cases of coronavirus disease 2019 in Dongguan, China - Hai-en Pan; Xiao-yi Shi; Zhi-dan Zheng; Qin Tang; Qing-Yang Zhong; Huan-huan Cao; Song Chen; Hai-peng Zhu (Infectious Diseases, 2021)

The prevalence and risks of major comorbidities among inpatients with pulmonary tuberculosis in China from a gender and age perspective: a large-scale multicenter observational study - Wanli Kang; Jian Du; Song Yang; Jiajia Yu; Hongyan Chen; Jianxiong Liu; Jinshan Ma; Mingwu Li; Jingmin Qin; Wei Shu; Peilan Zong; Yi Zhang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Influence of Dose on Neutrophil-Mediated Delivery of Nanoparticles for Tumor-Targeting Therapy Strategies - Min Liu; Cong Li; NaYan; Dan Zhao; Hongxia Zhang; Jie Li; Xueying Tang; Xinrong Liu; Yihui Deng; Yanzhi Song (AAPS PharmSciTech, 2021)

Comparative transcriptome analysis of the gills of Procambarus clarkii provide novel insights into the response mechanism of ammonia stress tolerance - Chenchen Shen; Dan Tang; Yuze Bai; Yaqi Luo; Lv Wu; Yiping Zhang; Zhengfei Wang (Molecular Biology Reports, 2021)

Suitability of Nansha Mangrove Wetland for High Nitrogen Shrimp Pond Wastewater Treatment - Dan Wang; Xianming Xie; Weiyi Tang; Hongzhong Pan; Jie Luo (Bulletin of Environmental Contamination and Toxicology, 2021)

Method for feature analysis and intelligent recognition of infrasound signals of soil landslides - Dunlong Liu; Dan Tang; Shaojie Zhang; Xiaopeng Leng; Kaiheng Hu; Lei He (Bulletin of Engineering Geology and the Environment, 2021)

The missing pieces for better future predictions in subarctic ecosystems: A Torneträsk case study - Didac Pascual; Jonas Åkerman; Marina Becher; Terry V. Callaghan; Torben R. Christensen; Ellen Dorrepaal; Urban Emanuelsson; Reiner Giesler; Dan Hammarlund; Edward Hanna; Annika Hofgaard; Hongxiao Jin; et al. (Ambio, 2021)
Arctic and subarctic ecosystems are experiencing substantial changes in hydrology, vegetation, permafrost conditions, and carbon cycling, in response to climatic change and other anthropogenic drivers, and these changes are likely to continue over this century. The total magnitude of these changes results from multiple interactions among these drivers. Field measurements can address the overall responses to different changing drivers, but are less capable of quantifying the interactions among them. Currently, a comprehensive assessment of the drivers of ecosystem changes, and the magnitude of their direct and indirect impacts on subarctic ecosystems, is missing. The Torneträsk area, in the Swedish subarctic, has an unrivalled history of environmental observation over 100 years, and is one of the most studied sites in the Arctic. In this study, we summarize and rank the drivers of ecosystem change in the Torneträsk area, and propose research priorities identified, by expert assessment, to improve predictions of ecosystem changes. The research priorities identified include understanding impacts on ecosystems brought on by altered frequency and intensity of winter warming events, evapotranspiration rates, rainfall, duration of snow cover and lake-ice, changed soil moisture, and droughts. This case study can help us understand the ongoing ecosystem changes occurring in the Torneträsk area, and contribute to improve predictions of future ecosystem changes at a larger scale. This understanding will provide the basis for the future mitigation and adaptation plans needed in a changing climate.

The secondary metabolite regulator, BbSmr1 , is a central regulator of conidiation via the BrlA‐AbaA‐WetA pathway in Beauveria bassiana - Jin‐Feng Chen; Yu Liu; Gui‐Rong Tang; Dan Jin; Xi Chen; Yan Pei; Yan‐Hua Fan (Environmental Microbiology, 2021)
Summary The filamentous fungus Beauveria bassiana , an insect fungal pathogen, is widely used for pest biocontrol. Aerial conidia are infectious propagules, and their yield and viability greatly affect the field application of this fungus; however, little is known about the molecular regulatory mechanism of the triggered conidiation. In the present study, we find that the secondary metabolite regulator BbSmr1 is involved in the regulation of asexual conidiation development and stress response in B. bassiana . A deficiency in Bbsmr1 results in a prominent fluffy‐like phenotype on solid medium, decreased conidial yield, accelerated conidial germination, as well as increased tolerance to H 2 O 2 stress and cell wall inhibitors. The deletion of Bbsmr1 also leads to thickened conidial cell walls and changed cell epitopes. Overexpressing either BbbrlA or BbabaA in the ∆Bbsmr1 strain can rescue the phenotypes of conidial development and stress response. BbSmr1 activates BbbrlA transcription by directly binding to the A4GA3 sequence of the BbbrlA promoter. BbBrlA in turn binds to the promoter of Bbsmr1 and negatively regulates the expression of Bbsmr1 . These results indicate that BbSmr1 positively regulates conidial development in B. bassiana by activating the central development pathway BrlA‐AbaA‐WetA and provides insights into the developmental regulatory mechanism of entomopathogenic fungi.

Critical roles of macrophages in pressure overload-induced cardiac remodeling - Dan Yang; Han-Qing Liu; Fang-Yuan Liu; Nan Tang; Zhen Guo; Shu-Qing Ma; Peng An; Ming-Yu Wang; Hai-Ming Wu; Zheng Yang; Di Fan; Qi-Zhu Tang (Journal of Molecular Medicine, 2021)

Effects of Porphyromonas gingivalis and Its Underlying Mechanisms on Alzheimer-Like Tau Hyperphosphorylation in Sprague-Dawley Rats - Zhiqun Tang; Dan Liang; Miaoying Cheng; Xinyi Su; Runhe Liu; Yiding Zhang; Hongkun Wu (Journal of Molecular Neuroscience, 2021)

Adakitic rocks at convergent plate boundaries: Compositions and petrogenesis - Qiang Wang; Lulu Hao; Xiuzheng Zhang; Jinsheng Zhou; Jun Wang; Qiwei Li; Lin Ma; Long Zhang; Yue Qi; Gongjian Tang; Wei Dan; Jingjing Fan (Science China Earth Sciences, 2020)

Heme oxygenase 1 plays a crucial role in swamp eel response to oxidative stress induced by cadmium exposure or Aeromonas hydrophila infection - Yuwei Zang; Shuting Zheng; Fang Tang; Long Yang; Xiping Wei; Dan Kong; Wenxiu Sun; Wei Li (Fish Physiology and Biochemistry, 2020)

Using full-length metabarcoding and DNA barcoding to infer community assembly for speciose taxonomic groups: a case study - Mengdi Hao; Qian Jin; Guanliang Meng; Caiqing Yang; Shenzhou Yang; Zhiyong Shi; Min Tang; Shanlin Liu; Yinan Li; Jing Li; Dan Zhang; Xu Su; et al. (Evolutionary Ecology, 2020)

The spillover effects of China’s regional environmental markets to local listed firms: a risk Granger causality approach - Shujin Zhu; Yiding Tang; Xingzhi Qiao; Cheng Peng; Dan Li (Environmental Science and Pollution Research, 2020)

Spororrminone A and 2- epi -spororrminone A, two new chromones from an endolichenic fungus Sporormiella irregularis - Mei-Juan Huang; Yan-Jun Li; Jia Tang; Guo-Dong Chen; Dan Hu; Wei Xu; Liang-Dong Guo; Xin-Sheng Yao; Hao Gao (Natural Product Research, 2020)

Microplastics in the soil environment: Occurrence, risks, interactions and fate – A review - Baile Xu; Fei Liu; Zachary Cryder; Dan Huang; Zhijiang Lu; Yan He; Haizhen Wang; Zhenmei Lu; Philip C. Brookes; Caixian Tang; Jay Gan; Jianming Xu (Critical Reviews in Environmental Science and Technology, 2020)

Whole-Brain Map of Long-Range Monosynaptic Inputs to Different Cell Types in the Amygdala of the Mouse - Jia-Yu Fu; Xiao-Dan Yu; Yi Zhu; Shi-Ze Xie; Meng-Yu Tang; Bin Yu; Xiao-Ming Li (Neuroscience Bulletin, 2020)
The amygdala, which is involved in various behaviors and emotions, is reported to connect with the whole brain. However, the long-range inputs of distinct cell types have not yet been defined. Here, we used a retrograde trans-synaptic rabies virus to generate a whole-brain map of inputs to the main cell types in the mouse amygdala. We identified 37 individual regions that projected to neurons expressing vesicular glutamate transporter 2, 78 regions to parvalbumin-expressing neurons, 104 regions to neurons expressing protein kinase C-δ, and 89 regions to somatostatin-expressing neurons. The amygdala received massive projections from the isocortex and striatum. Several nuclei, such as the caudate-putamen and the CA1 field of the hippocampus, exhibited input preferences to different cell types in the amygdala. Notably, we identified several novel input areas, including the substantia innominata and zona incerta. These findings provide anatomical evidence to help understand the precise connections and diverse functions of the amygdala.

Two new compounds from the marine sponge derived fungus Penicillium chrysogenum - Xiao Han; Pinglin Li; Xiangchao Luo; Dan Qiao; Xuli Tang; Guoqiang Li (Natural Product Research, 2020)

Transcriptome Analysis Reveals Potential Genes Involved in Digestive Enzyme Function in a Mudflat Crab Helice tientsinensis - Zhengfei Wang; Dan Tang; Huayun Guo; Xueling Shi (Thalassas: An International Journal of Marine Sciences, 2020)

Ridge subduction, magmatism, and metallogenesis - Qiang Wang; Gongjian Tang; Lulu Hao; Derek Wyman; Lin Ma; Wei Dan; Xiuzheng Zhang; Jinheng Liu; Tongyu Huang; Chuanbing Xu (Science China Earth Sciences, 2020)

Neo-debromoaplysiatoxin C, with new structural rearrangement, derived from debromoaplysiatoxin - Yang-Hua Tang; Ting-Ting Liang; Ting-Ting Fan; Lawrence Jordan Keen; Xiao-Dan Zhang; Lin Xu; Qi Zhao; Rong Zeng; Bing-Nan Han (Natural Product Research, 2020)

Cinnamaldehyde improves the growth performance and digestion and absorption capacity in grass carp (Ctenopharyngodon idella) - Yang Zhou; Wei-Dan Jiang; Jin-Xiu Zhang; Lin Feng; Pei Wu; Yang Liu; Jun Jiang; Sheng-Yao Kuang; Ling Tang; Yan Peng; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2020)

The dynamic process of dietary soybean β-conglycinin in digestion, absorption, and metabolism among different intestinal segments in grass carp (Ctenopharyngodon idella) - Xu-Dong Duan; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Jun Jiang; Bei-Ping Tan; Qi-Hui Yang; Sheng-Yao Kuang; Ling Tang; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2020)

Efficacy of amisulpride on postoperative nausea and vomiting: a systematic review and meta-analysis - Lu-Feng Zhang; Chao-Fan Zhang; Wen-Xin Tang; Long He; Yang Liu; Dan-Dan Tian; Yan-Qiu Ai (European Journal of Clinical Pharmacology, 2020)

Regional assemblages shaped by historical and contemporary factors: Evidence from a species‐rich insect group - Mengdi Hao; Qian Jin; Guanliang Meng; Caiqing Yang; Shenzhou Yang; Zhiyong Shi; Min Tang; Shanlin Liu; Yinan Li; Dan Zhang; Xu Su; Chungkun Shih; et al. (Molecular Ecology, 2020)
Understanding diversity patterns requires accounting for the roles of both historical and contemporary factors in the assembly of communities. Here, we compared diversity patterns of two moth assemblages sampled from Taihang and Yanshan mountains in Northern China and performed ancestral range reconstructions using the Multi‐State Speciation and Extinction model, to track the origins of these patterns. Further, we estimated diversification rates of the two moth assemblages and explored the effects of contemporary ecological factors. From 7,788 specimens we identified 835 species belonging to 23 families, using both DNA barcode analysis and morphology. Moths in Yanshan mountains showed higher species diversity than in Taihang mountains. Ancestral range analysis indicated Yanshan as the origin, with significant historical dispersals from Yanshan to Taihang. Asymmetrical diversification, population expansion, along with frequent and considerable gene flow were detected between communities. Moreover, dispersal limitation or the joint effect of environment filtering and dispersal limitation were inferred as main driving forces shaping current diversity patterns. In summary, we demonstrate that a multiscale (community, population and species level) analysis incorporating both historical and contemporary factors can be useful in delineating factors contributing to community assembly and patterning in diversity.

Translocator protein 18 kDa: a potential therapeutic biomarker for post traumatic stress disorder - Zhi-Kun Qiu; Xu Liu; Yong Chen; Rong-Jia Wu; Shi-Feng Guan; Yun-yun Pan; Qian-Bo Wang; Dan Tang; Tao Zhu; Ji-Sheng Chen (Metabolic Brain Disease, 2020)

Identification, association, and expression analysis of ZmNAC134 gene response to phosphorus deficiency tolerance traits in maize at seedling stage - Javed Hussain Sahito; Fei Zheng; Haitao Tang; Xuan He; Bowen Luo; Xiao Zhang; Peng Ma; Xin Ding; Dan Liu; Ling Wu; Shibin Gao (Euphytica, 2020)

Detection of serum IgM and IgG for COVID-19 diagnosis - Ling Zhong; Junlan Chuan; Bo Gong; Ping Shuai; Yu Zhou; Yi Zhang; Zhilin Jiang; Dingding Zhang; Xiaoqi Liu; Shi Ma; Yi Huang; He Lin; et al. (Science China Life Sciences, 2020)

Evolution of digestive enzyme genes associated with dietary diversity of crabs - Zhengfei Wang; Dan Tang; Huayun Guo; Chenchen Shen; Lv Wu; Yaqi Luo (Genetica, 2020)

Environmentally persistent free radicals in PM2.5: a review - Mengxia Xu; Tao Wu; Yu-Ting Tang; Tong Chen; Lavrent Khachatryan; Poornima Ramesh Iyer; Dengting Guo; Anran Chen; Miao Lyu; Jinhu Li; Jiaqi Liu; Dan Li; et al. (Waste Disposal & Sustainable Energy, 2019)

Comparative transcriptome analysis reveals the expression and characterization of digestive enzyme genes in the hepatopancreas of the Chinese mitten crab - Huayun Guo; Dan Tang; Xueling Shi; Qiong Wu; Ruobing Liu; Boping Tang; Zhengfei Wang (Fisheries Science, 2019)

Soybean glycinin decreased growth performance, impaired intestinal health, and amino acid absorption capacity of juvenile grass carp (Ctenopharyngodon idella) - Ya-Lin Zhang; Xu-Dong Duan; Wei-Dan Jiang; Lin Feng; Pei Wu; Yang Liu; Jun Jiang; Sheng-Yao Kuang; Ling Tang; Wu-Neng Tang; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2019)

Joint toxicity of six common heavy metals to Chlorella pyrenoidosa - Ling-Yun Mo; Dan-Na Zhao; Meng Qin; Li-Tang Qin; Hong-Hu Zeng; Yan-Peng Liang (Environmental Science and Pollution Research, 2019)

The antifungal activity of essential oil from Melaleuca leucadendra (L.) L. grown in China and its synergistic effects with conventional antibiotics against Candida - Jing Zhang; Huihui Wu; Dan Jiang; Yongan Yang; Wenjian Tang; Kehan Xu (Natural Product Research, 2019)

QTL analysis and candidate gene identification for plant height in cotton based on an interspecific backcross inbred line population of Gossypium hirsutum × Gossypium barbadense - Jianjiang Ma; Wenfeng Pei; Qifeng Ma; Yanhui Geng; Guoyuan Liu; Ji Liu; Yupeng Cui; Xia Zhang; Man Wu; Xingli Li; Dan Li; XinShan Zang; et al. (Theoretical and Applied Genetics, 2019)

Skin test of tuberculin purified protein derivatives with a dissolving microneedle-array patch - Wei Wang; Hou Ming Liu; Jing Zhou; Yu Guang Wang; Xi Feng; Hao Tang; Qinying Yan; Rong Sheng Zhu; Yu Wei Wu; Xing Guo Wang; Dan He; Fan Chen (Drug Delivery and Translational Research, 2019)

MicroRNA-377-3p inhibits growth and invasion through sponging JAG1 in ovarian cancer - Liulin Tang; Bin Yang; Xiaolan Cao; Qin Li; Li Jiang; Dan Wang (Genes & Genomics, 2019)

Anti-secretogranin III therapy of oxygen-induced retinopathy with optimal safety - Fen Tang; Michelle E. LeBlanc; Weiwen Wang; Dan Liang; Ping Chen; Tsung-Han Chou; Hong Tian; Wei Li (Angiogenesis, 2019)

Comparison of GPS-based precipitable water vapor using various reanalysis datasets for the coastal regions of China - Zhaoyang Wang; Xinghua Zhou; Zhe Xing; Qiuhua Tang; Dan Ma; Chao Ding (Theoretical and Applied Climatology, 2019)

RETRACTED ARTICLE: EDAR, LYPLAL1, PRDM16, PAX3, DKK1, TNFSF12, CACNA2D3, and SUPT3H gene variants influence facial morphology in a Eurasian population - Yi Li; Wenting Zhao; Dan Li; Xianming Tao; Ziyi Xiong; Jing Liu; Wei Zhang; Anquan Ji; Kun Tang; Fan Liu; Caixia Li (Human Genetics, 2019)

Paleogeomorphic genesis assembly method for paleogeomorphic recovery in the major region of the Tahe Oil Field, Tarim Basin, northwest China - Jianwen Cao; Zhonghua Tang; Qingyu Zhang; Yong Dan (Carbonates and Evaporites, 2019)

Reduced thiamine binding is a novel mechanism for TPK deficiency disorder - Wenjie Huang; Jiao Qin; Dingdong Liu; Yan Wang; Xiaofei Shen; Na Yang; Hui Zhou; Xiao-Tang Cai; Zhi-Ling Wang; Dan Yu; Rong Luo; Qingxiang Sun; et al. (Molecular Genetics and Genomics, 2019)

Integrated phytoremediation system for uranium-contaminated soils by adding a plant growth promoting bacterial mixture and mowing grass - Xin Qi; Xichao Hao; Xiaoming Chen; Shiqi Xiao; Shilin Chen; Xuegang Luo; Shanqiang Wang; Jia Tian; Dan Wang; Yunlai Tang (Journal of Soils and Sediments, 2019)

Detection and genetic characterization of porcine pegivirus from pigs in China - Dan Lei; Yu Ye; Kun Lin; Fanfan Zhang; Dongyan Huang; Kai Li; Weifeng Yuan; Qiong Wu; Zhen Ding; Leyi Wang; Deping Song; Yuxin Tang (Virus Genes, 2019)

Comparative transcriptome analysis in the hepatopancreas of Helice tientsinensis exposed to the toxic metal cadmium - Zhengfei Wang; Dan Tang; Linxia Sun; Xueling Shi; Ruobing Liu; Huayun Guo; Boping Tang (Genes & Genomics, 2019)

Mitochondrial OXPHOS genes provides insights into genetics basis of hypoxia adaptation in anchialine cave shrimps - Huayun Guo; Hao Yang; Yitao Tao; Dan Tang; Qiong Wu; Zhengfei Wang; Boping Tang (Genes & Genomics, 2018)

Clinical evaluation of a panel of multiplex quantitative real-time reverse transcription polymerase chain reaction assays for the detection of 16 respiratory viruses associated with community-acquired pneumonia - Dan Zhang; Haiyan Mao; Xiuyu Lou; Junhang Pan; Hao Yan; Hongfeng Tang; Yan Shu; Yun Zhao; Xiaoli Cheng; Hong Tao; Yanjun Zhang; Xuejun Ma (Archives of Virology, 2018)

Association of TRIMCyp and TRIM5α from assam macaques leads to a functional trade-off between HIV-1 and N-MLV inhibition - Dan Mu; Jia-Wu Zhu; Feng-Liang Liu; Hong-Yi Zheng; Yong-Tang Zheng (Science China Life Sciences, 2018)

Expression of BC1 Impairs Spatial Learning and Memory in Alzheimer’s Disease Via APP Translation - Tongmei Zhang; Pei Pang; Zemin Fang; Yu Guo; Hao Li; Xinyan Li; Tian Tian; Xin Yang; Wenting Chen; Shu Shu; Na Tang; Jianhua Wu; et al. (Molecular Neurobiology, 2018)

Effects of Urbanization, Soil Property and Vegetation Configuration on Soil Infiltration of Urban Forest in Changchun, Northeast China - Peijiang Wang; Haifeng Zheng; Zhibin Ren; Dan Zhang; Chang Zhai; Zhixia Mao; Ze Tang; Xingyuan He (Chinese Geographical Science, 2018)

Sorption-desorption behaviors of heavy metals by biochar-compost amendment with different ratios in contaminated wetland soil - Zhaoxue Yang; Jie Liang; Lin Tang; Guangming Zeng; Man Yu; Xiaodong Li; Xuemei Li; Yingying Qian; Haipeng Wu; Yuan Luo; Dan Mo (Journal of Soils and Sediments, 2018)

Evaluating environmental equities of urban forest in terms of cooling services using ETM+ and Google data - Ze Tang; Haifeng Zheng; Zhibin Ren; Dan Zhang; Peijiang Wang; Chang Zhai; Mingxing Cui; Xingyuan He (Journal of the Indian Society of Remote Sensing, 2018)

Avoidance of host resistance in the oviposition-site preferences of rose bitterling - Romain Rouchet; Carl Smith; Huanzhang Liu; Caroline Methling; Karel Douda; Dan Yu; Qionying Tang; Martin Reichard (Evolutionary Ecology, 2017)

Interleukin-18, matrix metalloproteinase-22 and -29 are independent risk factors of human coronary heart disease - Dong-Yi Jin; Cong-Lin Liu; Jun-Nan Tang; Zhao-Zhong Zhu; Xue-Xi Xuan; Xiao-Dan Zhu; Yun-Zhe Wang; Tian-Xia Zhang; De-Liang Shen; Xiao-Fang Wang; Guo-Ping Shi; Jin-Ying Zhang (Journal of Zhejiang University-SCIENCE B, 2017)

RETRACTED ARTICLE: Revisiting the male genetic landscape of China: a multi-center study of almost 38,000 Y-STR haplotypes - Michael Nothnagel; Guangyao Fan; Fei Guo; Yongfeng He; Yiping Hou; Shengping Hu; Jiang Huang; Xianhua Jiang; Wook Kim; Kicheol Kim; Chengtao Li; Hui Li; et al. (Human Genetics, 2017)

Neutrophil-To-Lymphocyte Ratio Predicts 3-Month Outcome of Acute Ischemic Stroke - Sen Qun; Yan Tang; Jing Sun; Zhaoxia Liu; Juncang Wu; Ji Zhang; Jidong Guo; Zhiqiang Xu; Dan Zhang; Zhengxu Chen; Fuyong Hu; Xingshun Xu; et al. (Neurotoxicity Research, 2017)

Genetic diversity and association analysis of Chinese chestnut (Castanea mollissima Blume) cultivars based on SSR markers - Xibing Jiang; Dan Tang; Bangchu Gong (Brazilian Journal of Botany, 2017)

Development and evaluation of a rapid recombinase polymerase amplification assay for detection of coxsackievirus A6 - Kaifeng Wang; Yue Wu; Dan Yin; Shixing Tang; Guifang Hu; Yaqing He (Archives of Virology, 2017)

The induction of apoptosis in SGC-7901 cells through the ROS-mediated mitochondrial dysfunction pathway by a Ir(III) complex - Cheng Zhang; Shang-Hai Lai; Chuan-Chuan Zeng; Bing Tang; Dan Wan; De-Gang Xing; Yun-Jun Liu (JBIC Journal of Biological Inorganic Chemistry, 2016)

Contra-directional Coupling of Nur77 and Nurr1 in Neurodegeneration: A Novel Mechanism for Memantine-Induced Anti-inflammation and Anti-mitochondrial Impairment - Xiaobo Wei; Huimin Gao; Jing Zou; Xu Liu; Dan Chen; Jinchi Liao; Yunqi Xu; Long Ma; Beisha Tang; Zhuohua Zhang; Xiang Cai; Kunling Jin; et al. (Molecular Neurobiology, 2016)

Lipopolysaccharide suppresses human immunodeficiency virus 1 reverse transcription in macrophages - Feng-Liang Liu; Jia-Wu Zhu; Dan Mu; Yong-Tang Zheng (Archives of Virology, 2016)

Identification and characterization of differentially expressed miRNAs between bamboo shoot and rhizome shoot - Qun-Ying Jin; Hua-Zheng Peng; Er-Pei Lin; Nan Li; Dan-Ni Huang; Yan-Li Xu; Xi-Qi Hua; Kui-Hong Wang; Tang-Jun Zhu (Journal of Plant Biology, 2016)

Identification of JAZ1-MYC2 Complex in Lotus corniculatus - Meiliang Zhou; Zhanmin Sun; Jinbo Li; Dan Wang; Yixiong Tang; Yanmin Wu (Journal of Plant Growth Regulation, 2016)

Pacificimonas aurantium sp. nov., Isolated from the Seawater of the Pacific Ocean - Shuhui Li; Wenchu Zhou; Dan Lin; Kai Tang; Nianzhi Jiao (Current Microbiology, 2016)

Levels and distribution of organochlorine pesticides and hexachlorobutadiene in soils and terrestrial organisms from a former pesticide-producing area in Southwest China - Zhenwu Tang; Qifei Huang; Zhiqiang Nie; Yufei Yang; Jun Yang; Dan Qu; Jiali Cheng (Stochastic Environmental Research and Risk Assessment, 2016)

Phase 1 clinical trial demonstrated that MUC1 positive metastatic seminal vesicle cancer can be effectively eradicated by modified Anti-MUC1 chimeric antigen receptor transduced T cells - Fengtao You; Licui Jiang; Bozhen Zhang; Qiang Lu; Qiao Zhou; Xiaoyang Liao; Hong Wu; Kaiqi Du; Youcai Zhu; Huimin Meng; Zhishu Gong; Yunhui Zong; et al. (Science China Life Sciences, 2016)

Estimation of soil reinforcement by the roots of four post-dam prevailing grass species in the riparian zone of Three Gorges Reservoir, China - Rong-hua Zhong; Xiu-bin He; Yu-hai Bao; Qiang Tang; Jin-zhang Gao; Dan-dan Yan; Ming-feng Wang; Yu Li (Journal of Mountain Science, 2016)

Vascular endothelial growth factor-C protects heart from ischemia/reperfusion injury by inhibiting cardiomyocyte apoptosis - Xu-guang Chen; Yan-xia Lv; Dan Zhao; Lei Zhang; Fei Zheng; Jian-Ye Yang; Xiao-lin Li; Lu Wang; Lin-Yun Guo; Ya-mu Pan; Yu-wen Yan; Shi-You Chen; et al. (Molecular and Cellular Biochemistry, 2016)

The complete mitochondrial genome of fall armyworm Spodoptera frugiperda (Lepidoptera:Noctuidae) - Qiu-Ning Liu; Xin-Yue Chai; Dan-Dan Bian; Bao-Ming Ge; Chun-Lin Zhou; Bo-Ping Tang (Genes & Genomics, 2016)

MiR-219 Protects Against Seizure in the Kainic Acid Model of Epilepsy - Honghua Zheng; Rong Tang; Yi Yao; Zhilin Ji; Yuanyuan Cao; Zhaoji Liu; Feng Peng; Wenjie Wang; Dan Can; Huiqin Xing; Guojun Bu; Huaxi Xu; et al. (Molecular Neurobiology, 2016)

Two new eunicellin diterpenoids from the South China Sea gorgonian Muricella sibogae and their bioactivities - Xing-Wang Zhang; Xu-Li Tang; Hong-Rui Yuan; Dan-Qing Feng; Pei Su; Ping-Lin Li; Guo-Qiang Li (Natural Product Research, 2015)

Erratum to: Mining for low-nitrogen tolerance genes by integrating meta-analysis and large-scale gene expression data from maize - Bowen Luo; Haitao Tang; Hailan Liu; Shunzong Su; Suzhi Zhang; Ling Wu; Dan Liu; Shibin Gao (Euphytica, 2015)

Mining for low-nitrogen tolerance genes by integrating meta-analysis and large-scale gene expression data from maize - Bowen Luo; Haitao Tang; Hailan Liu; Su Shunzong; Suzhi Zhang; Ling Wu; Dan Liu; Shibin Gao (Euphytica, 2015)

Seasonal and interannual variations of carbon exchange over a rice-wheat rotation system on the North China Plain - Chen Chen; Dan Li; Zhiqiu Gao; Jianwu Tang; Xiaofeng Guo; Linlin Wang; Bingcheng Wan (Advances in Atmospheric Sciences, 2015)

Analysis of the Drought Stress-Responsive Transcriptome of Black Cottonwood (Populus trichocarpa) Using Deep RNA Sequencing - Sha Tang; Yan Dong; Dan Liang; Zhoujia Zhang; Chu-Yu Ye; Peng Shuai; Xiao Han; Ying Zhao; Weilun Yin; Xinli Xia (Plant Molecular Biology Reporter, 2015)

Mechanical force and tensile strain activated hepatic stellate cells and inhibited retinol metabolism - Su-Hong Yi; Yi Zhang; Dan Tang; Liang Zhu (Biotechnology Letters, 2015)

Regional integrated environmental modeling system: development and application - Shuyu Wang; Congbin Fu; Helin Wei; Yun Qian; Zhe Xiong; Jinming Feng; Deming Zhao; Li Dan; Zhiwei Han; Bingkai Su; Ming Zhao; Yaocun Zhang; et al. (Climatic Change, 2015)

Analysis of DNA methylation of perennial ryegrass under drought using the methylation-sensitive amplification polymorphism (MSAP) technique - Xiao-Mei Tang; Xiang Tao; Yan Wang; Dong-Wei Ma; Dan Li; Hong Yang; Xin-Rong Ma (Molecular Genetics and Genomics, 2014)

A prepared anti-MSTN polyclonal antibody reverses insulin resistance of diet-induced obese rats via regulation of PI3K/Akt/mTOR&FoxO1 signal pathways - Liang Tang; Chen-tao Liu; Xu-dan Wang; Kai Luo; Di-di Zhang; Ai-ping Chi; Jing Zhang; Li-jun Sun (Biotechnology Letters, 2014)

Characterizing the heavy metal-complexing potential of fluorescent water-extractable organic matter from composted municipal solid wastes using fluorescence excitation–emission matrix spectra coupled with parallel factor analysis - Xiao-Song He; Bei-Dou Xi; Hong-Wei Pan; Xiang Li; Dan Li; Dong-Yu Cui; Wen-Bin Tang; Ying Yuan (Environmental Science and Pollution Research, 2014)

Debris flow susceptibility assessment using a probabilistic approach: A case study in the Longchi area, Sichuan province, China - Ming Chang; Chuan Tang; Dan-dan Zhang; Guo-chao Ma (Journal of Mountain Science, 2014)

Effect of dietary lysine on growth, intestinal enzymes activities and antioxidant status of sub-adult grass carp (Ctenopharyngodon idella) - Xue-Yin Li; Ling Tang; Kai Hu; Yang Liu; Wei-Dan Jiang; Jun Jiang; Pei Wu; Gang-Fu Chen; Shu-Hong Li; Sheng-Yao Kuang; Lin Feng; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2014)

Over-expression of CXCR4 on mesenchymal stem cells protect against experimental colitis via immunomodulatory functions in impaired tissue - Xingxing Liu; Dongmei Zuo; Heng Fan; Qing Tang; Zhexing Shou; Dan Cao; Zhou Zou (Journal of Molecular Histology, 2014)

Geochronology and geochemistry of the Late Triassic Longtan pluton in South China: termination of the crustal melting and Indosinian orogenesis - Liang Qiu; Dan-Ping Yan; Mei-Fu Zhou; Nicholas T. Arndt; Shuang-Li Tang; Liang Qi (International Journal of Earth Sciences, 2014)

Calycosin entered HUVECs and ameliorated AGEs-promoted cell apoptosis via the Bcl-2 pathway - You-Hua Xu; Jianfeng Xiong; Shan-Shan Wang; Dan Tang; Ru-Shang Wang; Quan Zhu (Journal of Natural Medicines, 2014)

Lithium Chloride Alleviates Neurodegeneration Partly by Inhibiting Activity of GSK3β in a SCA3 Drosophila Model - Dan-Dan Jia; Li Zhang; Zhao Chen; Chun-Rong Wang; Feng-Zhen Huang; Ran-Hui Duan; Kun Xia; Bei-Sha Tang; Hong Jiang (The Cerebellum, 2013)

GSK-3β Polymorphism Discriminates Bipolar Disorder and Schizophrenia: A Systematic Meta-Analysis - Hui Tang; Na Shen; Huijuan Jin; Dan Liu; Xiaoping Miao; Ling-Qiang Zhu (Molecular Neurobiology, 2013)

Correlation of the cyclin A expression level with porcine circovirus type 2 propagation efficiency - Qinghai Tang; Shengbin Li; Hui Zhang; Yanwu Wei; Hongli Wu; Jianbo Liu; Yiping Wang; Dan Liu; Zhihui Zhang; Changming Liu (Archives of Virology, 2013)

In vivo study on the effects of curcumin on the expression profiles of anti-tumour genes (VEGF, CyclinD1 and CDK4) in liver of rats injected with DEN - Chu Zhu Huang; Wei Zhe Huang; Ge Zhang; Dan Ling Tang (Molecular Biology Reports, 2013)

RNA interference mediated pten knock-down inhibit the formation of polycystic ovary - Jie-Xiu Ouyang; Tao Luo; Hui-Yun Sun; Jian Huang; Dan-Feng Tang; Lei Wu; Yue-Hui Zheng; Li-Ping Zheng (Molecular and Cellular Biochemistry, 2013)

RETRACTED ARTICLE: Spironolactone inhibits apoptosis in rat mesangial cells under hyperglycaemic conditions via the Wnt signalling pathway - Dan Zhu; Hongwei Yu; Hongjiang He; Jiuli Ding; Jie Tang; Dan Cao; Lirong Hao (Molecular and Cellular Biochemistry, 2013)

Re-Examination of the Genotoxic Activity of Water Taken From the Songhua River in P. R. China - Jia Yu; Hong-Wei Dong; Li-Tian Shi; Hui-Ling Jiang; Jian-Wen Yu; Qian-Wen Zhao; Shi-Chun Cai; Dan Han; Xuan-Yue Tang; Jia-Ren Liu (Archives of Environmental Contamination and Toxicology, 2013)

The association between a single nucleotide polymorphism rs11966200 in MHC region and clinical features of generalized vitiligo in Chinese Han population - Jin Tang; Jian Lan Liu; Cheng Zhang; Da Yan Hu; Su Min He; Xian Bo Zuo; Pei Guang Wang; Liang Dan Sun; Xue Jun Zhang; Sen Yang (Molecular Biology Reports, 2013)

Melatonin Attenuates Scopolamine-Induced Memory/Synaptic Disorder by Rescuing EPACs/miR-124/Egr1 Pathway - Xiong Wang; Zhi-Hao Wang; Yuan-Yuan Wu; Hui Tang; Lu Tan; Xiang Wang; Xin-Ya Gao; Yan-Si Xiong; Dan Liu; Jian-Zhi Wang; Ling-Qiang Zhu (Molecular Neurobiology, 2013)

Global climate change will severely decrease potential distribution of the East Asian coldwater fish Rhynchocypris oxycephalus (Actinopterygii, Cyprinidae) - Dan Yu; Ming Chen; Zhuocheng Zhou; Rochard Eric; Qiongying Tang; Huanzhang Liu (Hydrobiologia, 2013)

Over-expression of integrin-linked kinase correlates with aberrant expression of Snail, E-cadherin and N-cadherin in oral squamous cell carcinoma: implications in tumor progression and metastasis - Dan Zhao; Xiu-Fa Tang; Kai Yang; Ji-Yuan Liu; Xiang-Rui Ma (Clinical & Experimental Metastasis, 2012)

Mitochondrial capture and incomplete lineage sorting in the diversification of balitorine loaches (Cypriniformes, Balitoridae) revealed by mitochondrial and nuclear genes - Qiong‐Ying Tang; Si‐Qing Liu; Dan Yu; Huan‐Zhang Liu; Patrick D. Danley (Zoologica Scripta, 2012)
Tang, Q.‐Y., Liu, S.‐Q., Yu, D., Liu, H.‐Z. & Danley, P.D. (2012) Mitochondrial capture and incomplete lineage sorting in the diversification of balitorine loaches (Cypriniformes, Balitoridae) revealed by mitochondrial and nuclear genes. — Zoologica Scripta , 41 , 233–247. Understanding the diversification of species is a central goal of evolutionary biological studies. One powerful tool to investigate the speciation process is molecular systematics. Here, we use molecular methods to investigate the evolution of balitorine loaches belonging to two genera, Lepturichthys and Jinshaia. Both genera contain only two species ( Lepturichthys fimbriata, Lepturichthys dolichopterus and Jinshaia sinensis and Jinshaia abbreviata ), all of which are endemic to China. These species share many morphological and ecological characters and exhibit overlapping distributions in the Upper Yangtze River. In this study, we used two mitochondrial genes (Cyt b and COI) and one nuclear gene (RAG1) to investigate the phylogenetic relationships within and between these two genera. Phylogenetic analyses and network construction based on mitochondrial and nuclear genes consistently supported the monophyly of Jinshaia . In contrast, the mitochondrial and nuclear genes yielded conflicting results in Lepturichthys . The phylogenetic analyses of mitochondrial sequences identify two distinct Lepturichthys lineages, Lepturichthys A and Lepturichthys B. Lepturichthys A includes most of L. fimbriata individuals from the Upper Yangtze River and is the sister group to all Jinshaia species. Lepturichthys B consists of the remaining L. fimbriata individuals from the Upper and Middle Yangtze River, and all L. dolichopterus individuals from the Minjiang River in Southeastern China. However, the analysis of the nuclear sequence indicates that the genus Lepturichthys is monophyletic and is only distantly related to Jinshaia . This incongruence suggests that introgressive hybridization might have occurred between L. fimbriata ( Lepturichthys A) and Jinshaia species. As a result of this hybridization event, L. fimbriata captured the mitochondrial genome of the sympatric Jinshaia species. This capture event appears to have occurred at least 1.74 million years ago. Additionally, L. fimbriata appears to be paraphyletic; the nuclear data indicated that L. dolichopterus forms a monophyletic clade nested within L. fimbriata . Because L. dolichopterus and L. fimbriata are allopatric and hybridization may not be possible, we suggest that the observed paraphyly of L. fimbriata is a product of incomplete lineage sorting. In addition, the reciprocal monophyly of J. sinensis and J. abbreviata could not be resolved. This may be the result of interspecific hybridization as these species occur sympatrically. However, incomplete lineage sorting may have caused the observed topology of the Jinshaia species. The data presented here illustrate the complex evolutionary history of the balitorine loach species: intergeneric hybridization and interspecific hybridization have likely occurred in this lineage. In addition, possible incomplete lineage sorting may further obscure the evolutionary history of this group. The complex relationships of the balitorine loaches provide a rich evolutionary system to study the creation of sympatric and sister species.

Enhanced thermal-tolerance of photosystem II by elevating root zone temperature in Prunus mira Koehne seedlings - Hai-Ping Hao; Chuang-Dao Jiang; Shou-Ren Zhang; Yu-Dan Tang; Lei Shi (Plant and Soil, 2012)

High-level expression of bioactive recombinant human lysozyme in the milk of transgenic mice using a modified human lactoferrin BAC - Shen Liu; Xiangqing Li; Dan Lu; Shengzhe Shang; Meili Wang; Min Zheng; Ran Zhang; Bo Tang; Qiuyan Li; Yunping Dai; Ning Li (Transgenic Research, 2012)

Protection by Vanadium, a Contemporary Treatment Approach to Both Diabetes and Focal Cerebral Ischemia in Rats - Zhenquan Liu; Pengtao Li; Dan Zhao; Huiling Tang; Jianyou Guo (Biological Trace Element Research, 2012)

Enhanced biodesulfurization by expression of dibenzothiophene uptake genes in Rhodococcus erythropolis - Ze-long Wang; Dan Wang; Qiang Li; Wang-liang Li; Huang Tang; Jian-min Xing (World Journal of Microbiology and Biotechnology, 2011)

Transgenic Brassica napus L. lines carrying a two gene construct demonstrate enhanced resistance against Plutella xylostella and Sclerotinia sclerotiorum - Hongbo Liu; Xiang Guo; Muhammad S. Naeem; Dan Liu; Ling Xu; Wenfang Zhang; Guixiang Tang; Weijun Zhou (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Heterologous Expression of a Gibberellin 2-Oxidase Gene from Arabidopsis thaliana Enhanced the Photosynthesis Capacity in Brassica napus L. - Bo Zhou; Dan Peng; Jianzhong Lin; Xingqun Huang; Wusheng Peng; Reqing He; Ming Guo; Dongying Tang; Xiaoying Zhao; Xuanming Liu (Journal of Plant Biology, 2011)

EEG dynamics reflects the partial and holistic effects in mental imagery generation - Jian Li; Yi-yuan Tang; Li Zhou; Qing-bao Yu; Song Li; Sui Dan-ni (Journal of Zhejiang University-SCIENCE B, 2010)

The woody plant poplar has a functionally conserved salt overly sensitive pathway in response to salinity stress - Ren-Jie Tang; Hua Liu; Yan Bao; Qun-Dan Lv; Lei Yang; Hong-Xia Zhang (Plant Molecular Biology, 2010)

Novel SNPs of the Caprine Growth Hormone Secretagogue Receptor (GHSR) Gene and Their Association with Growth Traits in Goats - Qijiang Jin; Xing Tang Fang; Liu Yang; Chun Lei Zhang; Jia Jie Sun; Dan Xia Chen; X. Y. Shi; Yu Du; Chuchao Lei; Hong Chen (Biochemical Genetics, 2010)

Over-expression of the AtGA2ox8 gene decreases the biomass accumulation and lignification in rapeseed (Brassica napus L.) - Xiao-ying Zhao; Deng-feng Zhu; Bo Zhou; Wu-sheng Peng; Jian-zhong Lin; Xing-qun Huang; Re-qing He; Yu-hong Zhuo; Dan Peng; Dong-ying Tang; Ming-fang Li; Xuan-ming Liu (Journal of Zhejiang University-SCIENCE B, 2010)

Biodelignification of rice straw by Phanerochaete chrysosporium in the presence of dirhamnolipid - Yun-Shan Liang; Xing-Zhong Yuan; Guang-Ming Zeng; Chen-Lu Hu; Hua Zhong; Dan-Lian Huang; Lin Tang; Jia-Jia Zhao (Biodegradation, 2010)

Characterization of CIMMYT bread wheats for high- and low-molecular weight glutenin subunits and other quality-related genes with SDS-PAGE, RP-HPLC and molecular markers - Dan Liang; Jianwei Tang; Roberto Javier Peña; Ravi Singh; Xinyao He; Xiaoyong Shen; Danian Yao; Xianchun Xia; Zhonghu He (Euphytica, 2010)

Bioassay-guided separation of the proinflammatory constituents from the roots of Euphorbia kansui - Xiaoyun Shu; Li Yu; Yuping Tang; Li Zhang; Anwei Ding; Dan Luo; Jin-ao Duan; Xiangchun Shen (Journal of Natural Medicines, 2010)

Sequencing the Potato Genome: Outline and First Results to Come from the Elucidation of the Sequence of the World’s Third Most Important Food Crop - Richard G. F. Visser; Christian W. B. Bachem; Jan M. de Boer; Glenn J. Bryan; Swarup K. Chakrabati; Sergio Feingold; Robert Gromadka; Roeland C. H. J. van Ham; Sanwen Huang; Jeanne M. E. Jacobs; Boris Kuznetsov; Paulo E. de Melo; et al. (American Journal of Potato Research, 2009)

Natural environment suitability for human settlements in China based on GIS - Zhiming Feng; Yanzhao Yang; Dan Zhang; Yan Tang (Journal of Geographical Sciences, 2009)

Use of a novel anti-proliferative compound coated on a biopolymer to mitigate platelet-derived growth factor-induced proliferation in human aortic smooth muscle cells: comparison with sirolimus - Yong-Dan Tang; Ambarish Pandey; Antonina Kolmakova; Xin-Tong Wang; Subbu S. Venkatraman; Subroto Chatterjee; Freddy Y. C. Boey (Glycoconjugate Journal, 2009)

Association of the DRD2 and DRD3 polymorphisms with response to pramipexole in Parkinson’s disease patients - Ying-Zi Liu; Bei-Sha Tang; Xin-Xiang Yan; Jie Liu; Dong-Sheng Ouyang; Li-Nuo Nie; Lan Fan; Zhi Li; Wei Ji; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

The involvement of sortase A in high virulence of STSS-causing Streptococcus suis serotype 2 - Changjun Wang; Ming Li; Youjun Feng; Feng Zheng; Yaqing Dong; Xiuzhen Pan; Gong Cheng; Ruiping Dong; Dan Hu; Xiaodan Feng; Junchao Ge; Di Liu; et al. (Archives of Microbiology, 2009)

Analysing the vegetation cover variation of China from AVHRR‐NDVI data - Xiaoguang Jiang; Dan Wang; Lingli Tang; Jian Hu; Xiaohuan Xi (International Journal of Remote Sensing, 2008)

Relief degree of land surface and its influence on population distribution in China - Zhiming Feng; Yan Tang; Yanzhao Yang; Dan Zhang (Journal of Geographical Sciences, 2008)

Expression of motilin in the hypothalamus and the effect of central erythromycin on gastric motility in diabetic rats - Yun-Dan Jia; Chang-Qin Liu; Ming Tang; Zheng-Yao Jiang (Neuroscience Bulletin, 2007)

Secreted Expression and Purification of Dengue 2 Virus Full-length Nonstructural Glycoprotein NS1 in Pichia. pastoris - Jun-mei Zhou; Yun-xia Tang; Dan-yun Fang; Jing-jiao Zhou; Yu Liang; Hui-yu Guo; Li-fang Jiang (Virus Genes, 2006)

Development of mariculture and its impacts in Chinese coastal waters - Yang Yu Feng; Li Chun Hou; Nie Xiang Ping; Tang Dan Ling; Chung Ik Kyo (Reviews in Fish Biology and Fisheries, 2004)

A GIS-based research on the distribution of rural settlements in Yulin of northern Shaanxi - Zhao Mu-dan; Tang Guo-an; Shi Wen-zhong; Liu Yong-mei (Journal of Geographical Sciences, 2002)

Evaluation on the accuracy of digital elevation models - Tang Guo-an; Josef Strobl; Gong Jian-ya; Zhao Mu-dan; Chen Zhen-jiang (Journal of Geographical Sciences, 2001)

Involving of the cytoplasmic region of leukemia inhibitory factor receptor α subunit, IL-6 related signal transducer-gp130 or Fas death domain for MAPK p42/44 activation in HL-60 cell with LIF or anti-Fas IgG - Houqi Liu; Jikuan Dan; Shuping Tang; Shaorong Wu (Molecular and Cellular Biochemistry, 2001)